Lychee seed extract improves growth performance and hepatic health in largemouth bass (Micropterus salmoides) fed high-fat diets: Novel insights from network pharmacology and in vivo validation - Zhenye Lin; Qi Li; Wenjie Chu; Shuling Bai; Shan Xie; Xiaotong Chen; Hao Chen; Zhipeng Zheng; Jiandong Zhu; Yongxin Liu; Yingying Yu; Tengfei Zhu (Aquaculture, 2027)

A reappraisal of the role of just transition in Taiwan’s 2050 net-zero pathway - Anton Ming-Zhi Gao; Jui-Chu Lin; Chien-Te Fan; Tsung Kuang Yeh; Jong-Shun Chen; Chao-Ning Liao (Energy and Climate Change, 2026)

MEK inhibitor cobimetinib increases calreticulin and induces immune modulation in TNBC - Ling-Ming Tseng; Ka-Yi Lau; Ji-Lin Chen; Pei-Yi Chu; Chun-Teng Huang; Wan-Lun Wang; Yuan-Ya Chang; Jiun-I Lai; Chi-Cheng Huang; Ming-Shen Dai; Chun-Yu Liu (Journal of Molecular Medicine, 2026)
Immunogenic cell death (ICD) can activate immune cells and potentiate the response to immunotherapy. The mitogen-activated protein kinase (MAPK) signaling pathway regulates the immune response and mediates T-cell receptor signaling. Activation of the MAPK signaling pathway decreases the levels of tumor-infiltrating lymphocytes in triple-negative breast cancer (TNBC) and is associated with worse survival. Here, we investigated the potential of the MEK inhibitor cobimetinib as an ICD inducer in TNBC. We demonstrated that cobimetinib elicited hallmarks of ICD, including elevated levels of damage-associated molecular patterns. Ectopic ERK expression attenuated cobimetinib-induced CRT. Cobimetinib also evoked caspase-8 activation with increased Bax and Bak expression, while caspase inhibitor suppressed cobimetinib-induced CRT expression and apoptosis. In immunocompetent (BALB/c) mice bearing 4T1 tumors, cobimetinib exhibited stronger tumor growth inhibition than in immunodeficient (nude) mice, suggesting an immune-dependent antitumor effect. Furthermore, cobimetinib treatment increased the proportions of naïve CD8 + T cells and effector CD4 + T cells and decreases the proportion of myeloid-derived suppressor cells in immunocompetent mice bearing 4T1 tumors. Notably, we observed differential immunomodulatory effects of cobimetinib in tumor-bearing mice compared to non–tumor-bearing immunocompetent mice. Our findings indicate that MEK inhibition is associated with ICD-related molecular alterations, and that cobimetinib may contribute to immune modulation in TNBC.

MiR-4327 targets TP53 to promote cervical cancer cell proliferation - Mei-Lin Chen; Chen-Yang Chu; Feng-Xian Zhang; Li-Pei Zhang; Ying Yang; Bai-Zhao Peng; Chuang-Hai Wu; Xiao-Mei Chen; Yan-Ting You; Bing-Ying Rong; Hiu Yee Kwan; Xiao-Shan Zhao; et al. (Functional & Integrative Genomics, 2026)
Cervical cancer is a leading cause of female malignancy worldwide. While microRNA-4327 (miR-4327) has been implicated as a potential oncogene, its functional role and molecular mechanisms in cervical cancer pathogenesis remain unclear. This study aimed to determine the oncogenic function of miR-4327 and elucidate its downstream regulatory mechanism in cervical cancer pathogenesis. We measured miR-4327 expression in clinical cervical cancer tissues and cell lines using quantitative real-time PCR (qRT-PCR). We then assessed its effects on proliferation, migration, invasion, and cell cycle progression through functional assays including cell counting kit-8 (CCK-8), colony formation, transwell, and flow cytometry. To evaluate tumor growth in vivo, we established a xenograft model in non-obese diabetic (NOD)-severe combined immune-deficient (scid) mice. Using bioinformatic analysis and luciferase reporter assays, we identified TP53 as a direct target of miR-4327 and further validated this regulatory relationship with gain- and loss-of-function experiments. We found that miR-4327 was significantly upregulated in cervical cancer and promoted malignant phenotypes such as proliferation, migration, invasion, and cell cycle progression in vitro. Consistent with this, overexpression of miR-4327 accelerated tumor growth in vivo. Mechanistically, we confirmed TP53 as a direct functional target of miR-4327. Knocking down TP53 phenocopied the oncogenic effects of miR-4327, while restoring TP53 expression rescued the tumor-promoting effects mediated by miR-4327. These findings reveal a novel miR-4327/TP53 regulatory axis and nominate miR-4327 as a potential therapeutic target for intervention.

Synchronous Paleo-Tethys closure in northern Iran: Constraints from Paleozoic-Mesozoic sediments in the western Alborz - Yiyang Lei; Yang Chu; Mark B. Allen; Wei Lin; Bo Wan; Ling Chen; Morteza Talebian; Guangyao Xin; Tanjie Liu; Yilin Guo; Lin Guo; Ranran Xia (Journal of Asian Earth Sciences, 2026)

Flower-centric temperature control: Optimizing osmanthus black tea aroma via environmental temperature regulation of floral vitality and enzymatic responses - Lin Xiang; Ahua Jie; Jian Lu; Jingjing Zhang; Dong Wang; Ying Zhou; Haowei Guo; Xinyu Feng; Weihong Huang; Guohua Ren; Qiang Chu; Ping Chen (Food Research International, 2026)

Chronic exposure to chlorate at regulatory safety limits induces p21/p16-mediated neuronal senescence and Parkinsonian-like decline - Cai-Jhen Wu; Chien-Tai Hong; Jiun-Lin Horng; Hung-Shao Lai; Hao-Yu Tsai; Tsorng-Harn Fong; Chen-Yuan Hsiao; Cheng-Ying Chu; Yvonne Jing Mei Liew; Tien-Chun Yang (Environmental Pollution, 2026)

Interfacial charge redistribution at ZnSe/V2O5 heterojunction encapsulated in N, P-doped carbon enables high-performance wide-temperature Zn-air batteries - Mingjie Yi; Shuanghui Lv; Leqian Chu; Jingwen Zhang; Lijun Lin; Liangqi Gui; Jing Huang; Jiaheng Zhang (Chemical Engineering Journal, 2026)

Xylarols A–G, structurally diverse specialized metabolites from mangrove endophytic fungus Xylaria sp. AH-75 and their anti-colorectal cancer activities - Dongmei Lin; Chengyan Chu; Falei Zhang; Xinghao Xu; Yue Li; Ziqian Liao; Xuanzheng Yue; Hanqi Zhang; Yuanyuan Feng; Huixiang Yang; Xiaolong Yang (Phytochemistry, 2026)

Research on mission planning method for self-propelled buoys under time-varying tidal current disturbances - Kehao Zhang; Mao Zheng; Xiumin Chu; Shigan Ding; Tianyue Zou; Bowen Lin (Ocean Engineering, 2026)

Nano-island Cu–Cu2O heterojunctions: Synergistic electroreduction of bromate at mixed-valence perimeters - Yu Chu; Junjie Li; Huihuan Lin; Binyu Ma; Zhipeng Luo; Yue Cheng; Xin Yu; Huabin Zeng (Journal of Water Process Engineering, 2026)

A photoreactor coupled with an elliptical reflector for boosting the advanced oxidation process - Shao-En Lin; Li-Kang Chu (Journal of Water Process Engineering, 2026)

Protein and polyphenol structure transformation persuade “colloid-suspension” phase conversion in green tea beverages - Xinxin Wang; Lin Wang; Yunqing Liu; Yani Pan; Xinyu Feng; Wenzhi Ling; Xiangru Wang; Sitong Zhong; Yili Shen; Ranran Zhao; Yuefei Wang; Ping Chen; et al. (Food Chemistry, 2026)

Newly identified TRAF7 interacts with TAK1 and regulates immune response in Chlamys farreri - Xiaoxue Lin; Zihao Zhang; Xiaolong Chu; Fengchen Liu; Kaixin Zhao; Qinghua Jin; Xiaotong Wang (Fish & Shellfish Immunology, 2026)

DataNet: linking multi-faceted building energy datasets for effective performance analysis at scale - Hye-Gi Kim; Hyery Shin; Han-Gyeong Chu; Dong Hyuk Yi; Sang-Lin Park; Doosung Kim; Hyunwoo Lim; Sungmin Yoon; Eui-Jong Kim; Jaewan Joe; Sunsook Kim; Hyeunguk Ahn; et al. (Energy and Buildings, 2026)

Decoupling of surface and lithospheric sutures, a review of Early Mesozoic Sulu UHP orogenic belt, eastern China - Lingtong Meng; Wei Lin; Yang Chu; Wei Wei; Lin Wu (Earth-Science Reviews, 2026)

Epitaxial high-entropy relaxor ferroelectric films for flexible piezoelectric sensors and MEMS - Yu-En Pan; Yu-Hao Tu; Li-Hui Tsao; Yu-Ju Lin; Sheng-Yao Hung; Yi-Chun Chen; Mengyao Xiao; Qibin Zeng; Huajun Liu; Chengkuo Lee; Ying-Hao Chu (Chemical Engineering Journal, 2026)

Low-carbon cork agglomerated materials via chitosan/blocked isocyanate adhesive: Cross-linking mechanism, high performance, and life cycle assessment - Jiaxing Zhang; Jingjing Li; Yibo Li; Yifan Yan; Yao Yi; Jing Yuan; Lin Chen; Tonghua Ma; Xiaobing Xie; Zheyun Liu; Shulei Li; Shilin Xu; et al. (Bioresource Technology, 2026)

A sunscreen UV filter disrupts energy homeostasis and impairs growth in the endangered living fossil Tachypleus tridentatus - Guangjin Li; Yiting Li; Xingda Lin; Shiyong Wang; Meijiao Yan; Yaoyao Chu; Chuihong Fang; Zhi Chen; Fengxiao Hu (Journal of Hazardous Materials, 2026)

Divergent effects of phosphate salts on advanced glycation end-product formation in minced pork during commercial sterilization - Li Lin; JuanJuan Zhang; Fuyu Chu; Keqiang Lai; Yiqun Huang (Food Chemistry, 2026)

PFAS associated with dysglycemia and glucose trajectories: a prospective cohort study from the Isomers of C8 Health Project in China - Wen-Qi Yang; Yun-Ting Zhang; Wen-Yu Wang; Haseeb Tufail Moryani; Muhammad Amjad; Zeeshan Mohammed; Xuan Liu; Yan-Xu Chen; Kun Zhao; Chu Chu; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Corrigendum to “Mg-doped CoCr₂O₄ nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage” [Chem. Eng. J. 535 (2026) 175200] - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

Enhanced oil adsorption from high-viscosity polymer-flooding produced wastewater by ionizing radiation pretreatment - Jiaxuan Lin; Libing Chu; Jianlong Wang; Qi Yang (Chemical Engineering Journal, 2026)

Assessing SUEWS-simulated near-surface air temperature and humidity using a paired forcing-validation framework in Xiong’an New Area - Lin Zhou; Guanwen Chen; Hua Yuan; Jian Hang; Jiajia Hua; Manrui Xue; Tian Chu; Yitao Guo; Liyue Zeng (Building and Environment, 2026)

Weather source heterogeneity affects disease forecasting: A case study of rice bacterial leaf blight in Taiwan - Jie-Hao Ou; Guo-Cih Lin; Yea-Fang Wu; Chi-Yu Chen; Guan-Ying Huang; Hau-Ping Chou; Chien-Chih Kuo; Hsin-Yuh Wu; Qiao-Juan Lai; Chih-Wei Wang; Yi-Chen Tsai; Chang-Hsin Kuo; et al. (Agricultural and Forest Meteorology, 2026)

Species Divergence in Oxytocin-Dependent Yawning on a Conserved Glutamatergic Erection Circuit - Yan-Chu-Fei Zhang; Qing-Wu Zheng; Yang Lu; Hao-Yuan Wang; Jiao Cang; Xin-Rui Wu; Lin-Yao Fan; Liang Li; Ni-Na Zhang; Xiao-Yang Zhang; Jing-Ning Zhu; Jian Jing; et al. (Neuroscience Bulletin, 2026)
Yawning coupled with penile erection is a conserved neurobehavioral syndrome mediated by the paraventricular hypothalamus (PVH). However, the distinct roles of oxytocin and its co-transmitters remain unresolved. Using chemogenetics, we showed that activation of PVH oxytocin neurons was sufficient to elicit both responses, whereas silencing these neurons abolished them. Viral tracing revealed that these neurons project collaterally to the brainstem reticular nucleus and spinal cord to spatially coordinate autonomic and somatic motor outputs. By dissecting the molecular mechanisms using CRISPR-Cas9, we found that vesicular glutamate transporter 2 (VGLUT2)-dependent glutamatergic transmission provides the primary drive for both behaviors, whereas the oxytocin peptide is selectively required for yawning but dispensable for erection. Comparative analyses across rats, hamsters, and mice demonstrated that while the glutamatergic erectile circuit was conserved, mice lacked spontaneous yawning and were resistant to apomorphine-induced yawning. These findings suggest a hierarchical co-transmission framework in which fast glutamatergic signaling provides the core drive, while oxytocin confers behavioral specificity.

Ameliorative effects of dietary curcuminoid supplementation on high-carbohydrate-diet-induced hepatic lipid metabolic disorders in largemouth bass (Micropterus salmoides) - Zhenye Lin; Zhipeng Zheng; Hongmian Mao; Wenjie Chu; Xiaotong Chen; Shan Xie; Shuling Bai; Qi Li; Hao Chen; Yongxin Liu; Jiandong Zhu; Tengfei Zhu; et al. (Aquaculture, 2026)

Self-cleaning van der Waals lamination for two-dimensional electronics - Chang Liu; Shuimei Ding; Xudong Wang; Guichen Teng; Jinhua Zeng; Ying Zhang; Qianru Zhao; Huiting Wang; Binmin Wu; Shuaiqin Wu; Yan Chen; Tie Lin; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Optimization of extraction process for active component (dihydromyricetin) from industrial crop vine tea (Ampelopsis grossedentata) and its potential application in functional products for alleviating intestinal inflammation - Zhongxing Chu; Zuomin Hu; Jinping Ding; Yaping Zhou; Feijun Luo; Qinlu Lin (Food Bioscience, 2026)

Principle Verification and Engineering Design of a Stable Negative-Pressure Fish Harvesting System - Lin Liqun; Zhang Yaoming; Zuo Mingliang; Xu Zhiqiang; Huang Wenyun; Chu Shupo (Aquacultural Engineering, 2026)

Insular divergence and host-associated diversification in ovoid-gall Daphnephila (Diptera: Cecidomyiidae) from Taiwan, with description of a new species - Sheng-Feng Lin; Tung-Chuan Chiang; Hsuan Chang; Yu-Chu Weng; Man-Miao Yang (Applied Entomology and Zoology, 2026)
The Old World cecidomyiid genus Daphnephila is primarily associated with Machilus (Lauraceae) plants and exhibits exceptionally high gall diversity in Taiwan. At present, six described species correspond to only seven of 40 known Daphnephila gall morphospecies on the island. In this study, we clarified the species identities of Taiwanese Daphnephila inducing long ovoid-galls and ovoid-galls on the leaves of five Machilus plants, and explored their diversification using molecular evidence. Accordingly, two species, D. yukawai sp. n. and D. taiwanensis , were recognized based on morphological characteristics and species delimitation method (Assemble Species by Automatic Partitioning). The former species utilizes only the endemic M . mushaensis , primarily inducing ovoid-galls along the major leaf vein, whereas the latter species associates with five Machilus species and induces two gall types on various leaf parts. Notably, when sympatric with D. yukawai sp. n., D. taiwanensis exhibits character displacement of galling habit, forming long ovoid-galls along the minor leaf veins. Furthermore, the COI-based IQ tree supported: (1) a single origin of East Asian ovoid-gall Daphnephila species, (2) the sister-group relationship between the Taiwanese lineage and a Chinese species, and (3) the role of M. mushaensis as the probable ancestral host of the Taiwanese lineage, including D. taiwanensis. These results suggest that D. taiwanensis colonized additional Machilus hosts after diverging from D. yukawai sp. n. Taken together, our findings indicate that novel plant associations and shifts in galling sites may have facilitated diversification in Daphnephila cecidomyiids, contributing to the remarkable richness of Daphnephila galls in Taiwan.

Integrative analysis of Huangjing-Gegen compatibility in treating COPD: a network pharmacology, molecular docking, and experimental study - Shaoqing Zhu; Jiaruo Li; Lin Chu; Yunpeng Zhu; Wei Wang; Man Wang; Zhenhua Zhu; Fei Mao; Pengjun Liu; Ying Chu (Natural Product Research, 2026)

Financing decarbonization targets: The role of Clean Development Mechanism projects in China's urban transition - Baoju Chu; Yunze Zhuo; Lingke Ai; Leyan Zeng; Shuyuan Lin (Environmental Impact Assessment Review, 2026)

Effects of microplastic-antibiotic composite pollution on photosynthetic responses in cucumber (Cucumis sativus L.) - Menglin Wang; Yajun Mao; Yiwen Chu; Ziyu Lin; Zhenxia Li (Plant and Soil, 2026)

The Spatial and Temporal Variability of the Clear Convective Boundary Layer at the ARM SGP Supersite - Yufei Chu; Zhien Wang; Min Deng; Guo Lin; Lulin Xue; Weiwei Li; Hyeyum Hailey Shin; Colby M. Brabec (Advances in Atmospheric Sciences, 2026)

Pharmacological effect of rhCC16 on COPD: anti-senescence via the PI3K-AKT-mTOR pathway - Rui Gao; Shuo Wu; Chu-lin Zhang; Chao-feng Liu; Ting Li; Min Guo; Zhao-yang Chen; Hai-long Wang; Min Pang (Molecular and Cellular Biochemistry, 2026)

Investigating the mechanisms of Suzijiangqi Pill in COPD intervention through UPLC Q-Exactive Orbitrap MS, network pharmacology, and animal experiments - Wei Wang; Shaoqing Zhu; Lin Chu; Yunpeng Zhu; Huan Yang (Natural Product Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Experimental performance analysis of inland vessel remote operation: A case study on the Yangtze River - Tianyue Zou; Mao Zheng; Xiumin Chu; Mengxia Li; Shigan Ding; Kehao Zhang; Tuyuan Xu; Bowen Lin; Yougui Yang (Ocean Engineering, 2026)

Synthesizing high-performance zeolite X from coal gangue for flue gas CO2 capture - Jiahao Liu; Xianghao Li; Xinru Zhang; Nien-Chu Lai; Zeyi Jiang; Lin Lin; Xinxin Zhang (Journal of Environmental Chemical Engineering, 2026)

Fine-scale post-fire forest recovery patterns and compound drivers in Taiwan’s high-mountain national parks - Chu-Chia Kuo; Yu-Ling Liu; Cheng-Tao Lin (Forest Ecology and Management, 2026)

Pt(II) complexes with narrow-spectrum emission for high-performance green organic light-emitting diodes - Qinghua Xia; Yong Cao; Yihan Chu; Yang Li; Xuanbo Hu; Jinyu Song; Cong Zhang; Xiao-Chun Hang; Lin Xu (Chemical Engineering Journal, 2026)

A novel Curcuma wenyujin-derived fructan modulates gut microbiota and metabolic pathways to ameliorate DSS-induced colitis - Zijun Li; Zhen Li; Liuxi Chu; Shiyu Hu; Chang Xue; Huixin Lin; Yawen Luo; Yihui Zhang; Jian Zhang; Zhouguang Wang (Carbohydrate Polymers, 2026)

Applications of machine learning in enhancing evaporation estimation for small reservoirs: a case study in semi-arid South Texas - Syed Muhammad Fahad Abdullah; Chu-Lin Cheng; Jude Benavides; Jungseok Ho; Rafael M. Almeida (Modeling Earth Systems and Environment, 2026)

Learning to follow: An end-to-end deep learning approach for vision-based vessel control - Shigan Ding; Mao Zheng; Nan Hai; Xiumin Chu; Bowen Lin; Tianyue Zou; Kehao Zhang; Wubin Hua; Lingyu Fu (Ocean Engineering, 2026)

Mutual information guided domain adaptation network for unsupervised transfer fault diagnosis of offshore wind turbines under time-varying conditions and scarce labels - Yun Kong; Guoyu Huang; Cuiying Lin; Haiqiang Wang; Qinkai Han; Junyu Qi; Hui Liu; Fulei Chu (Ocean Engineering, 2026)

Late Quaternary occurrences of Zoophycos in a high sedimentation rate setting on the continental margin off southwestern Taiwan: Implications for trace maker ecology - Ludvig Löwemark; Radha Krishna Pillutla; Andrew Tien-Shun Lin; Jen-Chu Yeh; Gueorgui Ratzov; Nathalie Babonneau; Shu-Kun Hsu; Chih-Chieh Su; Serge Lallemand; Wan-Ling Tseng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Biodegradable facilitation mimics extend the window of opportunity for salt marsh establishment - Zhaohui Li; Yuan Xu; Xianye Wang; Jian Shen; Siyuan Ma; Xiangqian Chu; Zhiyuan Zhao; Yanchen Yin; Xiaosong Xi; Lingli Wang; Lin Yuan (Journal of Environmental Management, 2026)

Mg-doped CoCr2O4 nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

Comparative Online–offline measurement of airborne toxic VOCs for health risk and source identification in an environmental justice community - Hsin-Cheng Hsieh; Yuan-Chang Su; Sheng-Po Chen; Chen-Hsuan Chu; Mei-Hui Tseng; Kuan-Chun Lee; Po-Sheng Tseng; Pei-Hsuan Hsu; Chih-Chung Chang; Chieh-Heng Wang; Jia-Lin Wang (Atmospheric Environment, 2026)

The vinculin-β-catenin axis promotes bone formation and repair: an essential prerequisite for the anti-osteoporotic efficacy of sclerostin-neutralizing antibody - Sixiong Lin; Chu Tao; Yishu Wang; Jianglong Li; YuJia Shi; Qinnan Yan; Yiming Zhong; Huanqing Gao; Tingxuan Wang; Yibo Wang; Qing Yao; Jianmei Huang; et al. (Science China Life Sciences, 2026)

Metabarcoding Chironomid Pupal Exuviae Enables Scalable Biomonitoring With High Comparability to Morphotaxonomy - Wu Han; Chu‐Ming Zhang; Cheng Qian; Tsz‐Ying Chan; Thilina S. Nimalrathna; Bai‐an Lin; Xiao‐Long Lin; Hong‐Qu Tang; Peter S. Cranston; Mathew Seymour (Molecular Ecology, 2026)
Conventional morphotaxonomy‐based biomonitoring requires modernization to enable timely assessments in the face of an accelerating freshwater biodiversity crisis. The Chironomid Pupal Exuviae Technique (CPET) is an established biomonitoring approach with considerable potential for integration with molecular methods, as the shed pupal skins of emerging adults provide a source of DNA. We tested the performance of DNA metabarcoding for detecting species richness, recovering beta‐diversity patterns and assessing biodiversity responses to environmental gradients using 15 mock communities and 12 natural chironomid pupal exuviae samples collected from Hong Kong streams. Additionally, the effects of primer choice were assessed by comparing a chironomid‐specific primer set (COI‐S) against a universal, highly degenerate primer set (COI‐V). Our results show that both primer sets achieved high species detection rates in mock communities (86% and 84%, respectively) and consistently recovered predefined community dissimilarities. In natural community samples, however, only COI‐S produced beta‐diversity patterns significantly congruent with that of the morphological dataset (Procrustes r = 0.74, p = 0.003). Both metabarcoding datasets effectively captured seasonal community shifts and demonstrated greater sensitivity to environmental gradients than traditional morphological identification. Notably, the COI‐S dataset explained the highest proportion of community variation (adjusted R 2 = 44.3%), along the environmental gradient, outperforming both the morphotaxonomy (32.5%) and the COI‐V (29.0%) analyses. Here we propose Meta‐CPET, an integrated framework that combines the ecological relevance of CPET with the efficiency, scalability, and resolution of DNA metabarcoding. Our findings show that bulk‐sample metabarcoding enables practical, standardized and large‐scale freshwater biomonitoring while maintaining strong comparability with conventional methods.

Regulation of EMT and cholangiocarcinoma metastasis by KIN17 through the mTOR signaling pathway - Yuxia Yang; Qianying Luo; Chuhong Huang; Xiaocong Lin; Lok Ting Chu; Qiuyan Li; Jinjing Tang; Tao Zeng (Molecular and Cellular Biochemistry, 2026)

An LLM-driven Agent framework for resilient modulus prediction: Integrating modified consistency index model and residual compensation - Xuanxuan Chu; Wenjun Zhang; Ling Zhao; Lin Tang; Hongjian Cai; Chengchao Guo (Transportation Geotechnics, 2026)

Comprehensive understanding of new particle formation in China through advanced modeling - Jiewen Shen; Bin Zhao; An Ning; Wei Nie; Chao Yan; Yuyang Li; Runlong Cai; Alfonso Saiz-Lopez; Manish Shrivastava; Biwu Chu; Da Gao; Nanna Myllys; et al. (Science Bulletin, 2026)

HDAC5 mediates the regulation of muscle-derived interleukin 6 on the differentiation of porcine intramuscular pre-adipocytes - Weimin Lin; Hongbing Song; Chongfan Du; Jing Wang; Xiaohan Zhang; Chu Yang; Tianfang Xiao; Ruiyi Lin (Domestic Animal Endocrinology, 2026)

Chlorine-resistant high-entropy spinel oxide catalyst for efficient and durable seawater anion exchange membrane water electrolysis - Thi Xuyen Nguyen; Ting-You Shih; Ngoc Thanh Thuy Tran; Thanh Tuan Nguyen; Yi-Chuan Chu; Bo-Han Lai; Chun-Kuo Peng; Yu-Ru Lin; Yan-Gu Lin; Kao-Shu Chuang; Jeng-Kuei Chang; Thi Y Phung Nguyen; et al. (Chemical Engineering Journal, 2026)

Review of National Laws and Regulations in China in Relation to the Precautionary Approach to Fisheries Management - Xiao‐lin Chu (Fisheries Management and Ecology, 2026)
The precautionary approach has been widely accepted as an important guideline in international, regional, and national fisheries management. The United Nations Fish Stocks Agreement provided a foundational framework for the application of the precautionary approach in fisheries management. Several Regional Fisheries Management Organizations explicitly referenced the precautionary approach in their conventions. Additionally, several significant fishing countries integrated the precautionary approach into their domestic legislation and actively implemented a precautionary approach in practice. However, China has not yet formally integrated the precautionary approach into its fishery legislation and management practices. Given the acceptance and effectiveness of the precautionary approach in fisheries management globally, China should incorporate the precautionary approach into its legislative and administrative frameworks for fisheries. We reviewed current Chinese laws and regulations for the precautionary approach and identified gaps, challenges, and opportunities for the precautionary approach and recommend the application of the precautionary approach in China's fisheries management. Recent advances in China's fisheries management, including the ongoing revision of the Fishery Law and the fishery quota system pilot program, established favorable circumstances for the potential adoption of the precautionary approach.

Targeting the gut-liver axis with dietary polyphenols to ameliorate metabolic dysfunction-associated steatotic liver disease: advances in molecular mechanisms - Zuomin Hu; Zeyu He; Yuyan Wang; Zhongxing Chu; Yaping Zhou; Wen Li; Jun Lu; Qinlu Lin; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2026)

Interactive effects of retinal biomarkers and sleep on cognition: longitudinal evidence from community-dwelling older adults - Ting-Wen Chu; Yi-Ting Hsieh; Jeng-Min Chiou; Yao-Lin Liu; Yen-Ching Chen; Jen-Hau Chen (GeroScience, 2026)

Establishment of a spinal cord-derived cell line from Micropterus salmoides reveals differential host-pathogen interactions and innate immune evasion strategies - Xin Chu; Lingyun Lin; Jinpeng Gong; Mingyue Gao; Jinyu Shen; Yan Zhang; Xiaoyi Pan (Aquaculture, 2026)

Association between perfluoroalkyl and polyfluoroalkyl substances exposure and reproductive longevity for female in the United States: A population-based study - Anhui Ning; Feng Shao; Qingzheng Yang; Yiqian Ren; Shenxuan Zhou; Jinfeng Lin; Minjie Chu; Yan Zhang (Toxicology Letters, 2026)

Late quaternary eruption history of the Tatun Volcano Group (Taiwan) – new constraints from zircon double-dating and 40Ar/39Ar dating of lava flows in Mt. Shamao - Karl D. Jabagat; Yuan-Hsi Lee; Martin Danišík; Daniel Miggins; Mei-Fei Chu; Yu-Ming Lai; Yun-Chieh Lo; Po-Tsun Lee; Cheng-Horng Lin (Tectonophysics, 2026)

Retrieving forest LAI from Landsat via 3D look-up table generated by realistic LiDAR scenes - Jianbo Qi; Siying He; Xun Zhao; Su Ye; Tianjia Chu; Zhexiu Yu; Simei Lin; Huaguo Huang (Remote Sensing of Environment, 2026)

Prenatal and postpartum residential greenness and behavioral development in early Childhood: Findings from a birth cohort - Wen-Chi Chao; Ming-Lun Zou; Chih-Da Wu; Jian-Pei Huang; Heng-Kien Au; Chen-Li Lin; Shih-Peng Mao; Hsing-Jasmine Chao; Ling-Chu Chien; Hsueh-Wen Hsu; Pilyoung Kim; Yi-Hua Chen (Environmental Research, 2026)

Noise-resistant automatic seismic framework for monitoring rockslide slope - Chung-Ray Chu; Chiao-Yin Lu; Guan-Wei Lin; En-Jui Lee; Che-Hsin Liu; Chih-Hsin Chang; Hsiao-Yu Huang (Engineering Geology, 2026)

Sensitivity of soil hydrothermal dynamics to soil organic matter in CLM5.0 in permafrost regions on the Qinghai–Tibet plateau - Jiajie Peng; Yuxin Zhang; Lin Zhao; Shuhua Yang; Guojie Hu; Minxuan Xiao; Xiaoyu Chu; Xuchun Yan; Yao Xiao; Xiangfei Li (Theoretical and Applied Climatology, 2026)

Effects of Three Microbiome-Based Therapies on Loperamide-Induced Constipation in Mice by Restoring Intestinal Motility and Modulating the Intestinal Microbiota - Xinfeng Bai; Lin Xu; Kai Wang; Lei Chen; Tianyu Bai; Peipei Li; Weihua Chu; Chao Song (Probiotics and Antimicrobial Proteins, 2026)

Boron and oxygen isotopes fractionation between borate minerals and fluids and implications for borate deposit formation - Da-Sheng Zuo; Hai-Zhen Wei; Jian-Jun Lu; M.R. Palmer; A.E. Williams-Jones; Jun-Lin Wang; Shao-Yong Jiang; Ke Yang; He-Feng Lin; Simon V. Hohl; Yi-Chu Chen (Applied Geochemistry, 2026)

Cigarette smoking combines with genetic variants to regulate FOXN3 and associate with bladder cancer risk - Yiwen Zheng; Youhan Wu; Jinyue Zhang; Chenfei Zhao; Tianqin Wang; Qunbo Wang; Qiang Lv; Chao Qin; Lin Yuan; Haiyan Chu; Mulong Du; Meilin Wang; et al. (Archives of Toxicology, 2026)

Disentangling meteorological and emission drivers of PM2.5 and bridging the gap to WHO guideline: A case study in an underdeveloped ethnic minority County in Southwest China - Xuling Ma; Yanlin Chu; Yi Li; Ying Wang; Weili Lin (Air Quality, Atmosphere & Health, 2026)

Inflammation mediates the association between per- and polyfluoroalkyl substance exposure and kidney function: Integrating epidemiological and animal evidence - Li-Xia Liang; Wen-Wen Bao; Chu Chu; Lu-Yin Wu; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Jing-Wen Huang; Li-Zi Lin; Yang Zhou; Ling-Zhang Meng; Kun Ye; et al. (Journal of Hazardous Materials, 2026)

Construction of a multilayer perceptron based intelligent platform for dynamic quality monitoring and shelf-life prediction of bivalves - Yi Yuan; Songyi Lin; Xiuping Dong; Bo Liu; Haiyou Dong; Jiaxin Qiang; Junbo Chu; Simin Zhang (Food Chemistry, 2026)

Molecular and functional characterization of interleukin-1β in red drum (Sciaenops ocellatus) and its pivotal role in antibacterial immunity - Lin Zhang; Jinglu Ma; Jingyao Yu; Qing Chu (Fish & Shellfish Immunology, 2026)

Organic substitution for synthetic fertilizer mitigates the negative effects of warming on soil quality, greenhouse gas emissions, and soybean yields - Xiaoyu Wang; Jiangsen Chu; Mengyou Zhang; Mingjun Hou; Ke Zheng; Leili Lin; Zhengjun Yan; Xiaoxiao Li; Zhao Che; He Song; Gong Wu (Field Crops Research, 2026)

Custom hydrogen-bond network grants hydrogel superior zinc-anode stability - Kun Zheng; Yang Zhang; Jialin Wang; Lin Wang; Jian Chu; Yi Wang; Jinhui Song (Chemical Engineering Journal, 2026)

Additive-mediated controlled growth of printed perovskite for planar and heterostructure solar cells - Anjali Thakran; Yen-Yu Wang; Rohan Paste; Atul Dhage; Yu-Te Chen; Mario Hofmann; Yu-Jung Lu; Chung Hsin Lu; Shih- I. Lu; Yan-Duo Lin; Chih Wei Chu (Chemical Engineering Journal, 2026)

Injectable near-infrared–responsive silk fibroin nanocomposite hydrogel enabling spatiotemporally controlled photothermal chemotherapy - Ling-Chu Yang; Ching-Wen Hwang; Shao-Hsuan Tsao; Hsin-Yao Lin; Yunching Chen; Dehui Wan (Chemical Engineering Journal, 2026)

Melatonin suppresses glycolysis and coordinately disrupts DNA repair via targeting the YAP1-NAMPT signaling in breast cancer - Yi-Wen Lai; Cheng-Ying Chu; Zei-Wei Liu; Hsin-Ying Lu; Chi-Ching Lee; Mei-Hsiang Lin; Cheng-Wei Lin (Chemico-Biological Interactions, 2026)

Dual phosphorylation of DISC1 at Ser58 and Ser713 regulates polarization of cortical neurons via GSK3β - Jun Ren; Yiliang Xu; Lin Yuan; Yingxin Liu; Qian Chu; Tian Zhao; Wei Zhang; Jing Tian; Shi-Qiang Wang; Haihong Ye (Science China Life Sciences, 2026)

Nitrogen thresholds for coastal Casuarina equisetifolia: Soil acidification and microbial shifts drive restoration limits - Wei Chu; Yue Guo; ZongNan Wu; YanYan Wang; MingMei Wu; ZeYan Wu; WenXiong Lin (Applied Soil Ecology, 2026)

Tai Chi modulating multimodal connectivity patterns and cognitive function in cerebral small vessel disease - Xiaoyong Zhong; Zhongpeng Dai; Liuxi Chu; Hongliang Zhou; Wanqing Lin; Bin Chen (GeroScience, 2026)

Pooled data from phase 3 clinical trials comparing the clinical activity of ceftolozane/tazobactam versus meropenem for the treatment of complicated intra-abdominal infections - Zhiqiang Li; Yue Kang; Hongqiang Gao; Yingpeng Zhao; Ding Luo; Dongdong Wang; Xiang Zhang; Jieqi Yu; Guang Chu; Jun Cao; Fan Wang; Xiongqi Zhao; et al. (Infectious Diseases, 2026)

Two novel TRAF homologs are implicated in the immunological response and interact with IRAK in the Zhikong scallop (Chlamys farreri) - Jiwen Chen; Wei Chen; Yifan Qu; Xiaoxue Lin; Haikun Zhang; Jilv Ma; Jie Cui; Fengchen Liu; Zhongyi Chu; Yue Zhao; Yabin Wang; Yaqiong Liu; et al. (Aquaculture, 2026)

Characteristics and generation mechanisms of tremors across a mountain belt - Yi-Chu Hua; Kate Huihsuan Chen; Satoshi Ide; Pei-Ying Patty Lin (Tectonophysics, 2026)

Early Cretaceous shortening event recorded by the emplacement of the Tiantai pluton, Eastern South China Block - Ran An; Wei Wei; Wei Lin; Chao Song; Yang Chu (Tectonophysics, 2026)

FINDER: Flow-aware intelligent navigation through distilled experience and reinforcement learning for UUVs in complex flow fields - Shuguang Chu; Haihan Feng; Yuheng Ou; Mingwei Lin; Dejun Li (Ocean Engineering, 2026)

Combined exposure to microplastics and cadmium alters gut microbiota composition in preschool children: A cross-sectional study - Chi-Sian Kao; Chuen-Bin Jiang; Chih-Chieh Yang; Ying-Lin Wang; Yi-Hua Chen; Hsing Jasmine Chao; Hsing-Cheng Hsi; Ling-Chu Chien (Journal of Hazardous Materials, 2026)

Sustainable soil management in acidic paddy fields: liming and biochar application reduce greenhouse gas emissions while enhancing rice yields - Gong Wu; Xiaoyu Wang; Xing Wei; Mengyou Zhang; Jiangseng Chu; Mingjun Hou; Leili Lin; Yang Chen; Zhao Che; Xiaoxiao Li; Can Zhang; He Song (Journal of Environmental Management, 2026)

Quadratic polynomial prediction model-based isotope-coded equivalent reporter ion assay: A novel single-calibration LC–MS/MS strategy for sensitive quantification of steroidal sapogenin isomers in functional foods - Yue-Cai Hou; Chu Chen; Xiao-Feng Huang; Lin-Sen Qing (Food Chemistry, 2026)

Differential associations of PFAS in follicular fluid and serum with reproductive hormones: Insights from a Chinese IVF cohort GIVES - Kun Zhao; Chu Chu; Michael S. Bloom; Jian-Ping Cong; Marjut Roponen; Pasi Jalava; Mo Yang; Wan-Ting He; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2026)

Sulfone site enables H2O2 practical fabrication over metal-free photocatalyst - Zhi-Peng Tao; Lin Liu; Ke-Chao Wang; Chen-Ning Li; Jia-Qi Chu; Zhen-Hui Kang; Zheng-Bo Han (Chemical Engineering Journal, 2026)

Applying Interpretable Machine Learning for Hypoxia Mitigation: an Operational Framework Coupling Predictive Modeling and Causal Inference for Urban River Management - Jia-yun Chen; Da-wei Wang; Zu-lin Hua; Ke-jian Chu; Li Gu (Water Resources Management, 2026)

A1-Reactive Astrocytes in the Posterior Part of Paraventricular Thalamic Nucleus Are Involved in Pain Modulation in Mice - Han-Xue Sun; Zhong-Yi Liu; Jia-Ni Li; Liu-Jie Zhao; Xue-Mei Wu; Chu-Han Liu; Jie Hong; Ke-Hua Zhu; Feng-Ling Wu; Si-Hai Chen; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2026)

AMPK Activation by ENERGI Ameliorates Behavioral and Synaptic Deficits in a Mouse Model of Autism - Ming-Chia Chu; Chi-Chun Wu; Yueh-Jung Chung; Chieh-Yu Chang; Han-Fang Wu; Sze-Chi Tsai; Tzu-Ning Peng; Tzu-Jung Yang; Hui-Ching Lin (Molecular Neurobiology, 2026)
Autism spectrum disorder (ASD), a neurodevelopmental disorder, is characterized by synaptic dysregulation as its underlying pathophysiological mechanism. AMP-activated protein kinase (AMPK), an intracellular energy sensor, plays a pivotal role in regulating synaptic integrity and function. Current treatments for ASD exhibit limited benefits in alleviating the core symptoms of ASD. Consequently, we investigated the therapeutic potential of ENERGI, a novel AMPK-activating compound, in a valproate (VPA)-induced mouse model of ASD. ENERGI was administered via drinking water to VPA-induced ASD offspring. After 7 days of treatment, ENERGI gradually alleviated social defects, repetitive behaviors, and emotional comorbidities in VPA-induced ASD offspring. At the synaptic level, ENERGI treatment restored aberrant plasticity, spine structure, and dendritic arborization in the hippocampus of VPA-induced ASD offspring. Notably, the curative effects of ENERGI in VPA-induced ASD offspring were equivalent to those of D-cycloserine (DCS), a known therapeutic candidate for ASD. Moreover, ENERGI demonstrated superior efficacy in restoring spine abnormalities than DCS. Mechanistically, 7-day ENERGI treatment reversed the reduction in AMPK phosphorylation, and normalized the elevated PSD95 and synaptic GluA2 levels in VPA-induced ASD offspring, whereas DCS treatment only rescued the synaptic GluA2 levels. Overall, these findings suggest that AMPK activation by ENERGI effectively reverses behavioral and synaptic deficits in a preclinical ASD model, supporting AMPK as a promising target for developing novel ASD therapies.

Pilot study on integrating multidisciplinary technologies to implement an autonomous and smart harvester for asparagus - Joe-Air Jiang; Jen-Cheng Wang; Hung-Jen Lin; Cheng-Ying Chou; Chia-Chun Chien; Wei-Hao Huang; An-Chi Liu; Cheng-Chun Lee; Ming-Chi Guo; Jui-Chu Peng (Computers and Electronics in Agriculture, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Rhizobacteria-mediated phenolic acid degradation alleviates replant stress in Casuarina equisetifolia via multi-level soil–plant regulation - Wei Chu; YanYan Wang; MingMei Wu; ZongNan Wu; LiuTing Zhou; Zi Wang; ZeYan Wu; WenXiong Lin (Rhizosphere, 2025)

Late Permian strike-slip tectonics in the northern North China Craton: new insights from geological and geophysical data of the Longwangmiao granitic pluton - Chao Song; Wei Lin; Wei Wei; Lingtong Meng; Yang Chu; Qinying Wu; Zhao Guo; Yin Wang; Ran An; Fei Liu; Jinhui Yang (Journal of Asian Earth Sciences, 2025)

Probabilistic health risk assessment of rare earth elements through rice (Oryza sativa L.) consumption using Monte Carlo simulation - Zzu-Ying Huang; Chien-Hui Syu; Lin-Chu Chien; Zeng-Yei Hseu (Food Chemistry, 2025)

Impacts of the extent of pasteurization treatments on advanced glycation end-products in fish steaks: Initial heating, storage, and reheating - Linzhi TAN; Lin LI; Fuyu CHU; Keqiang LAI; Yiqun HUANG (Food Chemistry, 2025)

Uncovering AphBvp-mediated regulation of PirAvp/PirBvp toxins and biofilm formation in AHPND causing Vibrio parahaemolyticus - Michael Eniola Ayenero; Ramya Kumar; Han-Ching Wang; Phuoc Thien Le; Yu-Hsuan Chen; Chu Fang Lo; Shin-Jen Lin; Hao-Ching Wang (Fish & Shellfish Immunology, 2025)

Uncovering the gene regulation of PirAvp and PirBvp toxins in AHPND causing Vibrio parahaemolyticus - Shin Jen Lin; Chu Fang Lo; Hao Ching Wang (Fish & Shellfish Immunology, 2025)

Fermented Broussonetia papyrifera leaves on growth performance, immune responses, and resistance to Vibrio of shrimp - Guan-Lin Lai; Yu-Ru Lin; Ta-Jeng Yang; Yu-Ting Chu; Fan-Hua Nan; Yeh-Fang Hu (Fish & Shellfish Immunology, 2025)

Effects of feed supplementation with fermented Broussonetia papyrifera leaves on non-specific immune responses, resistance to Vibrio parahaemolyticus, growth, intestinal histology, and microbiota of white shrimp (Penaeus vannamei) - Guan-Lin Lai; Yu-Ru Lin; Ta-Jeng Yang; Yu-Ting Chu; Fan-Hua Nan; Yeh-Fang Hu (Fish & Shellfish Immunology, 2025)

Alkylammonium ligands-driven perovskite lattice engineering for white perovskite nanocrystals single emitters - Jean-Sébastien Bénas; Zhen-Li Yan; Wei-Cheng Chen; Chu-Chen Chueh; Jing-Yan Wu; Wei-Wen Chen; Fang-Cheng Liang; Erdi Akman; Yu-Jung Lu; Yen-Yu Wang; Ja-Hon Lin; Ye Zhou; et al. (Chemical Engineering Journal, 2025)

Covalent organic frameworks with synergistic linkages and functional groups boost electrochemiluminescence for sensitive detection of long non-coding RNA - Linlin Song; Lin Cui; Xiaoran Zou; Xueting Cao; Wenqi Chu; Wenjie Gao; Lin Cheng; Bing Sun; Chun-yang Zhang (Chemical Engineering Journal, 2025)

Exploring the protein complexity of lipid droplets in DHA-producing Schizochytrium sp. and potential applications of lipid droplet-associated proteins in lipid production - Chu-Bin Lin; Jun-Jie Wu; Xue-Qiang Chen; Jia-Xue Zhao; Shan Jiang; Xue-Rong Zhou; Peng-Yang Liu; Feng-Hong Huang; Xia Wan (Chemical Engineering Journal, 2025)

Assessment of habitat characteristics in typical seagrass bed ecosystems along the coast of Changhai County, Dalian - Yuchen Chu; Jun Yang; Juncheng Yin; Jie Tian; Jun Song; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; Yanjun Wang; Qian Sun; Quanxiang Meng; et al. (Acta Oceanologica Sinica, 2025)

Joint Scheduling of New Energy Hybrid Tugboats and Berths Under Shore Power Constraint - Liangyong Chu; Jiachen Lin; Xiyao Xu; Zihao Yang; Qiuping Yang (Journal of Marine Science and Engineering, 2025)
With the rapid advancement of battery technology, new energy hybrid tugboats have been progressively adopted. In order to align with the trend of electrifying tugboat fleets, a mixed-integer linear programming (MILP) model for the joint scheduling of new energy hybrid tugboats and berths has been established. The model incorporates the constraint imposed by the limited number of tugboat charging connectors. The objective is to minimize the total cost over the scheduling horizon, including ship waiting, delayed-departure costs, and the operating costs of both conventional diesel and hybrid tugboats. In light of the characteristics inherent to the problem, a hybrid solution approach combining CPLEX with a heuristic-enhanced whale optimization algorithm (WOA) is employed to solve the model. A case study was conducted using data on the energy consumption of tugboats at Xiamen Port. The effectiveness of the model and algorithm was then verified through a series of small-scale instance experiments. Finally, a comprehensive sensitivity analysis of key parameters is finally conducted, including the number of tugboat charging connectors, battery capacity, and charging rate. This analysis provides valuable guidance for port tugboat operations.

Research on Acoustic-Electrical Integrated Technology in Geothermal Resource Exploration, Development and Monitoring - Feng Chu; Rui Xu; Rong-hua Zhang; Yi-guo Xue; Deng-rui Wu; Lin-zhi Lang; Shu-ge Liu; Jing-kai Qu (Applied Geophysics, 2025)

The germline POLD1 c.1420 C > A (p.Leu474Ile) variant segregates with endometrial cancer, colorectal cancer and colonic polyps demonstrating hypermutation and defective POLD1 mutational signatures - Daniel D. Buchanan; Peter Georgeson; Romy Walker; Jihoon E. Joo; Mark Clendenning; Julia Como; Ryan O’Keeffe; Alysha Prisc; Yen Lin Chu; Mark A. Jenkins; Christophe Rosty; Ingrid M. Winship; et al. (Familial Cancer, 2025)

Exploring the management of the pelagic tuna fisheries in China: Evolution, challenges and recommendations - Xiao-lin CHU (Fisheries Research, 2025)

Geotechnical reconnaissance of Hualien Port after the 2024 ML 7.2 hualien earthquake - Hsuan-Chih Yang; Chun-Jia Huang; Yung-Yen Ko; Kuan-Yu Chen; Chi-Chin Tsai; Chun-Hung Lin; Yu Wei Hwang; Min-Chien Chu; Yu-Syuan Jhuo; Yu-Ting Hsueh; Shodai Okano; LeeYi Wang; et al. (Soil Dynamics and Earthquake Engineering, 2025)

Quality enhancement of batter-coated oysters via low temperature vacuum frying technique and machine learning-based prediction models for shelf life and quality dynamics - Junbo Chu; Songyi Lin; Xiuping Dong; Bo Liu; Haiyou Dong; Simin Zhang (Food Chemistry, 2025)

A practical approach for assessing damage to bolted steel connections after fires and earthquakes - Heui-Yung Chang; Chi Wei Li; Chu-Tsen Liao; Ker-Chun Lin; Chi-Ming Lai (Engineering Structures, 2025)

The proteo- and chitinolytic coordinate mechanisms of Streptomyces sp. SCUT-3 and its application in chitinous wastes recycling - Ming-Shu Zhang; Zhi-Wei Li; Lei Wu; Zi-Yang Luo; Can Qin; Fu-Gen Zhang; Chu-Yan Liang; Hai-Ning Wang; De-Lin Lu; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Light-capture capability based flexible negative pyramid microarrays coated with silver nano-islands for SERS detection - Chia-Hsien Lin; Yun-Chu Chen; Kuan-Syun Wang; Ding-Jia Yueh; Shih-Hsien Yeh; Jeng-Shiung Chen; Yung-Hsin Cheng; Yuh-Lin Wang; Ting-Yu Liu (Chemical Engineering Journal, 2025)

Influences of sub-zero temperature on dynamic tensile behavior of rhyolite porphyry - Zilong Zhou; Fanjunhui Mo; Xin Cai; Chu Wang; Chunping Lin; Yuanping Lai; Shaohui Tang; Zhongkang Wang (Cold Regions Science and Technology, 2025)

Study on the transition mechanisms of tensile mechanical properties and fracture patterns in frozen sandstone - Zilong Zhou; Cuigang Chen; Xin Cai; Chu Wang; Peiyu Wang; Jifeng Yuan; Chunping Lin (Cold Regions Science and Technology, 2025)

Morphology of the subgenital plate gland in Solenopsis males (Hymenoptera, Formicidae) - Chu Wang; Fu-Ya Chung; Chung-Chi Lin; Johan Billen (Arthropod Structure & Development, 2025)

Application of weight prediction for Holstein dairy cows in non-pregnant and postpartum stages - Hsin-I Chiang; Jia-Ming Zhou; Wen-Lin Chu (Biosystems Engineering, 2025)

Characterization of SiIκB confirms the existence of a conserved IκB–NF-κB regulatory mechanism in sea urchin Strongylocentrotus intermedius - Yifan Qu; Yan Gao; Jie Cui; Haikun Zhang; Fengchen Liu; Xiaoxue Lin; Zhongyi Chu; Yaqiong Liu; Yijing Han; Baoyu Huang; Xiaotong Wang (Fish & Shellfish Immunology, 2025)

Interfacial engineering meets process optimization: Highly stable silicon-graphite anodes via pre-calendering polyvinylidene difluoride-MgO coatings - Chu-Chun Lin; Cheng-Che Chien; Yu-Ting Weng; Chia-Chen Fang; Nae-Lih Wu; Rainer Adelung; Mozaffar Abdollahifar; Ryo Takata; Carlos Eduardo Alarcón-Suesca; Franz Schmidt (Chemical Engineering Journal, 2025)

Carbon nanotube/two-dimensional metal–organic framework composites with enhanced thermoelectric performances for thermoelectric generators - Cheng-Yuan Lin; Jhe-Wei Chang; Meng-Hao Lin; Kuan-Chu Wu; Shao-Huan Hong; Jhih-Min Lin; Chung-Wei Kung; Cheng-Liang Liu (Chemical Engineering Journal, 2025)

Sensitive enzymatic cycling assay for glutathione and glutathione disulfide content - Xinyue Lin; Yajun Chu; Qianhe Xu; Qiuying Nie; Cui Xu; Jianguo Fang; Junmin Zhang (Analytica Chimica Acta, 2025)

Integrating machine learning and metabolomics to uncover new biomarkers for predicting pesticide exposure among patients with kidney function decline - Junne-Ming Sung; Yu-Chi Hung; Wan-Ru Wang; Chiau-Jun Chu; Yen-Ping Lin; Kuan-Hung Liu; Trias Mahmudiono; Hsiu-Ling Chen (Science of The Total Environment, 2025)

Integrating satellite information, land use regression, and machine learning to estimate the spatiotemporal variation of ionic composition in PM2.5 across Taiwan - Kang Lo; Tang-Huang Lin; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Chun-Sheng Huang; Ho-Tang Liao; Yee-Lin Wu; Chang-Fu Wu (Science of The Total Environment, 2025)

Mineralogical insights into the release behaviors of potentially toxic elements from the indigenous Zn smelting slags dumping sites - Ze-Lin Xu; Mei-Chun Zhou; Jin-Hui Miao; Wen-Chu Zhao; Rong-Bing Fu; Da-Mao Xu (Process Safety and Environmental Protection, 2025)

Augmented phototransformation of brominated disinfection by-products via surface water introduction during sunlit reclaimed water storage - De-Xiu Wu; Yuan-Chu Qin; Wen-Long Wang; Yan-Lin Chen; Qian-Yuan Wu (Journal of Hazardous Materials, 2025)

Characterization of IL-34 and CSF-1R in Sciaenops ocellatus: IL-34 participates in its anti-bacterial immune responses to Vibrio harveyi infection - Jiale Zhou; Jingyao Yu; Lin Zhang; Qing Chu (Fish & Shellfish Immunology, 2025)

Phosphorus flame retardant for enhancing spectral selectivity and fire safety of radiative cooling coatings - Jing Gao; Liangyuan Qi; Liang Chen; Wenyue Guo; Bicheng Lin; Zefan Feng; Suhong Li; Yuan Hu; Fukai Chu; Weiyi Xing (Chemical Engineering Journal, 2025)

Successional trajectories differ between soil microbial guilds after logging in mixed conifer-broadleaf forests - Qiuyan Tan; Xingwu Lin; Leho Tedersoo; Jiasui Li; Xiuhai Zhao; Jianguo Zhu; Haiyan Chu; Teng Yang (Plant and Soil, 2025)

Multiomics reveals the impact of microplastics and di-n-octyl phthalate on hormone biosynthesis in cucumber - Haoran Zhuang; Yiwen Chu; Menglin Wang; Bo Liu; Bihua Chen; Ziyu Lin; Zhenxia Li (Physiology and Molecular Biology of Plants, 2025)

Whether aristolochic acid directly drives hepatocarcinogenesis: comprehensive investigations from mutational signatures to animal models - Lu Yang; Wanjun Lin; Meina Shi; Zifeng Huang; Xuening Zhang; Yanchao Yang; Tong Chu; Dayuan Zheng; Dongfan Yang; Wenzhe Ma (Archives of Toxicology, 2025)

Whole-genome resequencing-based assessment of genomic diversity and selection signatures in Rhipicephalus microplus from Shaanxi, China - Yi-yao Mou; FU-wen Wang; YU-kun Kang; Ya-qing Li; YU-ying Yang; Tian-yuan Liu; Chu-zhao Lei; Qing Lin (Veterinary Parasitology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Harvesting vibration energy for efficiently piezocatalytic degradation of organic dyes by Bi11VO19 nanosheets - Yingjie Zhou; Yuxin Chu; Yao Lin; Chenyu Gong; Lingwei Xu; Kaiqi Wang; Yiming He; Ying Wu (Journal of Cleaner Production, 2025)

Effect of water vapor on the structure and performance of silver catalysts for ethylene oxidation - Yandong Chu; Hongmei Liang; Qiang Lin; Haoyang Huang; Ping Che; Yongsheng Han (Chemical Engineering Journal, 2025)

miR-200b Regulates Cellular Proliferation and Inflammatory Responses by Targeting Dual-Specificity Phosphatase 1 in Lower Vertebrates, Sciaenops ocellatus - Jingyao Yu; Qing Chu; Lin Zhang (Marine Biotechnology, 2025)

Enhanced Hair Growth Through Transdermal Delivery of Bacopa Monnieri Extract Using a Needle-Free Supersonic Atomizer - Yu-Chiuan Wu; Yi-Ping Lin; Ching-Yi Chang; Hsia-Ying Cheng; Tien-Huei Chu; Chien-Chih Chen; Shyh-Ming Kuo (Journal of Medical and Biological Engineering, 2025)

Lung microbiota metabolite L-malic acid attenuates the airway inflammation in asthma by inhibiting ferroptosis - Lishan Lin; Danhui Huang; Haohua Huang; Lingyan Xie; Yi Huang; Cuiping Ye; Lanhe Chu; Yujie Qiao; Xiaojing Meng; Shaoxi Cai; Hangming Dong (Toxicology and Applied Pharmacology, 2025)

Suppression of TaHDA8-mediated lysine deacetylation of TaAREB3 acts as a drought-adaptive mechanism in wheat root development - Zehui Liu; Qun Yang; Xingbei Liu; Jinpeng Li; Lei Zhang; Wei Chu; Jingchen Lin; Debiao Liu; Danyang Zhao; Xiao Peng; Chaowu Zeng; Mingming Xin; et al. (Molecular Plant, 2025)

Transfer patterns of human blood to follicular fluid of per- and polyfluoroalkyl substances with distinct molecular structures and physico-chemical properties - Yun-Ting Zhang; Michael S. Bloom; Yang Zhou; Saif Ur Rehman; Chu Chu; Kun Zhao; Biao Yin; Zhong Lin; Yuan-Yuan Fan; Li-Zi Lin; Ru-Qing Liu; Weihong Tan; et al. (Journal of Hazardous Materials, 2025)

Novel synthesis and application of biochar for controlling release and exposure of mercury in the farmland: From human health risk perspective - Nathan Thadeo Yoashi; Che-Jung Hsu; Ying-Lin Wang; Po-Hui Wu; Zheng-Yei Hseu; Ling-Chu Chien; Hsing-Cheng Hsi (Environmental Research, 2025)

The review of shark conservation legislation in China: deficiencies and potential avenues for improvement - Xiao-Lin Chu (Biodiversity and Conservation, 2025)

Whole-genome sequences revealed genomic diversity and selection signatures of Dermacentor silvarum in Shaanxi, China - Yi-yao Mou; Meng-ke Lin; Yu-ying Yang; Yu-kun Kang; Ya-qing Li; Tian-yuan Liu; Chu-zhao Lei; Qing Lin (Veterinary Parasitology, 2025)

In-situ geotechnical properties of abyssal sediments and implications for environmental impacts of polymetallic nodule mining - Zhenggang Li; Zhou Li; James R. Hein; Yangrui Cheng; Yuwei Liu; Shiquan Lin; Hao Wang; Xibin Han; Yanhui Dong; Fengyou Chu; Xiaohu Li (Marine Geology, 2025)

Formation of aroma characteristics driven by microorganisms during long-term storage of Liubao tea - Chang Xu; Jinming Zhang; Yani Pan; Xinyu Feng; Anran Yan; Xinxin Wang; Lin Xiang; Haowei Guo; Lixin He; Tianyuan Chen; Fangyuan Fan; Shuying Gong; et al. (Food Chemistry, 2025)

Corrigendum to ‘Biochar-amended constructed wetlands enhance sulfadiazine removal and reduce resistance genes accumulation in treatment of mariculture wastewater’ [Environ. Res., Volume 273 (2025) 121161] - Yuan-yuan Gao; Yu-xin Wu; Wang-chao Chu; Li Lai; Jia-hao Sun; Lin-lan Zhuang; Fei-fei Liu (Environmental Research, 2025)

Integrative analysis based on CRISPR screen identifies apilimod as a potential therapeutic agent for cisplatin-induced acute kidney injury treatment - Yunpeng Chu; Muyun Wei; Zhongyu Cao; Luan Chen; Jie Tan; Wei Bao; Fan Yang; Yingtian Zhang; Yunxiao Lin; Yutong Zhang; Shiyi Li; Cai Lv; et al. (Science China Life Sciences, 2025)

Indochina orogenic belt and related geodynamics - Wei Lin; Yin Wang; Fei Liu; Lingtong Meng; Qinying Wu; Zhao Guo; Wei Wei; Yang Chu; Jinyan Li; Qingchen Wang; Michel Faure; Vuong Van Nguyen (Science China Earth Sciences, 2025)

Mechanical performance and microstructure of HSLWC incorporating MWCNTs and shale-based aggregates - Qiansha Li; Jin Chai Lee; Xiaojiang Hong; Qian He; Jing Lin Ng; Wei Chek Moon; Ming Kun Yew; May Yen Chu; Bo Li (Innovative Infrastructure Solutions, 2025)

Microbiological Activity and Oxygen Availability Influence Arsenic Mobilization and Redox Transformation in an Arsenic-Rich Aquifer - Yu-Chen Su; Yu-Ju Chu; Chia-Cheng Wei; Chan-Wei Yu; Pei-Ling Yen; Yu-Hsuan Kuo; Ting-An Lin; Vivian Hsiu-Chuan Liao (Exposure and Health, 2025)

Experimental study on coupled effects of water and sub-zero temperatures on mechanical behavior and damage evolution of sandstone under uniaxial compression - Xin Cai; Chu Wang; Cuigang Chen; Zilong Zhou; Zhengtao Fang; Chunping Lin (Bulletin of Engineering Geology and the Environment, 2025)

Structural resilience analysis of rural networks based on complex network theory - Xiaofei Tang; Yifan Cao; Wenhui Lin; Jinlong Chu; Jiulin Li (Frontiers of Earth Science, 2025)

Luminescence dating of core DLC70-2 from the North Yellow Sea in China and its implication for late Quaternary transgressions - Nan Tang; Zhongbo Wang; Penghui Lin; Yuexin Liu; Zonghui Wu; Haozheng Tian; Xi Mei; Jun Sun; Jianghao Qi; Rihui Li; Shuyu Wu; Hongxian Chu; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Biochar-amended constructed wetlands enhance sulfadiazine removal and reduce resistance genes accumulation in treatment of mariculture wastewater - Yuan-yuan Gao; Yu-xin Wu; Wang-chao Chu; Li Lai; Jia-hao Sun; Lin-lan Zhuang; Fei-fei Liu (Environmental Research, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Estimating and characterizing spatiotemporal distributions of elemental PM2.5 using an ensemble machine learning approach in Taiwan - Chun-Sheng Huang; Kang Lo; Yee-Lin Wu; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Cheng-Pin Kuo; Ho-Tang Liao; Tang-Huang Lin; Chang-Fu Wu (Atmospheric Pollution Research, 2025)

Sternal glands in Strumigenys ants - Chu Wang; Fu-Ya Chung; Chung-Chi Lin; Johan Billen (Arthropod Structure & Development, 2025)

The association between anti-inflammatory therapies and renal outcomes in patients with established cardiovascular disease or high cardiovascular risks: a meta-analysis of randomised controlled trials - Wenfeng Yang; Zonglin Li; Chu Lin; Xiaoling Cai; Fang Lv; Wenjia Yang; Linong Ji (Inflammopharmacology, 2025)

Temporal Dynamics of Immune Response Signalling in Largemouth Bass ( Micropterus salmoides ) Infected With Largemouth Bass Virus - Xin Chu; Jing Chen; Lingyun Lin; Jiayun Yao; Lei Huang; Mingyue Gao; Jinyu Shen; Xiaoyi Pan (Journal of Fish Diseases, 2025)
The largemouth bass virus (LMBV) significantly impacts Chinese largemouth bass aquaculture. The molecular mechanisms regulating LMBV virulence and the gene responses stimulated in the host during infection remain unclear. This study investigates the transcriptional dynamics and signalling pathways activated during the immune response to LMBV by analysing the transcriptome of head kidney tissues at 1, 4, 7, and 28 days post‐infection (dpi) using RNA sequencing. Histopathological and viral load analyses indicated early tissue disruption, followed by extensive recovery by 28 dpi. Analysis of differentially expressed genes (DEGs) and weighted gene co‐expression network analysis (WGCNA), combined with Venn analysis of samples at 1, 4, and 7 dpi, identified significant and common genes. Early infection triggered robust innate immunity through activation of the RIG‐I like receptor and cGAS‐STING signalling pathways, which activated type I interferons (IFNs) and interferon‐stimulated genes (ISGs). Later stages indicated activation of adaptive immune responses. Validation of randomly selected genes via RT‐qPCR confirmed the RNA‐seq results, showing consistent expression patterns. This comprehensive study offers new insights into the sustained innate and adaptive immune responses to LMBV.

Nationwide suspect screening of new psychoactive substances (NPSs) and other controlled substances in Taiwan wastewater using liquid chromatography–High resolution mass spectrometry (LC-HRMS) - Yuan-Chih Chen; Jen-Yi Hsu; Yung-Chieh Lin; Chiau-Jun Chu; Yen-Ping Lin; Yun-Ju Tsai; Pao-Chi Liao (Chemosphere, 2025)

Knockout of dead end 1 by CRISPR/Cas9 leads to loss of germ cells and male-biased sex development in freshwater angelfish (Pterophyllum scalare) - Wai-Kwan Chu; Shih-Chin Huang; Ching-Fong Chang; Yu-Ho Lin; Jen-Leih Wu; Hong-Yi Gong (Aquaculture, 2025)

Origin and deposition of deepwater homogenites from a sedimentological perspective: Examples from offshore SW Taiwan - Radha Krishna Pillutla; Andrew Tien-Shun Lin; Jen-Chu Yeh; Gueorgui Ratzov; Nathalie Babonneau; Shu-Kun Hsu; Chih-Chieh Su; Serge Lallemand; Ludvig Löwemark (Sedimentary Geology, 2025)

Evidence for a command neuron controlling calling song in the cricket Gryllus assimilis - Chu-Cheng Lin; Berthold Hedwig (Journal of Insect Physiology, 2025)

Wide-area tip-like effect boosting electrocatalytic sulfion oxidation for energy-efficient hydrogen production in seawater electrolysis - Kecheng Tong; Wenhui Qiu; Shucong Zhang; Weiyue Zhao; Pingwei Wu; Fei Lin; Lei Chu; Huanlei Wang; Weiqian Tian; Minghua Huang (Chemical Engineering Journal, 2025)

Enhanced electrocatalytic conversion of CO2 to CO via a non-stoichiometric zinc-fluorine amorphous interface - Hsin-Chiao Wu; Chia-Chen Lin; Chu-Hsin Yang; Yu-Wei Huang; Chen-Hao Yeh; Yu-Jen Chou; Ta-Chung Liu (Chemical Engineering Journal, 2025)

Groundwater Level Prediction by Wavelet Deep Learning with Smart Pumping Data - Tsai-Ning Weng; Ray-Shyan Wu; Tzu-Han Weng; Yi-Ho Chen; Tsai-Chun Lai; Jui-Yun Hsieh; Chu-Chun Hsu; Yuan-Chien Lin (Water Resources Management, 2025)

Human Amniotic Epithelial Stem Cells Promote Functional Recovery After Spinal Cord Injury In Rats By Regulating The Polarization Of Macrophages - Hongyan Zhang; Jingjing Liu; Beike Chen; Xin Chen; Shijun Wei; Guanghui Zhang; Xiaomin Yan; Xingsen Xue; Guangjian He; Jiangkai Lin; Hua Feng; Weihua Chu (Molecular Neurobiology, 2025)

Discovery of novel benzbromarone derivatives via the closed metabolic site as potent human uric acid transporter 1 (URAT1) inhibitors - Wenfeng Ye; Mingchao He; Gaofeng Lin; Li Shao; Jiajia Mo; Yan Zhao; Xiaodong Ma; Qinlong Xu; Zhaoxing Chu (Medicinal Chemistry Research, 2025)

Displacement evolution of failure and non-failure sliding rock slopes - Hsien-Li Kuo; Guan-Wei Lin; Ting-Yu Lin; Che-Hsin Liu; Chung-Ray Chu; Chih-Hsin Chang; Ching-Weei Lin; Hongey Chen (Landslides, 2025)

Isogarcinol Reduces MARS Levels and Deactivates the PI3K/AKT Pathway to Suppress the Malignant Properties of Breast Cancer Cells - Dechao Zhang; Yunhai Chu; Meng Li; Lin Du (Cell Biochemistry and Biophysics, 2025)

MiR-218 Exhibits Anti-Leukemia Effects by Targeting CTNND2 in Primary Acute Erythroid Leukemia HEL Cells - Ming-qiang Chu; Ting-juan Zhang; Zi-qi Liu; Qian Yang; Ting-ting Du; Min-jie Zhang; Ye Jin; Yong-jie Cao; Xiang-mei Wen; Zi-jun Xu; Yang-jing Zhao; Jiang Lin; et al. (Cell Biochemistry and Biophysics, 2025)

Time-series InSAR reveals new insights into land subsidence in the Yellow River Delta, China - Yi Zhang; Ziliang Si; Xu Lin; Zehua Zhang; Hongxian Chu; Chang Cao; Yanxia Liu; Haijun Huang; Bingqi Huang; Zechao Bai; Kuifeng Wang; Xinghua Zhou; et al. (Marine Georesources & Geotechnology, 2025)

Determination of pullout capacity for an inclined single-plate helical pile under combined loading in clay - Fei Liu; Po Cheng; Hongnan Lin; Jiangtao Yi; Yu Peng; Jun Hu; Ya-pei Chu (Marine Georesources & Geotechnology, 2025)

How does globally accumulated tropical cyclone energy vary in response to a changing climate? - Kaiyue Shan; Fengfei Song; Yanluan Lin; Wenchao Chu; Chengfei He; Pao-Shin Chu; Lixin Wu; Xiping Yu (Science Bulletin, 2025)

Another inner truth of shaking: Water migration and transformation-advanced physicochemical alterations in tea leaves - Zhilong Hao; Jinyuan Wang; Jiayun Zhuang; Xinyu Feng; Helin Lv; Jiao Feng; Shuping Ye; Weisu Tian; Guanjun Pan; Ping Chen; Hongzheng Lin; Qiang Chu (Food Chemistry, 2025)

Mitochondrial alterations and signatures in hepatocellular carcinoma - Tsung-Hsien Chen; Shu-Hsien Lin; Ming-Yang Lee; Hsiang-Chen Wang; Kun-Feng Tsai; Chu-Kuang Chou (Cancer and Metastasis Reviews, 2025)

Removal of single and multi-heavy metals from piggery digestate by the electric field-microalgae system: Influences, kinetics and mechanisms - Xiaosong Tian; Min Wang; Xing Liao; Shiyu Chu; Haixiang Cheng; Xiaoai Lin; Longzao Luo (Algal Research, 2025)

Toll-like receptors landscape in Takifugu fasciatus: Dynamic responses to Aeromonas hydrophila, poly I:C, and Ichthyophthirius multifiliis challenge - Ge Lin; Peng Chu; Xiang Gong; Yuxi Liu; Kai Zhang; Xianhui Ning; Tao Wang; Shaowu Yin; Jie Ji (Aquaculture, 2025)

Network analysis was effective in establishing the soil quality index and differentiated among changes in land-use type - Ming Gao; Wei Hu; Meng Li; Shuli Wang; Lin Chu (Soil and Tillage Research, 2025)

Adaptive reward shaping based reinforcement learning for docking control of autonomous underwater vehicles - Shuguang Chu; Mingwei Lin; Dejun Li; Ri Lin; Sa Xiao (Ocean Engineering, 2025)

Enrichment of methanotrophic consortium and its aerobic cometabolism of mixed vinyl chloride pollutants using methane gas and micro- and nano-bubbles - Chun-Chin Wang; Chih-Ming Liang; Ting-I Lin; Chu-Fang Yang (International Biodeterioration & Biodegradation, 2025)

Effects of dietary fiber on the quality of fried oysters and oil Permeation mechanism - Junbo Chu; Songyi Lin; Yuxin Xie; Lin Ma; Simin Zhang (Food Research International, 2025)

Flowering in aged white tea: Recovering umami taste and amplifying of stale aroma - Wan Zhu; Xinyu Feng; Yani Pan; Haowei Guo; Yunqing Liu; Xingchen Lin; Fangyuan Fan; Shuying Gong; Ping Chen; Qiang Chu (Food Chemistry, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

A sensitive post-column derivatization approach for enhancing hydroxyl metabolites detection - Yen-Chu Lin; Shiu-Wen Huang; San-Yuan Wang; Jing-Rong Su; Jimmy Junxiang Wang; Ming-Jen Hsu; Hsiao-Wei Liao (Analytica Chimica Acta, 2025)

Year-round natural spawning, early ontogeny, and larval rearing of the painted sweetlips, Diagramma pictum (Thunberg, 1792) in a hatchery: Potential as a new species for mariculture - Pei-Sheng Chiu; Bo-Hong Yu; Yu-Hsin Tu; Yeong-Torng Chu; Cheng-Hsuan Huang; Shine-Wei Ho; Sun-Hon Lin; Shinn-Lih Yeh; Ming-Yih Leu (Aquaculture, 2025)

Removal of heavy metals from single- and multi-metal solution by magnetic microalgae-derived biochar - Xiaosong Tian; Shiyu Chu; Yujie Hu; Longzao Luo; Xiaoai Lin; Hui Wang (Journal of Water Process Engineering, 2025)

Molecular characterization of extended-spectrum β-lactamases from the Akkermansia genus - Jiafu Lin; Tiantian Wang; Yaliang Zhou; Jingzhou Sha; Xueke Chen; Wenjie Wang; Chuan Zhang; Feng Xie; Yiwen Chu; Xinrong Wang; Dan Luo; Tao Song (International Journal of Food Microbiology, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

Dual functionality of carbazole-based phosphonic acid molecular additives realizes efficient hole transport layer-free perovskite light-emitting diodes - Yin-Ti Lai; Chiung-Han Chen; Ming-Hsuan Yu; Hsing-Yu Kuo; I-Chih Ni; Bi-Hsuan Lin; Hobeom Kim; Chi-Ching Kuo; Yu-Jung Lu; Chu-Chen Chueh (Chemical Engineering Journal, 2025)

Visible light-powered photodynamic antibacterial chlorophyllin-derived metallochlorins - Yuling Xue; Kuoran Xing; Max Jing Rui Tham; Bang Lin Li; Narattam Sikdar; Lai Peng Leong; Ching Hua Lee; Justin Jang Hann Chu; Wee Han Ang; David Tai Leong (Chemical Engineering Journal, 2025)

Ion mitigation and strain regulation with 2D Semi-Metals for MA-Based perovskite materials in highly efficient solar cells - Chintam Hanmandlu; Soumallya Banerjee; Abhishek Kumar; Zeeshan Alam Ansari; Ramesh Kumar; Yen-Yu Wang; Lin- Chyn Yuan; Shenghan Li; Raman Sanker; Chandra Shekar Gantepogu; You-Yun Wen; Shyam Narayan Singh Yadav; et al. (Chemical Engineering Journal, 2025)

Deep learning in the advanced core sample porosity determination with XCT image - Hung-Yu Wu; Ching-Li Kuo; Chen-Yi Lin; Wei-Ta Chu (Earth Science Informatics, 2025)

Application of seismically derived tilt signals to characterize groundwater flow regimes: An example from a constant-rate pumping test in Taiwan - Chu-Fang Yang; Wu-Cheng Chi; Chien-Chung Ke; Chin-Jen Lin (Journal of Hydrology, 2024)

Estimating monthly NO2, O3, and SO2 concentrations via an ensemble three-stage procedure with downscaled satellite remote sensing data and ground measurements - Chu-Chih Chen; Yin-Ru Wang; Fu-Cheng Wang; Yi-Shiang Shiu; Chang-Fu Wu; Tang-Huang Lin (Journal of Hazardous Materials, 2024)

Combining fermentation broth with spent water recycling for microalgae cultivation: Nutrient reutilization, biodiesel production and techno-economic simulation - Ruoyu Chu; Haolun An; Lefei Cai; Yu Chen; Guangming Zeng; Jie Yuan; Lin Tang (Journal of Cleaner Production, 2024)

Effects of deep, air and vacuum frying on oyster quality and protein-mediated mechanism analysis via TMT quantitative proteomics - Junbo Chu; Songyi Lin; Baoshang Fu; Xiangning Meng; Jiaxin Qiang; Simin Zhang (Food Chemistry, 2024)

Role of pyrochar amendment toward carbon neutrality of rice paddy field by mitigating methane emission: A global evaluation by meta-analysis - Xinran Liu; Shuai Yin; Shuhan Xu; Jian Lin; Chengming Zhang; Linkui Cao; Qingnan Chu; Zhimin Sha (Field Crops Research, 2024)

Effects of salinity and temperature on the icing of sessile saltwater droplets on solid surfaces - Canjun Zhao; Zhifeng Hu; Yukai Lin; Xiaomin Wu; Xuan Zhang; Fuqiang Chu (Desalination, 2024)

Bioinspired fibrous scaffolds with hierarchical orientations for enhanced spinal cord injury repair - Yun Chu; Keni Yang; Lei Huang; Wangping Hao; Haitao Zhao; Tiandi Xiong; Wen Yang; Baohui Zhang; Kexin Zheng; Tongtong Zhao; Lin Qian; Xu Gao; et al. (Chemical Engineering Journal, 2024)

Injectable responsive chemodynamic hydrogel for the sustained and localized delivery of a ferroptosis inducer to improve anticancer therapy - Chu-Hung Chung; Tzu-Wei Lu; Chi Lin; Cheng-Wei Lin; Fwu-Long Mi (Chemical Engineering Journal, 2024)

In enzymatic reactions, the reverse reaction reduces product noise - Ching-Chu Hsieh; Yung-Chun Lin; Wei-Bo Lin; Che-Chi Shu (BioSystems, 2024)

A Deniable Encryption Method for Modulation-Based DNA Storage - Ling Chu; Yanqing Su; Xiangzhen Zan; Wanmin Lin; Xiangyu Yao; Peng Xu; Wenbin Liu (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Virtual Reality Fusion Testing-Based Autonomous Collision Avoidance of Ships in Open Water: Methods and Practices - Haiming Zhou; Mao Zheng; Xiumin Chu; Chengqiang Yu; Jinyu Lei; Bowen Lin; Kehao Zhang; Wubin Hua (Journal of Marine Science and Engineering, 2024)
With the rapid development of autonomous collision avoidance algorithms on ships, the technical demand for the testing and verification of autonomous collision avoidance algorithms is increasing; however, the current testing of autonomous collision avoidance algorithms is mainly based on the virtual simulation of the computer. To realize the testing and verification of the autonomous collision avoidance algorithm in the real ship scene, a method of virtual reality fusion testing in open water is proposed and real ship testing is carried out. Firstly, an autonomous ship collision avoidance test and evaluation system is established to research the test method of ship encounters in open water. Starting from the convention on the international regulations for preventing collisions at sea (COLREG), the main scenario elements of ship collision avoidance are analyzed. Based on the parametric modeling method of ship collision avoidance scenarios, a standard test scenario library for ship collision avoidance in open waters is established. Then, based on the demand for a ship collision avoidance function test, the evaluation index system of ship collision avoidance is constructed. Subsequently, for the uncertainty of the initial state of the real ship test at sea, the virtual–real space mapping method to realize the correspondence of the standard scenario in the real world is proposed. A standardized testing process to improve testing efficiency is established. Finally, the method of conducting virtual simulation and virtual reality fusion tests for various scenarios are verified, respectively. The test results show that the test method can effectively support the testing of autonomous collision avoidance algorithms for ships in open waters and provide a practical basis for improving the pertinence and practicability of ship collision avoidance testing.

Coral mariculture using abandoned abalone farming ponds in northeastern Taiwan - Shinya Shikina; Yin-Chu Cheng; Tzu-Chieh Lin; Yu-En Chang; Pin-Hsuan Tsai; Emma Chen; Yu-Chuan Chang; Yuen-Yi Leung; Yi-Chun Yu; Yi-Ling Chiu (Aquaculture, 2024)

Impact of photoaging on the chemical and cytotoxic properties of nanoscale zeolitic imidazolate framework-8 - Yi-Chun Chen; Kun-Yi Andrew Lin; Ying-Chu Chen; Yan-Yu Hong; Yu-Fang Hsu; Chia-Hua Lin (Journal of Hazardous Materials, 2024)

Uncovering the Shuixian tea grades hierarchy in Chinese national standard: From sensory evaluation to microstructure and volatile compounds analysis - Yanping Lin; Yibiao Huang; Xia Liu; Yani Pan; Xinyu Feng; Haowei Guo; Xiaolan Li; Yike Tao; Ping Chen; Qiang Chu (Food Chemistry, 2024)

Intrauterine exposure to long-chain perfluorocarboxylic acids (PFCAs) were associated with reduced primary bile acids in three-year-old children: Findings from a prospective birth cohort study - Yu-Ting Guo; Jin-bo Huang; Jing-chuan Xue; Shuang-Jian Qin; Dan Cai; Qi-Zhen Wu; Chu Chu; Cui-lan Tang; Yan-qi Xie; Li-Zi Lin; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2024)

Solvation structure manipulation of ester-based electrolyte by acetonitrile additive enables high-capacity and stable K-storage for phenazine-based anode - Xiaokang Chu; Ran Chen; Hang Chen; Hao Wang; Luanjie Nie; Haobo Xia; Qingxue Lai; Zixia Lin; Mengtao Ma; Hao Gong; Jing Zheng (Chemical Engineering Journal, 2024)

Dissecting the temporal genetic networks programming soybean embryo development from embryonic morphogenesis to post-germination - Yen-Ching Wang; Wei-Hsun Hsieh; Liang-Peng Lin; Meng-Hsun He; Ya-Ting Jhan; Chu-Jun Huang; Junpeng Zhan; Ching-Chun Chang; Tzung-Fu Hsieh; Jer-Young Lin (Plant Cell Reports, 2024)

Safety analysis code development and validation for lead-cooled fast reactor with helical coiled once-through steam generator - Jiaxin Zhang; Chenglong Wang; Wenxi Tian; G.H Su; Suizheng Qiu; Lin Xian; Kun Cheng; Xiao Chu; Shiying Wei; Guo Chen (Annals of Nuclear Energy, 2024)

Hepatic and metabolic outcomes induced by sub-chronic exposure to polystyrene microplastics in mice - Sheng-Han Lee; Ting-An Lin; Yuan-Horng Yan; Chu-Chun Chien; Tsun-Jen Cheng (Archives of Toxicology, 2024)

Soil microbial influences over coexistence potential in multispecies plant communities in a subtropical forest - Weitao Wang; Hangyu Wu; Tingting Wu; Zijing Luo; Wei Lin; Hanlun Liu; Junli Xiao; Wenqi Luo; Yuanzhi Li; Youshi Wang; Chuliang Song; Gaurav Kandlikar; et al. (Ecology, 2024)
Soil microbes have long been recognized to substantially affect the coexistence of pairwise plant species across terrestrial ecosystems. However, projecting their impacts on the coexistence of multispecies plant systems remains a pressing challenge. To address this challenge, we conducted a greenhouse experiment with 540 seedlings of five tree species in a subtropical forest in China and evaluated microbial effects on multispecies coexistence using the structural method, which quantifies how the structure of species interactions influences the likelihood for multiple species to persist. Specifically, we grew seedlings alone or with competitors in different microbial contexts and fitted individual biomass to a population dynamic model to calculate intra‐ and interspecific interaction strength with and without soil microbes. We then used these interaction structures to calculate two metrics of multispecies coexistence, structural niche differences (which promote coexistence) and structural fitness differences (which drive exclusion), for all possible communities comprising two to five plant species. We found that soil microbes generally increased both the structural niche and fitness differences across all communities, with a much stronger effect on structural fitness differences. A further examination of functional traits between plant species pairs found that trait differences are stronger predictors of structural niche differences than of structural fitness differences, and that soil microbes have the potential to change trait‐mediated plant interactions. Our findings underscore that soil microbes strongly influence the coexistence of multispecies plant systems, and also add to the experimental evidence that the influence is more on fitness differences rather than on niche differences.

Visible-light-prompted photoelectrochemical sensors fabricated using Er3NbO7/P@g-C3N4/SnS2 nanocomposite for detecting mercury ion in environmental water samples - Abishek Jayapaul; Yu-Chien Lin; Ying-Chu Chen; Ting-Yu Liu; Ren-Jei Chung (Chemosphere, 2024)

Effects of microplastics and combined pollution of polystyrene and di-n-octyl phthalate on photosynthesis of cucumber (Cucumis sativus L.) - Haoran Zhuang; Zhenxia Li; Menglin Wang; Bo Liu; Yiwen Chu; Ziyu Lin (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

OSL and radiocarbon dating of core TBF-1 on the outer shelf of the East China Sea and implications for late Quaternary stratigraphic correlation - Zhongbo Wang; Nan Tang; Penghui Lin; Pengyu Qiao; Kai Lu; Xi Mei; Jun Sun; Jianghao Qi; Yang Wang; Hongxian Chu; Zhongping Lai (Quaternary Geochronology, 2024)

Catalytic fixation of hydrogen sulfide over CuO-CaCO3 co-impregnated tea stalk-derived biochar - Fangcong Lin; Leiping Wang; Xiaorong Dai; Zun Man; Yang Meng; Dongtao Chu; Yuting Yang; Wei Wang; Hang Xiao; Kaiying Wang (Journal of Environmental Chemical Engineering, 2024)

High-throughput generation of monodisperse double emulsions via controllable symmetric splitting in Y-shaped microchannels - Lin-Ling Fan; Wei Wang; Xiao-Jie Ju; Zhuang Liu; Rui Xie; Jianhong Xu; Guangsheng Luo; Da-Wei Pan; Liang-Yin Chu (Chemical Engineering Journal, 2024)

Uncovering and preventing polytellurides dissolution enables stable sodium-ion storage: A case study of SnTe - Zhixin Liang; Jianlian Huang; Wei Zhang; Heying Chu; Qinghua Li; Haibin Lu; Zeyu Lin; Junling Wang; Haiping Lin; Yuyang Chen; Shiyun Xiong; Shaoming Huang (Chemical Engineering Journal, 2024)

Development and validation of sloped ground pressure prediction model for a tracked tractor in hilly and mountainous environments - Fuzeng Yang; Qi Liu; Yuxuan JI; Hongli Chu; Luojia Duan; Zhong Lin; Yuanfeng Shou; Zhijie Liu (Soil and Tillage Research, 2024)

Refining metallic nano-copper by electron-rich black carbon for superior Fenton-like catalysis in water purification: The capacitive regulation of corrosive electron transfer - Lu Zhao; Xing-Bo Chen; Xin-Ru Hu; Lei Chen; Shun Feng; Ai-Yong Zhang; Shu-Chuan Peng; Zhi-Xian Lin; Chu Jiang; Wei Da; Qi-Xin Wei (Journal of Hazardous Materials, 2024)

Soil application of graphitic carbon nitride nanosheets alleviate cadmium toxicity by altering subcellular distribution, chemical forms of cadmium and improving nitrogen availability in soybean (Glycine max L.) - Kai Xu; Lifan Zheng; Kaifei Chu; Chenghua Xing; Jiajing Shu; Keming Fang; Shuting Ma; Yong Fang; Jianfang Yan; Miaozhen Cai; Xi-Lin Wu (Journal of Environmental Management, 2024)

Golden-flower fungus (Eurotiwm Cristatum) presents fungal flower aroma as well as accelerates the aging of white tea (Shoumei) - Wan Zhu; Su Zhou; Haowei Guo; Jiali Hu; Yanyan Cao; Yingxin Xu; Xingchen Lin; Baoming Tian; Fangyuan Fan; Shuying Gong; Ping Chen; Qiang Chu (Food Chemistry, 2024)

A systematic investigation of PVDF-HFP in perovskite solar cells for improved space mission reliability - Seoungjun Ahn; Wei-Hao Chiu; Wei-Chen Chu; Pei-Yu Chen; Ting-Han Lin; Kun-Mu Lee (Chemical Engineering Journal, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

Electrolyte matching design for carboxylic acid-based organic K-storage anode - Jing Zheng; Hao Wang; Chi Hu; Hang Chen; Wanying Zhang; Xiaokang Chu; Luanjie Nie; Ran Chen; Jianying Long; Meng Lei; Jijian Xu; Zixia Lin; et al. (Chemical Engineering Journal, 2024)

A distinct manganese deposit on a Middle Permian carbonate platform in South China - Wenchao Yu; Zhichen Liu; Bolin Zhang; Daoliang Chu; Wei Wei; Lin Xiao; Deng Chen; Yuansheng Du; Leslie J. Robbins; Kurt Konhauser (Chemical Geology, 2024)

The Predictability Limit of Oceanic Mesoscale Eddy Tracks in the South China Sea - Hailong Liu; Pingxiang Chu; Yao Meng; Mengrong Ding; Pengfei Lin; Ruiqiang Ding; Pengfei Wang; Weipeng Zheng (Advances in Atmospheric Sciences, 2024)

One-pot synthesis of high performance CQDs/TiO2 nanocomposites without carbon source addition - Ning Wang; Jiayi Lin; Yang Li; Tao Li; Youmei Chen; Jing Li; Shuyi Shuai; Lu Chen; Zhiyao Chu (Journal of Water Process Engineering, 2024)

Converting kitchen waste into value-added fertilizer using thermophilic semi-continuous composting-biofiltration two-stage process with minimized NH3 emission - Xiu-Lin Chu; Xiang-Yu Peng; Zhao-Yong Sun; Cai-Yun Xie; Yue-Qin Tang (Bioresource Technology, 2024)

Investigation into the effects of background particles on Serratia marcescens bioaerosol - Zhijian Liu; Haochuan Li; Jiaqi Chu; Zhenzhe Huang; Xia Xiao; Chaofan Lin; Jie Shi; Junzhou He (Building and Environment, 2024)

The toxicity of chlorine dioxide to clownfish and its bactericidal capability to pathogenic strains of vibrio spp. - Chia‐Te Lin; Juan‐Ting Liu; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2024)
Global ornamental fish transportation ranging from hours to days can produce multiple stress factors impact fish health and cause mortality. Clownfish, particularly Amphiprion ocellaris , are among the most traded saltwater ornamental fish. Vibrio includes several pathogenic strains that affect aquatic animals. Consequently, prophylactic treatment of the water or fish is recommended. In this study, six Vibrio strains including V. alginolyticus , V. parahaemolyticus and V. harveyi isolated from sick A. ocellaris and one V. harveyi strain from a sick East Asian fourfinger threadfin ( Eleutheronema rhadinum ) were tested for their sensitivity to a popular disinfectant, chlorine dioxide (ClO 2 ). The results showed that 0.25 ppm ClO 2 effectively suppressed five of the seven tested Vibrio strains for 24 h; however, 0.1 ppm ClO 2 is safer for A. ocellaris . Meanwhile, ClO 2 2.5 ppm reduced the bacterial counts to below 3.3 × 10 5 CFU/mL for 24 hours. The LC 50 of ClO 2 for A. ocellaris was 0.87 ppm at 10 min and 0.72 ppm at 24 h post treatment. Mild changes in water quality, including dissolved oxygen (DO), temperature and pH, were recorded during the trial. More research is necessary to understand the sensitivity of various aquatic animal pathogens to ClO 2 and its toxicity to different aquatic animals.

Prediction of Pier Scour Depth under Extreme Typhoon Storm Tide - Zongyu Li; Weiwei Lin; Dongdong Chu; Feng Liu; Zhilin Sun; Wankang Yang; Hanming Huang; Dan Xu (Journal of Marine Science and Engineering, 2024)
The Western Pacific region is highly vulnerable to typhoon storm surge disasters, with localized erosion posing a particularly prominent issue for coastal marine structures. The prevalence of extreme typhoon storm surges poses a significant threat to the safety of engineering projects in these areas. In this study, a parameterized wind field model with precise calculation of wind speed was employed to establish a numerical model for typhoon storm tides. Based on the Western Pacific typhoon data from 1949 to 2023, hydraulic simulations were conducted for Hangzhou Bay, Xiangshan Port, and Yueqing Bay, revealing maximum flow velocities of 4.5 m/s, 1.95 m/s, and 2.09 m/s, respectively. These velocities exceeded the maximum possible tidal flow by 0.47–1.17 m/s. Additionally, using Sun’s velocity formula, the initiation flow velocities were calculated to be 1.85 m/s, 1.81 m/s, and 2.06 m/s for the aforementioned locations. Through localized erosion tests conducted around typical bridge piers and the subsequent application of similarity criteria, the maximum depth of localized erosion in the study area was determined to range from 2.16 m to 16.1 m, which corresponds to 1.1–2.3 times the scour caused by the maximum tidal flow scenario. A comparison of the erosion test results with calculations based on several formulas demonstrated that the scour prediction formula proposed by Sun exhibited the highest accuracy. This study supplements the understanding of the impact of typhoon storm surges on bridge pier erosion and provides a scientific basis for the design of bridge foundations.

Functional identification of specialized diterpene synthases from Chamaecyparis obtusa and C. obtusa var. formosana to illustrate the putative evolution of diterpene synthases in Cupressaceae - Tsai-Jung Wu; Chi-Chun Lin; Li-Ting Ma; Chih-Kai Yang; Chen-Lung Ho; Sheng-Yang Wang; Fang-Hua Chu (Plant Science, 2024)

The effect of maturity of tea leaves and processing methods on the formation of milky flavor in white tea - A metabolomic study - Jiao Feng; Jiayun Zhuang; Qianlian Chen; Hongzheng Lin; Qiang Chu; Ping Chen; Fang Wang; Bugui Yu; Zhilong Hao (Food Chemistry, 2024)

A newly-discovered tea population variety processed Bai Mu Dan white tea: Flavor characteristics and chemical basis - Yanping Lin; Yibiao Huang; Su Zhou; Xiaolan Li; Yike Tao; Yani Pan; Xinyu Feng; Haowei Guo; Ping Chen; Qiang Chu (Food Chemistry, 2024)

AKR1C2 genetic variants mediate tobacco carcinogens metabolism involving bladder cancer susceptibility - Yanping Xiao; Yang Shen; Hui Song; Fang Gao; Zhenguang Mao; Qiang Lv; Chao Qin; Lin Yuan; Dongmei Wu; Haiyan Chu; Meilin Wang; Mulong Du; et al. (Archives of Toxicology, 2024)

Sunlight enhanced the formation of tribromomethane from benzotriazole degradation during the sunlight/free chlorine treatment in the presence of bromide - Ming-Chi Hsieh; Wan-Ning Lee; Yi-Hsuan Chu; Hank Hui-Hsiang Lin; Angela Yu-Chen Lin (Chemosphere, 2024)

In vivo study on osteogenic efficiency of nHA/ gel porous scaffold with nacre water-soluble matrix - SiRi-GuLeng Li; Zhu-Ling Guo; Si-Yu Tao; Tao Han; Jie Zhou; Wan-Yun Lin; Xiang Guo; Chu-Xing Li; Sunchuri Diwas; Xiao-Wen Hu (Tissue and Cell, 2024)

Effect of tea extracts on heterocyclic aromatic amines and advanced glycation end products in roasting Eleutheronema Tetradactylum and lipid-mediated inhibition mechanism analysis - Ruichun Wang; Songyi Lin; Junbo Chu; Yi Yuan; Simin Zhang (Food Bioscience, 2024)

Advancing Li3VO4 as a high-performance anode material for use in lithium-ion batteries and lithium-ion capacitors - Yu-Sheng Hsiao; Jen-Hsien Huang; Lin-Yang Weng; Ta-Hung Cheng; Han-Hsin Chiang; Cheng-Zhang Lu; Huei-Chu Weng; Lars Thomsen; Bruce Cowie; Wei Kong Pang; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Novel chitosan-modified biochar prepared from a Chinese herb residue for multiple heavy metals removal: Characterization, performance and mechanism - Chengjiu Wang; Jixu Qiao; Jiandan Yuan; Zhentao Tang; Tianzhe Chu; Ruifeng Lin; Hongting Wen; Chuan Zheng; Hulan Chen; Haijiao Xie; Cheng Peng; Yuzhu Tan (Bioresource Technology, 2024)

Examining arterial pulsation to identify and risk-stratify heart failure subjects with deep neural network - Chieh-Chun Huang; Shih-Hsien Sung; Wei-Ting Wang; Yin-Yuan Su; Chi-Jung Huang; Tzu-Yu Chu; Shao-Yuan Chuang; Chern-En Chiang; Chen-Huan Chen; Chen-Ching Lin; Hao-Min Cheng (Physical and Engineering Sciences in Medicine, 2024)
Hemodynamic parameters derived from pulse wave analysis have been shown to predict long-term outcomes in patients with heart failure (HF). Here we aimed to develop a deep-learning based algorithm that incorporates pressure waveforms for the identification and risk stratification of patients with HF. The first study, with a case–control study design to address data imbalance issue, included 431 subjects with HF exhibiting typical symptoms and 1545 control participants with no history of HF (non-HF). Carotid pressure waveforms were obtained from all the participants using applanation tonometry. The HF score, representing the probability of HF, was derived from a one-dimensional deep neural network (DNN) model trained with characteristics of the normalized carotid pressure waveform. In the second study of HF patients, we constructed a Cox regression model with 83 candidate clinical variables along with the HF score to predict the risk of all-cause mortality along with rehospitalization. To identify subjects using the HF score, the sensitivity, specificity, accuracy, F1 score, and area under receiver operating characteristic curve were 0.867, 0.851, 0.874, 0.878, and 0.93, respectively, from the hold-out cross-validation of the DNN, which was better than other machine learning models, including logistic regression, support vector machine, and random forest. With a median follow-up of 5.8 years, the multivariable Cox model using the HF score and other clinical variables outperformed the other HF risk prediction models with concordance index of 0.71, in which only the HF score and five clinical variables were independent significant predictors (p < 0.05), including age, history of percutaneous coronary intervention, concentration of sodium in the emergency room, N -terminal pro-brain natriuretic peptide, and hemoglobin. Our study demonstrated the diagnostic and prognostic utility of arterial waveforms in subjects with HF using a DNN model. Pulse wave contains valuable information that can benefit the clinical care of patients with HF.

Functional characterization of terpene synthases SmTPS1 involved in floral scent formation in Salvia miltiorrhiza - Xiaohong Li; Lin Liu; Jin Chu; Guo Wei; Jiaxue Li; Xu Sun; Honghong Fan (Phytochemistry, 2024)

Effects of quercetin and l-ascorbic acid on heterocyclic amines and advanced glycation end products production in roasted eel and lipid-mediated inhibition mechanism analysis - Junbo Chu; Songyi Lin; Yi Yuan; Siqi Zhang; Simin Zhang (Food Chemistry, 2024)

Geochemical indications of hydrothermal fluid through sediments within the Geolin Mounds and Mienhua Volcano hydrothermal fields, southernmost Okinawa Trough - Feng-Hsin Hsu; Chih-Chieh Su; Yu-Shih Lin; Hsiao-Fen Lee; Mei-Fei Chu; Tefang Lan; Shein-Fu Wu; Song-Chuen Chen (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Unravelling solvation structure and interfacial mechanism of pyrrolidinium-based ionic liquid electrolytes in potassium-ion batteries - Xiaokang Chu; Hao Wang; Chi Hu; Qingxue Lai; Luanjie Nie; Hang Chen; Ran Chen; Zixia Lin; Mengtao Ma; Jing Zheng (Chemical Engineering Journal, 2024)

Efficient EVs separation and detection by an alumina-nanochannel-array-membrane integrated microfluidic chip and an antibody barcode biochip - Jiaoyan Qiu; Qindong Guo; Yujin Chu; Chunhua Wang; Hao Xue; Yu Zhang; Hong Liu; Gang Li; Lin Han (Analytica Chimica Acta, 2024)

Experimental optimization and mechanism analysis of extracting flavonoids with the supramolecular solvents-based methods - Zhi-lu Yu; Shi-yi Hou; Li-mei Lin; Yu-ran Chu; Ya-mei Li; Zhi-min Zhang; Jing Yan; Bo-hou Xia (Sustainable Chemistry and Pharmacy, 2024)

Humic substances mediated superior photochemical pollutant conversion on defective TiO2 in environmentally relevant matrices: The key roles of oxygen vacancy in surface interactions, oxidant activation and radical generation - Song Hu; Lyumeng Ye; Bing-Jie Tian; Jia-Ying Li; Ai-Yong Zhang; Lu Zhao; Chi Zhang; Chu Jiang; Zhi-Xian Lin; Wei Da; Qi-Xin Wei (Science of The Total Environment, 2024)

Di-n-butyl phthalate promotes the neural differentiation of mouse embryonic stem cells through neurogenic differentiation 1 - Ying-Chu Lin; Kenly Wuputra; Kohsuke Kato; Chia-Chen Ku; Shigeo Saito; Michiya Noguchi; Yukio Nakamura; Michael Hsiao; Chang-Shen Lin; Deng-Chyang Wu; Atsushi Kawaguchi; Hsin-Su Yu; et al. (Environmental Pollution, 2024)

Oxidative stress and potential effects of metal nanoparticles: A review of biocompatibility and toxicity concerns - Yung-Li Wang; Yu-Hsuan Lee; Chu-Lin Chou; Yu-Sheng Chang; Wen-Chih Liu; Hui-Wen Chiu (Environmental Pollution, 2024)

Community Structure and Water Quality Assessment of Benthic Macroinvertebrates in Hongze Lake - Lixiao Ni; Lin Zhou; Amar Ali Adam Hamad; Chu Xu; Wenlu Sang; Cunhao Du; Yun Nie; Haoyue Li; Jiahui Shi; Shiyin Li (Bulletin of Environmental Contamination and Toxicology, 2024)

Identification, Characterization, and Probiotic Potentials of Lactobacillus pentosus SF-1 - Lin Jiao; Shufei Liang; Ruixia Chu; Wentao Wang; Kangsen Mai; Ming Liu; Min Wan (Journal of Ocean University of China, 2024)

Extraction-free, immuno-RPA-CRISPR/Cas13a-based one-pot detection of glypican-3 directly from extracellular vesicles - Xiangyan Xiao; Xiaocong Lin; Chu Lok Ting; Xueran Huang; Biyun Zeng; Tiancai Liu; Tao Zeng (Analytica Chimica Acta, 2024)

Carbon fluxes of China's coastal wetlands and impacts of reclamation and restoration - Weizhi Lu; Jingfeng Xiao; Haiqiang Gao; Qingyu Jia; Zhengjie Li; Jie Liang; Qinghui Xing; Dehua Mao; Hong Li; Xiaojing Chu; Hui Chen; Haiqiang Guo; et al. (Global Change Biology, 2024)
Coastal wetlands play an important role in regulating atmospheric carbon dioxide (CO 2 ) concentrations and contribute significantly to climate change mitigation. However, climate change, reclamation, and restoration have been causing substantial changes in coastal wetland areas and carbon exchange in China during recent decades. Here we compiled a carbon flux database consisting of 15 coastal wetland sites to assess the magnitude, patterns, and drivers of carbon fluxes and to compare fluxes among contrasting natural, disturbed, and restored wetlands. The natural coastal wetlands have the average net ecosystem exchange of CO 2 (NEE) of −577 g C m −2 year −1 , with −821 g C m −2 year −1 for mangrove forests and −430 g C m −2 year −1 for salt marshes. There are pronounced latitudinal patterns for carbon dioxide exchange of natural coastal wetlands: NEE increased whereas gross primary production (GPP) and respiration of ecosystem decreased with increasing latitude. Distinct environmental factors drive annual variations of GPP between mangroves and salt marshes; temperature was the dominant controlling factor in salt marshes, while temperature, precipitation, and solar radiation were co‐dominant in mangroves. Meanwhile, both anthropogenic reclamation and restoration had substantial effects on coastal wetland carbon fluxes, and the effect of the anthropogenic perturbation in mangroves was more extensive than that in salt marshes. Furthermore, from 1980 to 2020, anthropogenic reclamation of China's coastal wetlands caused a carbon loss of ~3720 Gg C, while the mangrove restoration project during the period of 2021–2025 may switch restored coastal wetlands from a carbon source to carbon sink with a net carbon gain of 73 Gg C. The comparison of carbon fluxes among these coastal wetlands can improve our understanding of how anthropogenic perturbation can affect the potentials of coastal blue carbon in China, which has implications for informing conservation and restoration strategies and efforts of coastal wetlands.

Efficient removal and transformation of Cr(VI) from alkaline wastewater to form a ferrochromium spinel multiphase via a modified ferrite process - Yingying Lan; Yiwei Sun; Shasha Chu; Bo Yang; Lijuan Zhang; Lin Xiao; Jinlin Li; Xiaochao Yuan; Xin Yan; Vladimir V. Galvita; Xintai Su (Chemosphere, 2024)

Chemical stabilization of demolition wastes in pavement bases using one–part fly ash and slag based geopolymers - Tung Doan; Arul Arulrajah; Youli Lin; Suksun Horpibulsuk; Jian Chu; Stephen Darmawan (Transportation Geotechnics, 2024)

Relationship of single and co-exposure of per-and polyfluoroalkyl substances and their alternatives with uric acid: A community-based study in China - Li-Xia Liang; Li-Zi Lin; Mohammed Zeeshan; Yang Zhou; Yong-Xiang Tang; Chu Chu; Yun-Ting Zhang; Ru-Qing Liu; Wenru Feng; Guang-Hui Dong (Journal of Hazardous Materials, 2024)

A method to assess industrial paraffin contamination levels in rice and its transferability analysis based on transfer component analysis - Zhentao Wang; Ruidong Wang; Yuhang Chu; Guoqing Chen; Tenghui Lin; Rui Jiang; Jinfeng Wang (Food Chemistry, 2024)

RNF4 prevents genomic instability caused by chronic DNA under-replication - Marissa K. Oram; Ryan M. Baxley; Emily M. Simon; Kevin Lin; Ya-Chu Chang; Liangjun Wang; Chad L. Myers; Anja-Katrin Bielinsky (DNA Repair, 2024)

In-Situ synthesis of NbC Nanoparticle-Decorated Polyimide-Derived graphene for enhanced thermal management - Yu-Sheng Hsiao; Chao-Yuan Lin; Lin-Yang Weng; Chun-Han Hsu; Ta-Hung Cheng; Jen-Hsien Huang; Nian-Jheng Wu; Wei Kong Pang; Shih-Chieh Hsu; Huei Chu Weng; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Photo-protection and photo-inhibition during light induction in Barbula indica and Conocephalum conicum under different light gradients - Chung-I. Chen; Kuan-Hung Lin; Meng-Yuan Huang; Kuei-Yu Yao; Chau-Ching Huang; Tzu-Chao Lin; En-Liang Chu; Jia-Dong Yang; Ching-Wen Wang (Photosynthesis Research, 2024)

Integrating water and insect pest management in agriculture - Po-An Lin; Sulav Paudel; Pin-Chu Lai; Raj K. GC; Dan-Hong Yang; Gary W. Felton (Journal of Pest Science, 2024)

Morphological and physiological response of amphibious Rotala rotundifolia from emergent to submerged form - Wangai Zhao; Jibo Xiao; Guo Lin; Qianqian Peng; Shuyi Chu (Journal of Plant Research, 2024)

Inherited BRCA1 and RNF43 pathogenic variants in a familial colorectal cancer type X family - James M. Chan; Mark Clendenning; Sharelle Joseland; Peter Georgeson; Khalid Mahmood; Jihoon E. Joo; Romy Walker; Julia Como; Susan Preston; Shuyi Marci Chai; Yen Lin Chu; Aaron L. Meyers; et al. (Familial Cancer, 2024)
Genetic susceptibility to familial colorectal cancer (CRC), including for individuals classified as Familial Colorectal Cancer Type X (FCCTX), remains poorly understood. We describe a multi-generation CRC-affected family segregating pathogenic variants in both BRCA1 , a gene associated with breast and ovarian cancer and RNF43 , a gene associated with Serrated Polyposis Syndrome (SPS). A single family out of 105 families meeting the criteria for FCCTX (Amsterdam I family history criteria with mismatch repair (MMR)-proficient CRCs) recruited to the Australasian Colorectal Cancer Family Registry (ACCFR; 1998–2008) that underwent whole exome sequencing (WES), was selected for further testing. CRC and polyp tissue from four carriers were molecularly characterized including a single CRC that underwent WES to determine tumor mutational signatures and loss of heterozygosity (LOH) events. Ten carriers of a germline pathogenic variant BRCA1 :c.2681_2682delAA p.Lys894ThrfsTer8 and eight carriers of a germline pathogenic variant RNF43 :c.988 C > T p.Arg330Ter were identified in this family. Seven members carried both variants, four of which developed CRC. A single carrier of the RNF43 variant met the 2019 World Health Organization (WHO 2019 ) criteria for SPS, developing a BRAF p.V600 wildtype CRC. Loss of the wildtype allele for both BRCA1 and RNF43 variants was observed in three CRC tumors while a LOH event across chromosome 17q encompassing both genes was observed in a CRC. Tumor mutational signature analysis identified the homologous recombination deficiency (HRD)-associated COSMIC signatures SBS3 and ID6 in a CRC for a carrier of both variants. Our findings show digenic inheritance of pathogenic variants in BRCA1 and RNF43 segregating with CRC in a FCCTX family. LOH and evidence of BRCA1-associated HRD supports the importance of both these tumor suppressor genes in CRC tumorigenesis.

Micro-nano-bubbles and their application in microalgae production: Wastewater treatment, carbon capture and microalgae separation - Xiaogang You; Libin Yang; Huaqiang Chu; Lei Zhang; Yongyuan Hong; Yi Lin; Xuefei Zhou; Yalei Zhang (Algal Research, 2024)

Formulation of PG-FA-L composite modifier for repairing expansive soil based on the statistical mixed design method - Fusheng Zha; ChuanQing Hu; Bo Kang; Lin Qin; Jie Li; ChengFu Chu (Chemosphere, 2024)

Short-term exposure to ozone may trigger the onset of Kawasaki disease: An individual-level, case-crossover study in East China - Yixiang Zhu; Renjie Chen; Cong Liu; Yue Niu; Xia Meng; Su Shi; Kexin Yu; Guoying Huang; Liping Xie; Siyuan Lin; Min Huang; Meirong Huang; et al. (Chemosphere, 2024)

The skin photoprotective effect of trilinolein: Induction of cellular autophagy via the AMPK-mTOR signaling pathway - Xianghong Lin; Na Deng; Huijuan Li; Jingxian Duan; Wenqiu Chen; Tao Liu; Sujiao Sun; Jimin Chu (Toxicology and Applied Pharmacology, 2024)

A novel method for the evaluation of ship berthing risk using AIS data - Bowen Lin; Mao Zheng; Xiumin Chu; Mingyang Zhang; Wengang Mao; Da Wu (Ocean Engineering, 2024)

Error modeling and hierarchical Bayesian fusion for spaceborne and ground radar rainfall data - Leilei Kou; Ying Mao; Zhengjian Lin; Haiyang Gao; Zhigang Chu; Aijun Chen (Journal of Hydrology, 2024)

Assessment of sources and health risks of heavy metals in metropolitan household dust among preschool children: The LEAPP-HIT study - Chi-Sian Kao; Ying-Lin Wang; Chuen-Bin Jiang; Pei-Ju Tai; Yi-Hua Chen; Hsing-Jasmine Chao; Yu-Chun Lo; Zeng-Yei Hseu; Hsing-Cheng Hsi; Ling-Chu Chien (Journal of Environmental Management, 2024)

Electrosynthesis of peracetic acid using in-situ generated H2O2 enabled by carbon-based bifunctional electrodes - Zeheng Lin; Felice; George E.P. O'Connell; Tao Wan; Ding Zhang; Lingyi Peng; Dewei Chu; Xunyu Lu; Zhaojun Han (Chemical Engineering Journal, 2024)

Ultralow-Concentration (0.1M) Electrolyte for stable bulk alloy (Sn, Bi) anode in Sodium-ion battery via Regulating Anions Structure - Changting Chu; Lin Zhou; Yong Cheng; Xuxu Wang; Limin Chang; Ping Nie; Chunli Wang; Limin Wang (Chemical Engineering Journal, 2024)

Improved thermal conductivity parameterization of SHAW model in permafrost regions on the Qinghai-Tibet Plateau - Miao Liu; Lin Zhao; Guojie Hu; Yao Xiao; Minxuan Xiao; Jianting Zhao; Xiaoyu Chu; Xiangfei Li (Cold Regions Science and Technology, 2024)

PSO-Based Predictive PID-Backstepping Controller Design for the Course-Keeping of Ships - Bowen Lin; Mao Zheng; Bing Han; Xiumin Chu; Mingyang Zhang; Haiming Zhou; Shigan Ding; Hao Wu; Kehao Zhang (Journal of Marine Science and Engineering, 2024)
Ship course-keeping control is of great significance to both navigation efficiency and safety. Nevertheless, the complex navigational conditions, unknown time-varying environmental disturbances, and complex dynamic characteristics of ships pose great difficulties for ship course-keeping. Thus, a PSO-based predictive PID-backstepping (P-PB) controller is proposed in this paper to realize the efficient and rapid course-keeping of ships. The proposed controller takes the ship’s target course, current course, yawing speed, as well as predictive motion parameters into consideration. In the design of the proposed controller, the PID controller is improved by introducing predictive control. Then, the improved controller is combined with a backstepping controller to balance the efficiency and stability of the control. Subsequently, the parameters in the proposed course-keeping controller are optimized by utilizing Particle Swarm Optimization (PSO), which can adaptively adjust the value of parameters in various scenarios, and thus further increase its efficiency. Finally, the improved controller is validated by carrying out simulation tests in various scenarios. The results show that it improves the course-keeping error and time-response specification by 4.19% and 9.71% on average, respectively, which can efficiently achieve the course-keeping of ships under various scenarios.

The Influence of Seamounts on the Enrichment of Rare Earth Elements in Sediments—A Case Study of the Marcus-Wake Seamounts in the Western Pacific Ocean - Tinglu Xiao; Dong Xu; Tao Deng; Junyu Lin; Liming Ye; Qian Ge; Xibin Han; Yanhui Dong; Fengyou Chu (Journal of Marine Science and Engineering, 2024)
Deep-sea sediments enriched in rare earth elements and yttrium (REY-rich sediments) are widely distributed on the deep-sea floor, and their formation mechanism remains elusive. Although studies have recognized the link between seamounts and REY-rich sediments, in-depth analysis of the specific roles and effects of seamounts in the formation of REY-rich sediments is lacking. In this study, we analyzed surface sediments from the Marcus-Wake Seamounts for grain size, geochemistry, and mineral composition and classified the samples into three types: samples with moderate REY content and dominated by terrestrial detritus; samples with high REY and authigenic mineral content; and samples rich in CaCO3 but poor in REY. The REY in the sediments of the study area partly originate from Asian dust input and partly from seawater and/or pore water, and are mainly enriched in REY carrier particles including bioapatite fossils and micronodules. The amount of REY carrier particles influences the REY content in the sediments. The current field, primary productivity, weathering process, and depositional environment around seamounts are different from those of abyssal plains, which are conducive to the formation of REY-rich sediments. Strong bottom currents may exist in the southeastern direction of some large seamounts (e.g., Niulang Guyot), leading to the selective accumulation of REY-rich bioapatite fossils and micronodules, resulting in the formation of REY-rich sediments.

CFD- and BPNN- based investigation and prediction of air pollutant dispersion in urban environment - Xisheng Lin; Yunfei Fu; Daniel Z. Peng; Chun-Ho Liu; Mengyuan Chu; Zengshun Chen; Fan Yang; Tim K.T. Tse; Cruz Y. Li; Xinxin Feng (Sustainable Cities and Society, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Transient ground bulge derived from a dense broadband seismic array during an aquifer step-drawdown pumping test - Wu-Cheng Chi; Chu-Fang Yang; Sebastian Wege; Chin-Jen Lin; Chien-Chung Ke (Journal of Hydrology, 2024)

Application of nZnO supported with nanoclay for improving shrimp immunity - Zhen-Hao Liao; Chieh-Yuan Chuang; Yin-Yu Chen; Yu-Ting Chu; Yeh-Fang Hu; Po-Tsang Lee; Jiang-Jen Lin; Fan-Hua Nan (Fish & Shellfish Immunology, 2024)

Global, regional, and national burden of ischemic heart disease attributable to ambient PM2.5 from 1990 to 2019: An analysis for the global burden of disease study 2019 - Li-Hao Guo; Li-Zi Lin; Yang Zhou; Bin Jalaludin; Lidia Morawska; Shyamali C. Dharmage; Luke D. Knibbs; Guo-Feng Huang; Duo-Hong Chen; Huimin Ma; Meng Gao; Joachim Heinrich; et al. (Environmental Research, 2024)

Phosphorus-containing reactive compounds to prepare fire-resistant vinyl resin for composites: Effects of flame retardant structures on properties and mechanisms - Mingming Yu; Yuji Chu; Wang Xie; Lin Fang; Ousheng Zhang; Musu Ren; Jinliang Sun (Chemical Engineering Journal, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Importance of lighting color and period for CO2 fixation and C-phycocyanin production during Thermosynechococcus sp. CL-1 growth - Birgitta Narindri Rara Winayu; Yu-Ting Lin; Hsin-Ta Hsueh; Hsin Chu (Biocatalysis and Agricultural Biotechnology, 2024)

Evaluation of polyphenols content and antioxidant ability of commercial herbal beer - Rui Lin; Xingguang Chen; Zhengcong Peng; Wenzhe Li; Jiyang Chu; Jian Lu; Guangfa Xie; Dianhui Wu (Systems Microbiology and Biomanufacturing, 2024)

Matrine Mediated Immune Protection in MS by Regulating Gut Microbiota and Production of SCFAs - Mengmeng Dou; Yaojuan Chu; Xueliang Zhou; Mengru Wang; Xinyu Li; Rui Ma; Zhirui Fan; Xiaoyu Zhao; Wenbin Wang; Silu Li; Ying Lv; Lin Zhu (Molecular Neurobiology, 2024)

Authentication of Asini Corii Colla and Taurus Corii Colla based on UPLC-MS/MS and the discovery of antioxidant peptides associated with the PI3K-AKT pathway - Wei Wang; Lin Chu; Liqun Chen; Rong Yang; Shaoqing Zhu; Yuanbin Zhang; Huan Yang (Natural Product Research, 2023)

Insulin regulates gap junction intercellular communication in porcine granulosa cells through modulation of connexin43 protein expression - Lin Yin; Wusu Wang; Weijun Pang; Gongshe Yang; Lei Gao; Guiyan Chu (Theriogenology, 2023)

What drives the spatial heterogeneity of cropping patterns in the Northeast China: The natural environment, the agricultural economy, or policy? - Zhe Yang; Lin Chu; Chen Wang; Yan Pan; Wenxia Su; Yulu Qin; Chongfa Cai (Science of The Total Environment, 2023)

Fragmentation of continental subduction is ending the Himalayan orogeny - Xiaofeng Liang; Yang Chu; Bo Wan; Ling Chen; Lin Chen; Eric Sandvol; Stephen P. Grand; Yibing Li; Minling Wang; Xiaobo Tian; Yun Chen; Tao Xu; et al. (Science Bulletin, 2023)

Yuexiconcha nov. gen. – A resilifer-bearing palaeotaxodont (Bivalvia, Protobranchia) from the Ordovician of Guangdong, South China - Zhi-jun Niu; Ren-jie Zhang; Paul A. Johnston; Chu-an Li; Zhi-hong Wang; Kun Hu; Fang Song; Yao-yan He; Jin-lan He; Xiao-ming Lin; Wen-qiang Yang (Geobios, 2023)

Integrated multifunctional nanoplatform for fluorescence detection and inactivation of Staphylococcus aureus - Jing-bo Jiao; Qing Kang; Jiang-li Cao; Shuai-qi Zhang; Chen-jing Ma; Tong Lin; Ze-hui Xiao; Chu-min Zhao; Ting Du; Xin-jun Du; Shuo Wang (Food Chemistry, 2023)

3D binder-free nanoarchitecture design of porous silicon/graphene fibers for ultrastable lithium storage - Yongbiao Mu; Ruijie Zhang; Bu-ke Wu; Ming Yang; Youqi Chu; Qing Zhang; Lingfeng Zou; Xianbin Wei; Zifan Liao; Haixiang Ren; Yiju Li; Lin Zeng (Chemical Engineering Journal, 2023)

Assessing the Impacts of Wetlands on Discharge and Nutrient Loading: Insights from Restoring Past Wetlands with GIS-Based Analysis and Modeling - Mosammat Mustari Khanaum; Tiansong Qi; Kyle D. Boutin; Marinus L. Otte; Zhulu Lin; Xuefeng Chu (Wetlands, 2023)

Rapid Genotyping of Campylobacter coli Strains from Poultry Meat by PFGE, Sau-PCR, and fla-DGGE - Ge-Feng Yao; Yi-Lin Hu; Nian-Qing Kong; Jin-Hong Liu; Yong-Wen Luo; Chu-Yi Li; Shui-Lian Bi (Current Microbiology, 2023)

Effectiveness and safety of botulinum neurotoxin for treating dyssynergic defecation: A systematic review and meta-analysis - Ching-Yu Chu; Yu-Chi Su; Pei-Chun Hsieh; Yu-Ching Lin (Toxicon, 2023)

Stereochemical insights into structurally diverse lignanamides from the herbs of Solanum lyratum Thunb. - Ye Chang; Ming Bai; Xin Zhang; Jiao-Yang Hou; Cheng-Yu Chu; Jia-Qi Niu; Guo-Dong Yao; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Propeller-shaft-hull coupling acoustic radiation characteristics induced by friction self-excitation of the stern bearing - Chang-Gang Lin; Ming-Song Zou; Li-Bo Qi; Can Sima; Ji-Long Chu (Ocean Engineering, 2023)

Experimental study on enhanced coal seam gas extraction by uniform pressure/pulse pressure N2 injection - Peng-fei Ji; Hai-fei Lin; Xiang-guo Kong; Shu-gang Li; Yu-chu Cai; Rui-zhe Wang; Yu Tian; Tian-shuo Zhao (Fuel, 2023)

Prenatal and postnatal exposure to heavy metals in PM2.5 and autism spectrum disorder - Hao-Hsuan Lin; Chau-Ren Jung; Chuan-Yao Lin; Ya-Chu Chang; Chia-Yun Hsieh; Pei-Chuan Hsu; Bao-Ru Chuang; Bing-Fang Hwang (Environmental Research, 2023)

The NOx-O3 photochemical reactive air pollutant dispersion around an isolated building—the role of turbulence model and building aspect ratio - Yunfei Fu; Xisheng Lin; Lu Li; Mengyuan Chu; Chun-Ho Liu; Zengshun Chen; Cruz Y. Li; K.T. Tse (Building and Environment, 2023)

A novel approach for predicting the concentration of exhaled aerosols exposure among healthcare workers in the operating room - Zhijian Liu; Zhenzhe Huang; Jiaqi Chu; Haochuan Li; Junzhou He; Chaofan Lin; Chuan Jiang; Guangpeng Yao; Shuanghuai Fan (Building and Environment, 2023)

Associations between parental and postnatal metal mixture exposure and developmental delays in a Taiwanese longitudinal birth cohort of preschool children - Chi-Sian Kao; Yen-Tzu Fan; Ying-Lin Wang; Yi-Hua Chen; Hsing-Jasmine Chao; Yu-Chun Lo; Chuen-Bin Jiang; Ling-Chu Chien (Environmental Science and Pollution Research, 2023)

Legacy per- and polyfluoroalkyl substances (PFASs) especially alternative PFASs in shellfish from Shandong Province, China: Distribution, sources, and health risk - Jiacheng Zhang; Wei Li; Luping Yang; Zunhua Chu; Yanni Jiao; Lin Wang; Lijun Zhu; Chuan Qin; Rui Liu; Xibao Gao (Marine Pollution Bulletin, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

NiCo/SiO2 nanospheres for efficient synergetic decarboxylation of fatty acids and upgrading of municipal sludge HTL bio-crude to biofuels - Hongju Lin; Yanchang Chu; Mingyu Xie; Le Yang; Gangfeng Ouyang (Journal of Environmental Chemical Engineering, 2023)

Flash-ignition of carbon black synthesized from acetylene diffusion flames and its application as ignition agents - Chih-Yung Wu; Yi-Chu Chen; Tse-Hao Wang; Po-Han Lin; Yi-Kuan Kuo (Fuel, 2023)

Removal of antibiotic-resistant bacteria and genes by Solar-activated Ferrate/ Peroxymonosulfate: Efficiency in aquaculture wastewater and mechanism - Ruixue Li; Xudai Wu; Zhenfei Han; Lijie Xu; Lu Gan; Yanqiong Zhang; Fengru Lu; Hua Lin; Xue Yang; Muting Yan; Wei Chu; Han Gong (Chemical Engineering Journal, 2023)

Revealing the solid-solution interface interference behaviors between Cu2+ and As(III) via partial peak area analysis of simulations and experiments - Bo Liang; Xiang-Yu Xiao; Zong-Yin Song; Yong-Yu Li; Xin Cai; Rui-Ze Xia; Shi-Hua Chen; Meng Yang; Pei-Hua Li; Chu-Hong Lin; Xing-Jiu Huang (Analytica Chimica Acta, 2023)

An overview of scholarly literature on navigation hazards in Arctic shipping routes - Bowen Lin; Mao Zheng; Xiumin Chu; Wengang Mao; Daiyong Zhang; Mingyang Zhang (Environmental Science and Pollution Research, 2023)

Environmental pollutant pre- and polyfluoroalkyl substances are associated with electrocardiogram parameters disorder in adults - Yuan-Yuan Fan; Chu Chu; Yun-Ting Zhang; Kun Zhao; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Lu-Yin Wu; Li-Zi Lin; Ru-Qing Liu; Wenru Feng; et al. (Journal of Hazardous Materials, 2023)

Temporal transition trends of cord blood lead levels in various human development index countries and in the Taipei metropolitan area - Yaw-Huei Hwang; Hui-Chu Wu; Ming-Kwang Shyu; Chien-Nan Lee; Shin-Yu Lin; Pau-Chung Chen; Hung-Yi Chuang; Pei-Wen Lin; Tso-Hsien Wu; Yen-Tzu Chen (Environmental Pollution, 2023)

Integrated single-cell RNA-seq analysis revealed podocyte injury through activation of the BMP7/AMPK/mTOR mediated autophagy pathway - Hongzhou Lin; Huihui Chen; Rengcheng Qian; Guoqi Tang; Yinjuan Ding; Yalan Jiang; Congde Chen; Dexuan Wang; Maoping Chu; Xiaoling Guo (Chemico-Biological Interactions, 2023)

A Self-attention Graph Convolutional Network for Precision Multi-tumor Early Diagnostics with DNA Methylation Data - Xue Jiang; Zhiqi Li; Aamir Mehmood; Heng Wang; Qiankun Wang; Yanyi Chu; Xueying Mao; Jing Zhao; Mingming Jiang; Bowen Zhao; Guanning Lin; Edwin Wang; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2023)

First report of anthracnose-twister disease of welsh onion caused by Colletotrichum siamense in Taiwan - Chin-Ya Yuan; Chiao-Wen Huang; Chu-Ping Lin; Jin-Hsing Huang (Journal of General Plant Pathology, 2023)

A novel diagnostic signature of circulating tsRNAs and miRNAs in esophageal squamous cell carcinoma detected with a microfluidic platform - Di Huang; Yujin Chu; Jiaoyan Qiu; Xiaoshuang Chen; Junhua Zhao; Yu Zhang; Shunjia Li; Yufeng Cheng; Han Shi; Lin Han; Jianbo Wang (Analytica Chimica Acta, 2023)

Image-based estimation of crown volume of individual street trees by plane calculation of angle disparity - Chenbing Guo; Yonghong Hu; Jun Qin; Lin Xu; Meihan Chu; Hongbing Wang (Urban Forestry & Urban Greening, 2023)

Dietary administration of a postbiotic, heat-killed Pediococcus pentosaceus PP4012 enhances growth performance, immune response and modulates intestinal microbiota of white shrimp, Penaeus vannamei - Rolissa Ballantyne; Jai-Wei Lee; Sz-Tsan Wang; Jin-Seng Lin; Deng-Yu Tseng; Yi-Chu Liao; Hsiao-Tung Chang; Ting-Yu Lee; Chun-Hung Liu (Fish & Shellfish Immunology, 2023)

Maternal exposure to fine particulate matter and congenital heart defects during preconception and pregnancy period: A cohort-based case-control study in the Taiwan maternal and child health database - Ya-Chu Chang; Yu-Ting Lin; Chau-Ren Jung; Ke-Wei Chen; Bing-Fang Hwang (Environmental Research, 2023)

Neuroprotective Effects of Oxymatrine via Triggering Autophagy and Inhibiting Apoptosis Following Spinal Cord Injury in Rats - Jian Li; Yang Cao; Lin-Na Li; Xin Chu; Yan-Song Wang; Jia-Jun Cai; Jin Zhao; Song Ma; Gang Li; Zhong-Kai Fan (Molecular Neurobiology, 2023)

Oral and inhalation bioaccessibility of mercury in contaminated soils and potential health risk to the kidneys and neurodevelopment of children in Taiwan - Ying-Lin Wang; Ming-Chien Mark Tsou; Li-Chi Lai; Zeng-Yei Hseu; Hsing-Cheng Hsi; Ling-Chu Chien (Environmental Geochemistry and Health, 2023)

Association between Glyphosate Exposure and Erythrograms in a Representative Sample of US Adults: NHANES 2013–2014 - Ming-Hao Chang; Pei-Lun Chu; ChiKang Wang; Chien-Yu Lin (Environmental Science and Pollution Research, 2023)

Culturing reef-building corals on a laboratory dish: a simple experimental platform for stony corals - Shinya Shikina; Tzu-Chieh Lin; Yu-Ling Chu; Yin-Chu Cheng; Yu-En Chang; Naohisa Wada; Sen-Lin Tang; Yoshiyuki Iizuka; Yi-Ling Chiu (Frontiers in Marine Science, 2023)
Development and maintenance of coral reef ecosystems rely on daily micro-biological activities of healthy corals. Although a comprehensive understanding of coral biological properties, as well as factors negatively affecting coral growth, are essential to conserve existing corals, the current lack of a tractable culture and experimental platform has delayed acquisition of such knowledge. Here we show a highly versatile culture system, “coral-on-a-laboratory dish” (CLD), allowing long-term culturing of various corals in plastic/glass Petri dishes with maintenance of their biological properties. Under optimized conditions, coral microcolonies (~5 mm x 5 mm fragments) of Pocillopora damicornis were cultured for several months in dishes with high survivorship and characteristic growth. These microcolonies maintained their biological properties, such as reproduction, skeleton formation, coral-algal symbiosis, ingestion, and digestion. Thus far, CLD has been used to maintain at least 4 other coral species from 4 other families, including the Acroporidae, the Pocilloporidae, the Poritidae, and the Merulinidae for more than 2 months with 100% survivorship. CLD is applicable to a variety of biophysiological studies, including coral-algal symbiosis and impact assessment of marine pollutants, e.g., a sunscreen substance, oxybenzone, and an organic biocide, Irgarol 1051, at cellular-level resolution. The CLD platform, which allows easy and inexpensive coral maintenance in a laboratory incubator, represents a technological breakthrough that will greatly advance coral studies.

Heterogeneity of the Ailaoshan–Song Ma ophiolitic mélange and its palaeogeographic implications for the evolution of Eastern Palaeo-Tethys - Fei Liu; Wei Lin; Yin Wang; Lingtong Meng; Michel Faure; Vuong Van Nguyen; Qinying Wu; Yang Chu; Wei Wei; Hoai Luong Thi Thu; Tich Van Vu; Qiuli Li; et al. (Tectonophysics, 2023)

An interlayer flame retardant method to effectively fire retardant and reinforce CF/EP composites by nanofiber film intercalation - Mingming Yu; Yuji Chu; Wang Xie; Lin Fang; Xueqiang Liu; Ousheng Zhang; Musu Ren; Jinliang Sun (Chemical Engineering Journal, 2023)

Vegetable extracts: Effective inhibitors of heterocyclic aromatic amines and advanced glycation end products in roasted Mackerel - Simin Zhang; Ruichun Wang; Junbo Chu; Chenyang Sun; Songyi Lin (Food Chemistry, 2023)

Long-term DEHP/MEHP exposure promotes colorectal cancer stemness associated with glycosylation alterations - Pei-Chun Shih; Hsin-Pao Chen; Ching-Cheng Hsu; Chung-Hsien Lin; Chou-Yuan Ko; Chao-Wen Hsueh; Cheng-Yi Huang; Tian-Huei Chu; Cheng-Chun Wu; Yu-Cheng Ho; Ngoc Uyen Nhi Nguyen; Shih-Chung Huang; et al. (Environmental Pollution, 2023)

Synergistic structure of LiFeO2 and Fe2O3 layers with electrostatic shielding effect to suppress surface lattice oxygen release of Ni-rich cathode - Youqi Chu; Yongbiao Mu; Lingfeng Zou; Jie Cheng; Shibo Xi; Qichang Pan; Meisheng Han; Hongqiang Wang; Qingyu Li; Fenghua Zheng; Qing Zhang; Lin Zeng (Chemical Engineering Journal, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Insight into copper-cerium catalysts with different Cu valence states for CO-SCR and in-situ DRIFTS study on reaction mechanism - Jinfeng Li; Jiexuan Zhu; Shiying Fu; Lin Tao; Bingxian Chu; Qiuju Qin; Jingkai Wang; Bin Li; Lihui Dong (Fuel, 2023)

Cadmium exposure induces histological damage and cytotoxicity in the cardiovascular system of mice - Shing-Hsien Chou; Hung-Chen Lin; Shao-Wei Chen; Yu-Ting Tai; Shih-Ming Jung; Fu-Hsiang Ko; Jong-Hwei Su Pang; Pao-Hsien Chu (Food and Chemical Toxicology, 2023)

Plant and fungal species interactions differ between aboveground and belowground habitats in mountain forests of eastern China - Teng Yang; Leho Tedersoo; Pamela S. Soltis; Douglas E. Soltis; Miao Sun; Yuying Ma; Yingying Ni; Xu Liu; Xiao Fu; Yu Shi; Han-Yang Lin; Yun-Peng Zhao; et al. (Science China Life Sciences, 2023)

Release, denitrification performance, and generated waste utilization of alkali-modified lignocellulosic materials as denitrification carbon sources - Zhiyuan Lin; Yu Ling; Guokai Yan; Haiyan Wang; Zhuanjun Zhao; Yang Chang; Weiyang Dong; Huan Wang; Zhaosheng Chu; Shuqi Guan; Yanjie Zhang; Fan Guo (Journal of Water Process Engineering, 2023)

Highly sensitive detection of lead ions and cadmium ions based on ZIF-8-NH2 enhanced by carbon nanotubes and bismuth film - Xingguang Chen; Tingting Xie; Chaoqun Lu; Jiyang Chu; Wenzhe Li; Rui Lin; Dianhui Wu; Qianhui Gu (Journal of Environmental Chemical Engineering, 2023)

Valorizing kitchen waste to produce value-added fertilizer by thermophilic semi-continuous composting followed by static stacking: Performance and bacterial community succession analysis - Xiang-Yu Peng; Shi-Peng Wang; Xiu-Lin Chu; Zhao-Yong Sun; Zi-Yuan Xia; Cai-Yun Xie; Min Gou; Yue-Qin Tang (Bioresource Technology, 2023)

Short-term Medication Effects on Brain Functional Activity and Network Architecture in First-Episode psychosis: a longitudinal fMRI study - Yajuan Zhang; Qiong Xiang; Chu-Chung Huang; Jiajia Zhao; Yuchen Liu; Ching-Po Lin; Dengtang Liu; Chun-Yi Zac Lo (Brain Imaging and Behavior, 2023)

Complete genome of Sphingomonas paucimobilis ZJSH1, an endophytic bacterium from Dendrobium officinale with stress resistance and growth promotion potential - Jin Li; Hangtao Wu; Qian Pu; Chu Zhang; Ying Chen; Zhengxin Lin; Xiufang Hu; Ou Li (Archives of Microbiology, 2023)

Association between long-term exposure to air pollution and the risk of incident laryngeal cancer: a longitudinal UK Biobank-based study - Jiada Wang; Chen Lin; Yidian Chu; Hongxia Deng; Zhisen Shen (Environmental Science and Pollution Research, 2023)
We assessed the association between long-term joint exposure to ambient air pollutants and the risk of laryngeal cancer and whether this risk was modified by genetic susceptibility. We used a multivariable Cox proportional hazards regression model to analyze data from UK Biobank to determine the relationship between long-term exposure to air pollutants–nitric oxide (NO), nitrogen dioxide (NO 2 ), and 2.5- µ m and 10- µ m particulate matter (PM 2.5 and PM 10 ) and the risk of laryngeal cancer. In multivariable-adjusted models, in model 3 and compared with the participants with lower quintile scores for air pollution, the participants with the highest quintile scores for air pollution had a higher laryngeal cancer risk. The observed association was more pronounced among the participants who were female, were smokers, had a systolic blood pressure equal to or greater than 120 mmHg, and had diabetes. Compared with the participants with a low GRS and the lowest quintile score for air pollution exposure, those with an intermediate GRS and the highest quintile score for air pollution exposure had a higher risk of laryngeal cancer. Long-term exposure to NO 2 , NO, or PM 2.5 , individually or jointly, was associated with a risk of incident laryngeal cancer, especially in the participants with an intermediate GRS.

Heterogeneous effects of other-regarding interventions on household recycling: A field experimental study - Maoliang Ling; Lin Xu; Xiaojing Chu (Journal of Environmental Management, 2023)

Identification and hepatoprotective activity of total glycosides of paeony with high content of paeoniflorin extracted from Paeonia lactiflora Pall - Lin Peng; Zhe Ma; Wenhui Chu; Peisi Jiang; Yongqian Fu; Pan Wang (Food and Chemical Toxicology, 2023)

Macroscale superlubricity and durability of in situ grown hydrogenated graphene coatings - Shuyu Fan; Shu Xiao; Songsheng Lin; Fenghua Su; Yifan Su; Paul K. Chu (Chemical Engineering Journal, 2023)

The spongiform tissue in Strumigenys ants contains exocrine glands - Chu Wang; Fu-Ya Chung; Chung-Chi Lin; Joshua C. Gibson; Sara McGuire; Andrew V. Suarez; Johan Billen (Arthropod Structure & Development, 2023)

Plastic film-mulched ridges and straw-mulched furrows increase soil carbon sequestration and net ecosystem economic benefit in a wheat-maize rotation - Xiaoqi Luo; Cheng Li; Nanping Lin; Naijiang Wang; Xiaosheng Chu; Hao Feng; Haixin Chen (Agriculture, Ecosystems & Environment, 2023)

Chemical investigations and cytotoxic effects of metabolites from Antrodia camphorata against human hepatocellular carcinoma cells - Yih-Fung Chen; Ho-Cheng Wu; Jia-Min Chang; Horng-Huey Ko; Chu-Hung Lin; Hsun-Shuo Chang (Natural Product Research, 2023)

Bioaerosol dispersion and environmental risk simulation: Method and a case study for a biopharmaceutical plant of Gansu province, China - Xin Xu; Chengxin Wang; Peng Wang; Yinghao Chu; Jing Guo; Xin Bo; Aijun Lin (Science of The Total Environment, 2023)

Promoting removal of copper from sediment and production of bioelectricity by sediment microbial fuel cells using tea extracts - Shu-Hui Liu; Chu-Yuan Yang; Chi-Wen Lin; Ting-Jun Zhu (Journal of Water Process Engineering, 2023)

A self-assembly hydrophobic oCDs/Ag nanoparticles SERS sensor for ultrasensitive melamine detection in milk - Jiaoyan Qiu; Yujin Chu; Qihang He; Yingkuan Han; Yu Zhang; Lin Han (Food Chemistry, 2023)

A highly-sensitive sensor based on carbon nanohorns@reduced graphene oxide coated by gold platinum core–shell nanoparticles for electrochemical detection of carbendazim in fruit and vegetable juice - Wenzhe Li; Peixuan Wang; Beibei Chu; Xingguang Chen; Zhengcong Peng; Jiyang Chu; Rui Lin; Qianhui Gu; Jian Lu; Dianhui Wu (Food Chemistry, 2023)

Lactoferrin attenuated urban particulate matter-induced nephrotoxicity by regulating the CSF2/CENPE axis - Wen-Chih Liu; Hui-Wen Chiu; Chu-Lin Chou; Yu-Jhe Chiu; Yu-Hsuan Lee (Environmental Pollution, 2023)

Encapsulating selenium into mesoporous carbon for high-performance aqueous Cu-Se battery - Zhouxiang Wu; Xia Lin; Junwei Zhang; Xiquan Chu; Jiaxi Xu; Jing Li; Yiwen Liu; Haoxiang Yu; Lei Yan; Liyuan Zhang; Jie Shu (Chemical Engineering Journal, 2023)

Clay nanosheets simultaneously intercalated and stabilized by PEGylated chitosan as drug delivery vehicles for cancer chemotherapy - Hsuan-Jung Huang; Shih-Yu Huang; Tzu-Hao Wang; Tzu-Yun Lin; Nan-Ching Huang; Orion Shih; U-Ser Jeng; Che-Yi Chu; Wen-Hsuan Chiang (Carbohydrate Polymers, 2023)

Comparisons of three-dimensional reflectivity and precipitation rate from GPM dual-frequency precipitation radar and ground dual-polarization radar - Leilei Kou; Ying Mao; Zhixuan Wang; Zhengjian Lin; Yao Chen; Haiyang Gao; Zhigang Chu; Aijun Chen (Atmospheric Research, 2023)

Dual bio-degradative pathways of di-2-ethylhexyl phthalate by a novel bacterium Burkholderia sp. SP4 - Yen-Shun Hsu; Yung-Hsin Liu; Chu-Hsuan Lin; Chih-Hsuan Tsai; Whei-Fen Wu (World Journal of Microbiology and Biotechnology, 2023)

Immunomodulatory Biomaterials and Emerging Analytical Techniques for Probing the Immune Micro-Environment - Nanyan Bian; Chenyu Chu; Shengan Rung; Vicha Huangphattarakul; Yi Man; Jie Lin; Chen Hu (Tissue Engineering and Regenerative Medicine, 2023)

Corrigendum to Correlation among the Ailaoshan-Song Ma-Song Chay orogenic belts and implications for the evolution of the eastern Paleo-Tethys Ocean [Tectonophysics 843 (2022) 229618]. - Yin Wang; Wei Lin; Michel Faure; Vuong Van Nguyen; Lingtong Meng; Yang Chu; Wei Wei; Hoai Luong Thi Thu; Claude Lepvrier; Tich Van Vu; Qiuli Li; Hao Wang; et al. (Tectonophysics, 2023)

Within-species plant phylogeny drives ectomycorrhizal fungal community composition in tree roots along a timberline - Teng Yang; Luyao Song; Han-Yang Lin; Ke Dong; Xiao Fu; Gui-Feng Gao; Jonathan M. Adams; Haiyan Chu (Soil Biology and Biochemistry, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Do sustainability committees reduce electricity use in Taiwan? Mitigating electricity regulation as motivation - Yu-Lin Chen; Mei-Chu Huang (Journal of Cleaner Production, 2023)

Partitioning behavior-oriented health risk assessment on internal organophosphorus flame retardants exposure - Quan Zhang; Mengjie Chu; Shu Lin; Jianlin Lou; Cui Wang (Environmental Research, 2023)

Oxidative stress and immune response of hepatopancreas in Chinese mitten crab Eriocheir sinensis under lipopolysaccharide challenge - Lin Zhou; Lanlu Chu; Jinliang Du; Zhijuan Nie; Liping Cao; Jiancao Gao; Gangchun Xu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Intimate interaction of TFSI− anions with MoO3−x oxygen vacancies boost ionic conductivity of cathode-supported solid polymer electrolyte - Rohan Paste; Chintam Hanmandlu; Po-Yu Su; Cheng-Hung Hou; Hsin-An Chen; Chun-Wei Pao; Jing-Jong Shyue; Kuei-Hsien Chen; Heng-Liang Wu; Hong-Cheu Lin; Chih Wei Chu (Chemical Engineering Journal, 2023)

Black phosphorus nanosheets suppress oxidative damage of stem cells for improved neurological recovery - Fumei He; Zeqi Liu; Jian Xu; Yue Xiong; Xiaopei Zhang; Junyang Qi; Xun Lin; Chengjun Chu; Lan Shen; Gan Liu; Wenbin Deng (Chemical Engineering Journal, 2023)

Dimerization induces bimodality in protein number distributions - Ming-Yang Ling; Lin-Jie Chiu; Ching-Chu Hsieh; Che-Chi Shu (BioSystems, 2023)

Shanghai Autism Early Development: An Integrative Chinese ASD Cohort - Yuan Dai; Yuqi Liu; Lingli Zhang; Tai Ren; Hui Wang; Juehua Yu; Xin Liu; Zilin Chen; Lin Deng; Minyi Tao; Hangyu Tan; Chu-Chung Huang; et al. (Neuroscience Bulletin, 2022)

Effects of Ran-GTP/importin β inhibition on the meiotic division of porcine oocytes - Yijing He; Jia Li; Lei Peng; Qiao Li; Yajie Chu; Qixin Lin; Jianjun Dai; Rong Rui; Shiqiang Ju (Histochemistry and Cell Biology, 2022)

A shallow constructed wetland combining porous filter material and Rotala rotundifolia for advanced treatment of municipal sewage at low HRT - Jibo Xiao; Guo Lin; Zhuangzhuang Cao; Shuyi Chu; Lingzhou Cui; Yunlong Yang; Xiangting Wu (Environmental Science and Pollution Research, 2022)

Impact of Spatial Variation and Uncertainty of Rainfall Intensity on Urban Flooding Assessment - Ruozhou Lin; Feifei Zheng; Yiyi Ma; Huan-Feng Duan; Shipeng Chu; Zhengzhi Deng (Water Resources Management, 2022)

ACC deaminase-encoding Pseudomonas putida arrests seed germination: an alternative strategy for grass and weed control - Di Zhou; Jia-Ling Zhao; Rui Wang; Hai-Lin Wang; Daniela D. Herrera-Balandrano; Tang-Min Chen; Xiao-Feng Lu; Xu-Chu Duan; Mahdi Shahriar; Xin-Chi Shi; Pedro Laborda; Su-Yan Wang (Plant and Soil, 2022)

Hepatocyte steatosis inhibits hepatitis B virus secretion via induction of endoplasmic reticulum stress - Qichuang Liu; Maoyuan Mu; Huan Chen; Guoyuan Zhang; Yanqing Yang; Jun Chu; Ying Li; Fangwan Yang; Shide Lin (Molecular and Cellular Biochemistry, 2022)

Groundwater vulnerability assessment of shallow aquifer in the South Texas sand sheet using a GIS-based DRASTIC model - Syed Istiyak Ahmed; Chu-Lin Cheng; Juan Gonzalez; James J. Kang; Jungseok Ho; Leslie Soto-Sanchez (Modeling Earth Systems and Environment, 2022)

An integrated analysis of pond ecosystem around Poyang Lake: assessment of water quality, sediment geochemistry, phytoplankton and benthic macroinvertebrates diversity and habitat condition - Wei Liu; Qiyang Tan; Yifan Chu; Jinmei Chen; Lingli Yang; Lin Ma; Yi Zhang; Zhenbin Wu; Feng He (Aquatic Ecology, 2022)

Assessing the effective spatial characteristics of input features through physics-informed machine learning models in inundation forecasting during typhoons - Bing-Chen Jhong; Chung-Yi Lin; You-Da Jhong; Hsiang-Kuan Chang; Jung-Lien Chu; Hsi-Ting Fang (Hydrological Sciences Journal, 2022)

Correction to: Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2022)

Modelling the variation of demersal fish distribution in Yellow Sea under climate change - Yugui Zhu; Yuting Lin; Jiansong Chu; Bin Kang; Gabriel Reygondeau; Qianshuo Zhao; Zhixin Zhang; Yunfeng Wang; William W. L. Cheung (Journal of Oceanology and Limnology, 2022)

Diminished miR-374c-5p negatively regulates IL (interleukin)-6 in unexplained recurrent spontaneous abortion - Lin Zhao; Li Han; Guozhen Hei; Ran Wei; Zhen Zhang; Xiaoxiao Zhu; Qiang Guo; Chu Chu; Xiaoxiao Fu; Ke Xu; Xia Li (Journal of Molecular Medicine, 2022)

Fine particulate matter measured by satellites predicts the risk of age-related macular degeneration in a longitudinal cohort study - Chung-Ling Liang; Chi-Min Wang; Chau-Ren Jung; Ya-Chu Chang; Chun-Ju Lin; Yu-Ting Lin; Bing-Fang Hwang (Environmental Science and Pollution Research, 2022)

Effect of starvation and refeeding on reactive oxygen species, autophagy and oxidative stress in Chinese perch ( Siniperca chuatsi ) muscle growth - Ping Wu; Lin Chen; Jia Cheng; Yaxiong Pan; Xin Zhu; Wuying Chu; Jianshe Zhang (Journal of Fish Biology, 2022)
In skeletal muscle, autophagy regulates the development and growth of muscle fibres and maintains the normal muscle metabolism. Under starvation and refeeding conditions, the effect of reactive oxygen species (ROS) levels on skeletal muscle autophagy is still unclear, although the excessive accumulation of ROS has been shown to increase autophagy in cells. The purpose of this study was to explore the effects of starvation and diet after starvation on the autophagy of adult Chinese perch muscle, and to determine the level of ROS in the muscle. We performed zero (Normal control), three and seven starvation treatments on adult Chinese perch, and returned to normal feeding for 3 days after starvation for 7 days. In the muscles of the adult Chinese perch muscle after 3 days of starvation, the autophagy marker protein LC3 and the number of autophagosomes remained basically the same as in the normal feeding situation. However, on starvation for 7 days, the mitochondrial autophagy was sensitive and the number of autophagosomes increased, but the antioxidant‐related molecules (malondialdehyde, catalase, glutathione S‐transferase, glutathione and anti‐superoxide anion) decreased and the accumulation of ROS was obvious. In addition, the extended starvation time also increased the level of LC3 protein. However, by refeeding after starvation this nutritional stress resulted in a decrease in ROS levels and a partial restoration of antioxidant enzyme activity. Our data show that in the adult Chinese perch muscle, starvation could reduce the antioxidant activity through the accumulation of ROS, and that the number of autophagosomes continues to increase. Refeeding after starvation could effectively compensate for the level of ROS, and restore the mRNA abundance of antioxidant genes and the activity of antioxidant enzymes to reduce autophagy and improve feed efficiency. Further research should optimize starvation conditions to reduce autophagy in muscles and maintain normal muscle metabolism.

Perfusion Defects and Collateral Flow Patterns in Acute Small Subcortical Infarction: a 4D Dynamic MRI Study - Yen-Chu Huang; Jiann-Der Lee; Yi-Ting Pan; Hsu-Huei Weng; Jen-Tsung Yang; Leng-Chieh Lin; Yuan-Hsiung Tsai (Translational Stroke Research, 2022)
The hemodynamic changes of acute small subcortical infarction (SSI) are not well understood. We evaluate the hemodynamic changes and collaterals in acute SSI using perfusion magnetic resonance imaging (MRI). A total of 103 patients with acute SSI in penetrating artery territories were recruited and underwent MRI within 24 h of stroke onset. Using 4D dynamic perfusion MRI, they were divided into three patterns: 25 (24%) with normal perfusion, 31 (30%) with compensated perfusion, and 47 (46%) with hypoperfusion. The development of anterograde or retrograde collaterals was also evaluated. Patients with hypoperfusion pattern had the highest rate of early neurological deterioration (32%, p = 0.007), the largest initial and final infarction volumes ( p < 0.001 and p = 0.029), the lowest relative cerebral blood flow (0.63, p < 0.001), and the lowest rate of anterograde and retrograde collaterals (19%, p < 0.001; 66%, p = 0.002). The anterograde collaterals were associated with higher relative cerebral blood volume (0.91 vs. 0.77; p = 0.024) and a higher rate of deep cerebral microbleeds (48 vs. 21%; p = 0.028), whereas retrograde collaterals were associated with higher systolic and diastolic blood pressure ( p = 0.031 and 0.020), smaller initial infarction volume (0.81 vs. 1.34 ml, p = 0.031), and a higher rate of lobar cerebral microbleeds (30 vs. 0%; p = 0.013). Both anterograde and retrograde collaterals may play a critical role in maintaining cerebral perfusion and can have an impact on patient clinical outcomes. Further studies are warranted to verify these findings and to investigate effective treatments.

The Impact of the Antipsychotic Medication Chlorpromazine on Cytotoxicity through Ca2+ Signaling Pathway in Glial Cell Models - Che-Sheng Chu; Yung-Shang Lin; Wei-Zhe Liang (Neurotoxicity Research, 2022)

The optimal combination of Nile red identification, colony polymerase chain reaction, and gas chromatography detection methods in screening for polyhydroxyalkanoicate-producing bacteria - Hung-Che Chou; Chia-Hsin Chen; Hsiao-Kai Chu; Chun-Mei Huang; Hui-Jun Wang; Wei-Lin Tu; Gia-Luen Guo (Archives of Microbiology, 2022)

Genotyping and phenotyping of Lactococcus garvieae isolates from fish by pulse‐field gel electrophoresis (PFGE) and electron microscopy indicate geographical and capsular variations - Shreesha Rao; Mei‐Yun Chen; Chiranan Sudpraseart; Peiry Lin; Terutoyo Yoshida; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2022)
Lactococcus garvieae is the etiological agent of Lactococcosis, an evolving disease affecting many fish species and causing significant economic losses worldwide. Assessing pathogen relatedness and bacterial population structure is critical for determining the epidemiology of L. garvieae infections and in establishing effective pathogen management methods. The previously published morphological and genetic studies point to a clonal population structure, as seen in other fish bacteria. In the present study, the pulsed‐field gel electrophoresis (PFGE) method was utilized to define a population of 41 Taiwanese isolates from outbreaks with comparisons to four well‐characterized non‐Taiwanese isolates previously published. Two restriction enzymes ( Apa I and Sma I) were utilized individually for PFGE analysis (cut‐off value = 90.0%), revealing genetic heterogeneity across L. garvieae isolates, with Apa I and Sma I yielding 12 and seven distinct PFGE band patterns, respectively. The phylogenic analysis using internal transcribed spacer region clustered all L. garvieae isolates in the same clad. Furthermore, the electron microscopic results confirmed the absence of capsular gene cluster (CGC) in previously characterized Taiwanese vaccine strain (S3) from grey mullet. Overall, our findings emphasize the importance of analysing the morphological and genetic diversity in L. garvieae being correlated for proper taxonomic classification in vaccine strain selection and epidemiological studies.

In Vitro Assessment of Transporter Mediated Perpetrator DDIs for Several Hepatitis C Virus Direct-Acting Antiviral Drugs and Prediction of DDIs with Statins Using Static Models - Xiaoyan Chu; Grace Hoyee Chan; Robert Houle; Meihong Lin; Jocelyn Yabut; Christine Fandozzi (The AAPS Journal, 2022)

An extended Human Connectome Project multimodal parcellation atlas of the human cortex and subcortical areas - Chu-Chung Huang; Edmund T. Rolls; Jianfeng Feng; Ching-Po Lin (Brain Structure and Function, 2022)

Comprehensive identification of protein orthologs in the family Ascoviridae facilitates an understanding of phylogenomics, protein conservation, and phosphorylation - Yanhua Shi; Weiping Lin; Jinxin Chu; Guohui Wang; Punan Zhao; Guo-hua Huang; Dianhai Hou (Archives of Virology, 2022)

Consistency correction of echo intensity data for multiple radar systems and its application in quantitative estimation of typhoon precipitation - Shuai Zhang; Jing Han; Bingke Zhao; Zhigang Chu; Jie Tang; Limin Lin; Xiaoqin Lu; Jiaming Yan (Frontiers of Earth Science, 2022)

P75 neurotrophin receptor controls subventricular zone neural stem cell migration after stroke - Sachin S. Deshpande; Subash C. Malik; Pasquale Conforti; Jia-di Lin; Yu-Hsuan Chu; Suvra Nath; Franziska Greulich; Meike-Ast Dumbach; N. Henriette Uhlenhaut; Christian Schachtrup (Cell and Tissue Research, 2022)
Stroke is the leading cause of adult disability. Endogenous neural stem/progenitor cells (NSPCs) originating from the subventricular zone (SVZ) contribute to the brain repair process. However, molecular mechanisms underlying CNS disease-induced SVZ NSPC-redirected migration to the lesion area are poorly understood. Here, we show that genetic depletion of the p75 neurotrophin receptor ( p75 NTR−/− ) in mice reduced SVZ NSPC migration towards the lesion area after cortical injury and that p75 NTR−/− NSPCs failed to migrate upon BDNF stimulation in vitro. Cortical injury rapidly increased p75 NTR abundance in SVZ NSPCs via bone morphogenetic protein (BMP) receptor signaling. SVZ-derived p75 NTR−/− NSPCs revealed an altered cytoskeletal network- and small GTPase family-related gene and protein expression. In accordance, BMP-treated non-migrating p75 NTR−/− NSPCs revealed an altered morphology and α-tubulin expression compared to BMP-treated migrating wild-type NSPCs. We propose that BMP-induced p75 NTR abundance in NSPCs is a regulator of SVZ NSPC migration to the lesion area via regulation of the cytoskeleton following cortical injury.

Id proteins: emerging roles in CNS disease and targets for modifying neural stemcell behavior - Yu-Hsuan Chu; Jia-di Lin; Suvra Nath; Christian Schachtrup (Cell and Tissue Research, 2022)
Neural stem/progenitor cells (NSPCs) are found in the adult brain and spinal cord, and endogenous or transplanted NSPCs contribute to repair processes and regulate immune responses in the CNS. However, the molecular mechanisms of NSPC survival and integration as well as their fate determination and functionality are still poorly understood. Inhibitor of DNA binding (Id) proteins are increasingly recognized as key determinants of NSPC fate specification. Id proteins act by antagonizing the DNA-binding activity of basic helix-loop-helix (bHLH) transcription factors, and the balance of Id and bHLH proteins determines cell fate decisions in numerous cell types and developmental stages. Id proteins are central in responses to environmental changes, as they occur in CNS injury and disease, and cellular responses in adult NSPCs implicate Id proteins as prime candidates for manipulating stemcell behavior. Here, we outline recent advances in understanding Id protein pleiotropic functions in CNS diseases and propose an integrated view of Id proteins and their promise as potential targets in modifying stemcell behavior to ameliorate CNS disease.

Evaluation of using comparative intradermal tuberculin test to diagnose bovine tuberculosis in dairy cattle in Taiwan - Heng-Ching Lin; Chishih Chu; Yaochi Su; Jyh-Mirn Lai (Tropical Animal Health and Production, 2022)

Characteristics of typical air pollutants in a valley-basin city in South China - Chu Wu; Jibing Li; Xiaoping Lin; Yangzhi Mo; Hui Zhang; Zhihui Liao; Yu Wang; Duohong Chen (Meteorology and Atmospheric Physics, 2022)

Upregulation of h-TERT and Ki-67 in ectopic endometrium is associated with recurrence of endometriosis - Jie Luo; Zhimin Song; Tao Zhang; Ketan Chu; Jingyi Li; Jianhong Zhou; Jun Lin (Journal of Zhejiang University-SCIENCE B, 2022)

Editorial: Rhizosphere microbiome special issue - Yong-Guan Zhu; Xianyong Lin; Haiyan Chu (Plant and Soil, 2022)

Functional variants of RPS6KB1 and PIK3R1 in the autophagy pathway genes and risk of bladder cancer - Lan Ma; Dongjian Zhang; Zhengkai Huang; Rui Zheng; Mulong Du; Qiang Lv; Chao Qin; Haiyan Chu; Lin Yuan; Zhengdong Zhang (Archives of Toxicology, 2022)

Cryptic niche differentiation of novel sediment ecotypes of Ruegeria pomeroyi correlates with nitrate respiration - Xingqin Lin; Jesse McNichol; Xiao Chu; Yang Qian; Haiwei Luo (Environmental Microbiology, 2022)
Summary Marine intertidal sediments fluctuate in redox conditions and nutrient availability, and they are also known as an important sink of nitrogen mainly through denitrification, yet how denitrifying bacteria adapt to this dynamic habitat remains largely untapped. Here, we investigated novel intertidal benthic ecotypes of the model pelagic marine bacterium Ruegeria pomeroyi DSS‐3 with a population genomic approach. While differing by only 1.3% at the 16S rRNA gene level, members of the intertidal benthic ecotypes are complete denitrifiers whereas the pelagic ecotype representative (DSS‐3) is a partial denitrifier lacking a nitrate reductase. The intertidal benthic ecotypes are further differentiated by using non‐homologous nitrate reductases and a different set of genes that allow alleviating oxidative stress and acquiring organic substrates. In the presence of nitrate, the two ecotypes showed contrasting growth patterns under initial oxygen concentrations at 1 vol% versus 7 vol% and supplemented with different carbon sources abundant in intertidal sediments. Collectively, this combination of evidence indicates that there are cryptic niches in coastal intertidal sediments that support divergent evolution of denitrifying bacteria. This knowledge will in turn help understand how these benthic environments operate to effectively remove nitrogen.

Bioactive compounds derived from the marine-derived fungus MCCC3A00951 and their influenza neuraminidase inhibition activity in vitro and in silico - Shun-Zhi Liu; Feng-Ming He; Yan-lin Bin; Chu-Fang Li; Bao-Ying Xie; Xi-Xiang Tang; Ying-Kun Qiu (Natural Product Research, 2021)

Long-term changes of water acidity in an intact forested watershed in south China - Xiao-dong Liu; Ying-jie Feng; Qi-feng Mo; Guo-wei Chu; Yue-lin Li; Qian-mei Zhang; Wei-qiang Zhang; Xian-hua Gan; Qing Zhou (Journal of Mountain Science, 2021)

Antibiotic intervention redisposes bacterial interspecific interacting dynamics in competitive environments - Jing Li; Xiaojie Chen; Jiafu Lin; Yang Yuan; Ting Huang; Lianming Du; Balakrishnan Prithiviraj; Aixue Zhang; Xinrong Wang; Yiwen Chu; Kelei Zhao (Environmental Microbiology, 2021)
Summary Interspecific interaction happens frequently among bacterial species and can promote the colonization of polymicrobial community in various environments. However, it is not clear whether the intervention of antibiotics, which is a common therapeutic method for infectious disease, will influence the interacting dynamics of different pathogenic bacteria. By using the frequently co‐isolated bacteria Pseudomonas aeruginosa and Staphylococcus aureus as models, here we identify an antibiotic‐determined mutual invasion relationship between bacterial pathogens. We show that although P . aeruginosa has a significant intrinsic competitive advantage over S . aureus by producing the quorum‐sensing (QS)‐controlled anti‐staphylococcal molecules, methicillin‐resistant S . aureus (MRSA) can inhibit neighbouring P . aeruginosa in the presence of subinhibitory aminoglycoside antibiotics (e.g. streptomycin) to P . aeruginosa . Importantly, subinhibitory streptomycin decreases the expression of QS‐regulated genes in P . aeruginosa and thus relieves the survival stress of MRSA brought by P . aeruginosa . On the other side, the iron‐uptake systems and pathogenicity of MRSA can be enhanced by the extracellular products of streptomycin‐treated P . aeruginosa . Therefore, this study provides an explanation for the substitution of dominant species and persistent coexistence of bacterial pathogens in the host with repeated antibiotic therapies and contributes to further understanding the pathogenesis of chronic polymicrobial infections.

Jasmonic acid and hydrogen sulfide modulate transcriptional and enzymatic changes of plasma membrane NADPH oxidases (NOXs) and decrease oxidative damage in Oryza sativa L. during thiocyanate exposure - Xiao-Zhang Yu; Yun-Peng Chu; Hua Zhang; Yu-Juan Lin; Peng Tian (Ecotoxicology, 2021)

Extensional tectonics and North China Craton destruction: Insights from the magnetic susceptibility anisotropy (AMS) of granite and metamorphic core complex - Wei Lin; Jipei Zeng; Lingtong Meng; Huabiao Qiu; Wei Wei; Zhiheng Ren; Yang Chu; Shuangjian Li; Chao Song; Qincheng Wang (Science China Earth Sciences, 2021)

Production of purple Ma bamboo (Dendrocalamus latiflorus Munro) with enhanced drought and cold stress tolerance by engineering anthocyanin biosynthesis - Mengqi Xiang; WenSha Ding; Chu Wu; Wenjia Wang; Shanwen Ye; Changyang Cai; Xin Hu; Nannan Wang; Weiyuan Bai; Xiaoshan Tang; Caiping Zhu; Xiaomin Yu; et al. (Planta, 2021)

Evaluating a Modified High Purity Polysorbate 20 Designed to Reduce the Risk of Free Fatty Acid Particle Formation - Nidhi Doshi; Kyle Ritchie; Tamanna Shobha; Jamie Giddings; Kathrin Gregoritza; Rosalynn Taing; Stephen Rumbelow; Jeff Chu; Anthony Tomlinson; Aadithya Kannan; Miguel Saggu; Si Kai Cai; et al. (Pharmaceutical Research, 2021)

Identification of a major QTL related to resistance to soybean mosaic virus in diverse soybean genetic populations - Jiahao Chu; Wenlong Li; Dongri Piao; Feng Lin; Xiaobo Huo; Hua Zhang; Hui Du; Youbin Kong; Yuan Jin; Xihuan Li; Caiying Zhang (Euphytica, 2021)

Rapid transition from MORB-type to SSZ-type oceanic crust generation following subduction initiation: insights from the mafic dikes and metamorphic soles in the Pozantı-Karsantı ophiolite, SE Turkey - Guang-Yao Xin; Yang Chu; Ben-Xun Su; Wei Lin; Ibrahim Uysal; Zhen-Tian Feng (Contributions to Mineralogy and Petrology, 2021)

Assessment of climate change effects on alpine summit vegetation in the transition of tropical to subtropical humid climate - Chu-Chia Kuo; Yu Su; Ho-Yih Liu; Cheng-Tao Lin (Plant Ecology, 2021)

Whole brain volume and cortical thickness abnormalities in Wilson’s disease: a clinical correlation study - Yukun Song; Lin Zou; Jing Zhao; Xiangxue Zhou; Yingqian Huang; Haishan Qiu; Haiwei Han; Zhiyun Yang; Xunhua Li; Xiaoying Tang; Jianping Chu (Brain Imaging and Behavior, 2021)

Lesions of abdominal connectives reveal a conserved organization of the calling song central pattern generator (CPG) network in different cricket species - Chu-Cheng Lin; Berthold Hedwig (Journal of Comparative Physiology A, 2021)
Although crickets move their front wings for sound production, the abdominal ganglia house the network of the singing central pattern generator. We compared the effects of specific lesions to the connectives of the abdominal ganglion chain on calling song activity in four different species of crickets, generating very different pulse patterns in their calling songs. In all species, singing activity was abolished after the connectives between the metathoracic ganglion complex and the first abdominal ganglion A3 were severed. The song structure was lost and males generated only single sound pulses when connectives between A3 and A4 were cut. Severing connectives between A4 and A5 had no effect in the trilling species, it led to an extension of chirps in a chirping species and to a loss of the phrase structure in two Teleogryllus species. Cutting the connectives between A5 and A6 caused no or minor changes in singing activity. In spite of the species-specific pulse patterns of calling songs, our data indicate a conserved organisation of the calling song motor pattern generating network. The generation of pulses is controlled by ganglia A3 and A4 while A4 and A5 provide the timing information for the chirp and/or phrase structure of the song.

Above‐ and belowground biodiversity jointly drive ecosystem stability in natural alpine grasslands on the Tibetan Plateau - Litong Chen; Lin Jiang; Xin Jing; Jiuluan Wang; Yu Shi; Haiyan Chu; Jin‐Sheng He (Global Ecology and Biogeography, 2021)
Aim Most existing studies that examined the biotic mechanisms of ecosystem stability have focused on aboveground biodiversity. Whether and how belowground biodiversity affects the stability of natural ecosystems is largely unknown. In the present study, we investigated the relationships between above‐ and belowground biodiversity and the temporal stability of grassland biomass production across a large gradient of soil and climatic conditions. Location Tibetan Plateau. Time period 2001–2016. Major taxa studied Alpine grass and soil bacteria, arbuscular mycorrhiza (AM) fungi and fauna. Methods We coupled a field biodiversity survey conducted in 54 alpine grassland ecosystems across the Tibetan Plateau with a satellite‐sensed proxy (enhanced vegetation index, EVI) of ecosystem productivity during 2001–2016. The temporal stability of primary productivity was calculated as the ratio of the mean annual peak EVI to the standard deviation of the annual peak EVI over this period. Plant diversity was determined using a classic vegetation survey approach, soil bacterial and AM fungal diversity were measured using a high‐throughput sequencing approach, and soil fauna was counted and identified at the order level after being extracted using a modified Berlese–Tullgren method. Results Our results demonstrated that both above‐ and belowground biodiversity were positively associated with ecosystem stability. Belowground biodiversity not only affected ecosystem stability directly, but also influenced it indirectly through plant diversity and soil fertility. Furthermore, soil pH, climate and its variability strongly influenced soil biodiversity, which in turn influenced ecosystem stability. Main conclusions Our study demonstrates the indispensable role of belowground biodiversity in regulating ecosystem stability, emphasizing the necessity of conserving this ‘hidden’ biodiversity in fragile alpine ecosystems facing ongoing environmental change.

Secondary Structural Transformation of Bovine Lactoferricin Affects Its Antibacterial Activity - Jie Pei; Lin Xiong; Pengjia Bao; Min Chu; Ping Yan; Xian Guo (Probiotics and Antimicrobial Proteins, 2021)

Cracking behaviors and strength of rock-like samples with steps of different geometries under shear stress - Hui-lin Le; Ji-hong Wei; Shao-rui Sun; Chu-chu Zhang (Journal of Mountain Science, 2021)

A Comprehensive Assessment of All-Oleate Polysorbate 80: Free Fatty Acid Particle Formation, Interfacial Protection and Oxidative Degradation - Nidhi Doshi; Jamie Giddings; Lin Luis; Arthur Wu; Kyle Ritchie; Wenqiang Liu; Wayman Chan; Rosalynn Taing; Jeff Chu; Alavattam Sreedhara; Aadithya Kannan; Pervina Kei; et al. (Pharmaceutical Research, 2021)

A new three-dimensional computerized ionospheric tomography model based on a neural network - Dunyong Zheng; Yibin Yao; Wenfeng Nie; Nan Chu; Dongfang Lin; Minsi Ao (GPS Solutions, 2021)

Genetic variants in N6-methyladenosine are associated with bladder cancer risk in the Chinese population - Hanting Liu; Jingjing Gu; Yu Jin; Qi Yuan; Gaoxiang Ma; Mulong Du; Yuqiu Ge; Chao Qin; Qiang Lv; Guangbo Fu; Meilin Wang; Haiyan Chu; et al. (Archives of Toxicology, 2021)

Phthalates exposure and attention-deficit/hyperactivity disorder in children: a systematic review of epidemiological literature - Sarva Mangala Praveena; Rusheni Munisvaradass; Ruziana Masiran; Ranjith Kumar Rajendran; Chu-Ching Lin; Suresh Kumar (Environmental Science and Pollution Research, 2020)

MiRNAs-Modulation of Nrf2 Signaling Networks in Regulation Oxidative Stress of Chinese Perch Skeletal Muscle After Fasting Treatment - Ping Wu; Lin Chen; Jia Cheng; Yaxiong Pan; Xinhong Guo; Wuying Chu; Jianshe Zhang; Xuanming Liu (Marine Biotechnology, 2020)

Nutrient factor-dependent performance of bacterial quorum sensing system during population evolution - Kelei Zhao; Jing Li; Yang Yuan; Jiafu Lin; Xinrong Wang; Yidong Guo; Yiwen Chu (Archives of Microbiology, 2020)

Dynamic Stability of an Ocean Current Turbine System - Shueei-Muh Lin; Yang-Yih Chen; Hung-Chu Hsu; Meng-Syue Li (Journal of Marine Science and Engineering, 2020)
This paper presents a theoretical solution for the dynamic stability of the ocean current turbine system developed in Taiwan. This system is tethered to the sea floor and uses the Kuroshio Current to produce electricity. To maintain the performance of the turbine system in the presence of the Kuroshio Current, the stability of the surfaced turbine needs to be considered. The proposed system is composed of a turbine, a buoyance platform, a traction rope, and a mooring foundation. The two-dimensional theoretical solutions treat the turbine as a rigid body with a movable structure that is moored with two cables. In this model, the gravity, buoyancy, and drag force generated by the wave on the turbine structure are considered. In addition, an analytical solution is proposed for the general system. Finally, the effects of the wave on the pitch motion and dynamical stability of the ocean current turbine system are investigated.

Stem-Cell Therapy as a Potential Strategy for Radiation-Induced Brain Injury - Chengyan Chu; Yue Gao; Xiaoyan Lan; Jianwen Lin; Aline M. Thomas; Shen Li (Stem Cell Reviews and Reports, 2020)

Fabrication and Characterization of an Aptamer-Based N-type Silicon Nanowire FET Biosensor for VEGF Detection - Serge Ismael Zida; Chu-Chun Yang; Yit Lung Khung; Yue-Der Lin (Journal of Medical and Biological Engineering, 2020)

Astrocytic GABAB Receptors in Mouse Hippocampus Control Responses to Behavioral Challenges through Astrocytic BDNF - Ji-Hong Liu; Ze-Lin Li; Yi-Si Liu; Huai-De Chu; Neng-Yuan Hu; Ding-Yu Wu; Lang Huang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2020)

Statistical Analysis on Heart Rate Variability for Graded Cardiopulmonary Groups with Different Exercise Intensities - Ching-Kun Chen; Shyan-Lung Lin; Cheng-Yi Huang; Tasi-Chu Wang; Ting-Yen Yao; Chieh-Liang Wu (Journal of Medical and Biological Engineering, 2020)

Nr1d1 affects autophagy in the skeletal muscles of juvenile Nile tilapia by regulating the rhythmic expression of autophagy-related genes - Ping Wu; Jia Cheng; Lin Chen; Jing Xiang; Yaxiong Pan; Yongzhan Zhang; Tao Zheng; Naiyuan Liu; Wuying Chu; Jianshe Zhang (Fish Physiology and Biochemistry, 2020)

Spectral and spatial kernel water quality mapping - Hone-Jay Chu; Lalu Muhamad Jaelani; Manh Van Nguyen; Chao-Hung Lin; Ariel C. Blanco (Environmental Monitoring and Assessment, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Soil plant-available phosphorus levels and maize genotypes determine the phosphorus acquisition efficiency and contribution of mycorrhizal pathway - Qun Chu; Lin Zhang; Jianwei Zhou; Lixing Yuan; Fanjun Chen; Fusuo Zhang; Gu Feng; Zed Rengel (Plant and Soil, 2020)

The roles of moisture transports in intraseasonal precipitation during the preflood season over South China - Qu‐cheng Chu; Qi‐guang Wang; Guo‐lin Feng (International Journal of Climatology, 2020)
The roles of moisture sources and transport in intraseasonal precipitation variabilities during the preflood season over South China are complex and different. In this paper, ERA‐Interim reanalysis data that were collected four times daily from 1979 to 2017 are used to analyse the variation and influence of moisture transport in intraseasonal precipitation during the preflood season over South China. Using the Hybrid Single‐Particle Lagrangian Integrated Trajectory model, fixed atmospheric moisture sources are defined: land area source (LD source), Indian Ocean source (IO source), Pacific Ocean source (PO source), South China Sea source (SCS source), and South China source (SC source). Sea source moisture transport accounts for more than 75% of the total precipitation during the preflood season, which is the most important moisture source in South China. For April, southeasterly moisture transport, which includes PO source and SCS source moisture transports, is the major moisture transport over South China. Then, the IO source and SCS source precipitation increased significantly during May. During June, the IO source precipitation accounted for 43.75% of the total precipitation, thus dominating precipitation over South China. In addition, there is a significant difference in the interdecadal variation in the preflood season precipitation before and after the Indian summer monsoon onset. Before the Indian summer monsoon onset, the land‐sea thermal contrast decreased, which led to a significant interdecadal reduction in the IO source, PO source, and SCS source moisture transports. After the Indian summer monsoon onset, the increase in IO source moisture transport is the primary cause of the interdecadal increase in precipitation over South China.

Effects of Starvation on Antioxidant-Related Signaling Molecules, Oxidative Stress, and Autophagy in Juvenile Chinese Perch Skeletal Muscle - Ping Wu; Aimin Wang; Jia Cheng; Lin Chen; Yaxiong Pan; Honghui Li; Qi Zhang; Jiaqi Zhang; Wuying Chu; Jianshe Zhang (Marine Biotechnology, 2020)

Methamphetamine-Induced Cognitive Deficits and Psychiatric Symptoms Are Associated with Serum Markers of Liver Damage - Tingting Zhao; Changping Zhai; Hongmei Song; Yanhai Wu; Chuanhui Ge; Yonglin Zhang; Hongxia Xu; Zhengsuo Chi; Hui Chu; Wei Shi; Xiaodong Cheng; Xin Li; et al. (Neurotoxicity Research, 2020)

The m6A methyltransferase METTL3 cooperates with demethylase ALKBH5 to regulate osteogenic differentiation through NF-κB signaling - Jinjin Yu; Lujun Shen; Yanli Liu; Hong Ming; Xinxing Zhu; Maoping Chu; Juntang Lin (Molecular and Cellular Biochemistry, 2020)

Using 1-propanol to significantly enhance the production of valuable odd-chain fatty acids by Rhodococcus opacus PD630 - Lin-Shang Zhang; Pei Xu; Mei-Yun Chu; Min-Hua Zong; Ji-Guo Yang; Wen-Yong Lou (World Journal of Microbiology and Biotechnology, 2019)

Roles of moisture sources and transport in precipitation variabilities during boreal summer over East China - Qu-cheng Chu; Rong Zhi; Qi-guang Wang; Guo-lin Feng (Climate Dynamics, 2019)

Plants alter their vertical root distribution rather than biomass allocation in response to changing precipitation - Bingwei Zhang; Marc W. Cadotte; Shiping Chen; Xingru Tan; Cuihai You; Tingting Ren; Minling Chen; Shanshan Wang; Weijing Li; Chengjin Chu; Lin Jiang; Yongfei Bai; et al. (Ecology, 2019)
Elucidating the variation of allocation pattern of ecosystem net primary productivity ( NPP ) and its underlying mechanisms is critically important for understanding the changes of aboveground and belowground ecosystem functions. Under optimal partitioning theory, plants should allocate more NPP to the organ that acquires the most limiting resource, and this expectation has been widely used to explain and predict NPP allocation under changing precipitation. However, confirmatory evidence for this theory has mostly come from observed spatial variation in the relationship between precipitation and NPP allocation across ecosystems, rather than directly from the influences of changing precipitation on NPP allocation within systems. We performed a 6‐yr five‐level precipitation manipulation experiment in a semiarid steppe to test whether changes in NPP allocation can be explained by the optimal partitioning theory, and how water requirement of plant community is maintained if NPP allocation is unaltered. The 30 precipitation levels (5 levels × 6 yr) were divided into dry, nominal, and wet precipitation ranges, relative to historical precipitation variation over the past six decades. We found that NPP in both aboveground ( ANPP ) and belowground ( BNPP ) increased nonlinearly as precipitation increased, while the allocation of NPP to BNPP ( f BNPP ) showed a concave quadratic relationship with precipitation. The declined f BNPP as precipitation increased in the dry range supported the optimal partitioning theory. However, in the nominal range, NPP allocation was not influenced by the changed precipitation; instead, BNPP was distributed more in the surface soil horizon (0–10 cm) as precipitation increased, and conversely more in the deeper soil layers (10–30 cm) as precipitation decreased. This response in root foraging appears to be a strategy to satisfy plant water requirements and partially explains the stable NPP allocation patterns. Overall, our results suggest that plants can adjust their vertical BNPP distribution in response to drought stress, and that only under extreme drought does the optimal partitioning theory strictly apply, highlighting the context dependency of the adaption and growth of plants under changing precipitation.

Immunological microenvironment alterations in follicles of women with proven severe endometriosis undergoing in vitro fertilization - Xiao-Dan Mao; Chen-Yu Hu; Meng-Chu Zhu; Hui-Lin Ou; Yu-Li Qian (Molecular Biology Reports, 2019)

Endoscopic ultrasonography is useful in the diagnosis and treatment of rectal neuroendocrine neoplasms: a case series - Qing Gu; Yi-ming Lin; Li Cen; Min Xu; Hong-zhang Li; Xian-chu Lin; Chao Lu (Journal of Zhejiang University-SCIENCE B, 2019)

Warming changes soil N and P supplies in model tropical forests - Zhiyang Lie; Wei Lin; Wenjuan Huang; Xiong Fang; Chumin Huang; Ting Wu; Guowei Chu; Shizhong Liu; Ze Meng; Guoyi Zhou; Juxiu Liu (Biology and Fertility of Soils, 2019)

Rapamycin Removes Damaged Mitochondria and Protects Human Trabecular Meshwork (TM-1) Cells from Chronic Oxidative Stress - Jing Na He; Shao Dan Zhang; Yang Qu; Hai Lin Wang; Clement C. Tham; Chi Pui Pang; Wai Kit Chu (Molecular Neurobiology, 2019)

3D-QSAR, molecular docking, and new compound design of pyrimidine derivatives as Src small molecule inhibitors - Jun-wei Wang; Ya-ting Deng; Han Chu; Juan Wang; Yong Hu; Zhi-hua Lin (Medicinal Chemistry Research, 2019)

Replication and Meta-analysis of the Association between BDNF Val66Met Polymorphism and Cognitive Impairment in Patients Receiving Chemotherapy - Chia Jie Tan; Sheree Wan Ting Lim; Yi Long Toh; Terence Ng; Angie Yeo; Maung Shwe; Koon Mian Foo; Pat Chu; Amit Jain; Si-Lin Koo; Rebecca A. Dent; Raymond Chee Hui Ng; et al. (Molecular Neurobiology, 2019)

Blood and seminal plasma mercury levels and predatory fish intake in relation to low semen quality - Chin-En Ai; Ching-Jen Li; Ming-Chien Tsou; Jun-Lin Chen; Hsing-Cheng Hsi; Ling-Chu Chien (Environmental Science and Pollution Research, 2019)

Distribution of mercury and methylmercury in surface water and surface sediment of river, irrigation canal, reservoir, and wetland in Taiwan - Ying-Lin Wang; Meng-Der Fang; Ling-Chu Chien; Chu-Ching Lin; Hsing-Cheng Hsi (Environmental Science and Pollution Research, 2019)

Spatial variation and soil nitrogen potential hotspots in a mixed land cover catchment on the Chinese Loess Plateau - Yun-long Yu; Zhao Jin; Henry Lin; Yun-qiang Wang; Ya-li Zhao; Guang-chen Chu; Jing Zhang; Yi Song; Han Zheng (Journal of Mountain Science, 2019)

Chimeric antigen receptor engineered innate immune cells in cancer immunotherapy - Chu Lin; Jun Zhang (Science China Life Sciences, 2019)

Interleukin-26 upregulates interleukin-22 production by human CD4+ T cells in tuberculous pleurisy - Min Zhang; Yi-Ran Niu; Jing-Yuan Liu; Xiao-Shan Wei; Xiao-Rong Wang; Lin-Lin Ye; Wen-Bei Peng; Jian-Chu Zhang; Xiao-Nan Tao; Qiong Zhou (Journal of Molecular Medicine, 2019)

Polymer translocation through a hairy channel mimicking the inner plug of a nuclear pore complex - Chibin Zhang; Zhiwei Cheng; Xiaohui Lin; Wenquan Chu (European Biophysics Journal, 2019)

Difference of trace element exposed routes and their health risks between agriculture and pastoral areas in Bay County Xinjiang, China - Muyesaier Tudi; Dung Tri Phung; Huada Daniel Ruan; Lin-sheng Yang; Hai-Jun Guo; Des Connell; Ross Sadler; Cordia Chu (Environmental Science and Pollution Research, 2019)

Cover Image - Theeraporn Pulpipat; Kuo‐Hua Lin; Ying‐Hao Chen; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2019)

Molecular characterization and pathogenicity of Francisella noatunensis subsp. orientalis isolated from cultured tilapia ( Oreochromis sp.) in Taiwan - Theeraporn Pulpipat; Kuo‐Hua Lin; Ying‐Hao Chen; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2019)
Francisella noatunensis subsp. orientalis is a causative agent of systemic granulomatous disease in tilapia. The present study was designed to understand the genetic and phenotypic diversities among Taiwanese Fno isolates obtained from tilapia ( n = 17) and green Texas cichlid ( Herichthys cyanoguttatus ) ( n = 1). The enzymatic profiles of the isolates were studied using the API ZYM system. Phylogenetic tree analysis of the 16S rRNA and housekeeping gene and pulsed‐field gel electrophoresis (PFGE) were carried out to determine the genotypic characters of all isolates. The phylogenetic tree showed similarity of 99%–100% nucleotide sequences of 16S rRNA and housekeeping genes compared to the Fno references genes from GenBank database. Comparatively, the results revealed an identical profile of enzymatic and PFGE pattern which was distincted from that of F. philomiragia . To understand the pathogenicity, the isolates were intraperitoneal injected to tilapia the gross lesions were observed concomitant with natural outbreak. Median lethal dose upon Nile tilapia and red tilapia were 9.06 × 10 3 CFU/fish and 2.08 × 10 2 CFU/fish, respectively. Thus, our data provide understanding the epidemiology of Taiwanese Fno isolates, and help in development of future control and prevention.

Gene structure, recombinant expression and function characterization of Siniperca chuatsi Fsrp‐3 - Jianhua Wang; Jia Cheng; Yulong Li; Huiling Yan; Ping Wu; Xin Zhu; Li Liu; Lin Chen; Wuying Chu; Jianshe Zhang (Journal of Fish Biology, 2019)
A full‐length complementary (c)DNA sequence encoding follistatin‐related protein 3 ( fsrp‐3 ) was determined from skeletal muscle in Chinese mandarin fish Siniperca chuatsi , its molecular structure was characterised and its function suggested. The putative structure of S. chuatsi Fsrp‐3 contains an N‐terminal domain and two follistatin domains. Quantitative reverse‐transcription (qRT)‐PCR assays revealed that fsrp‐3 messenger (m)RNA was differentially expressed among assayed tissues and was highly expressed in heart and intestine. fsrp‐3 mRNA exhibited increasing expression from the larval to the juvenile stage (500 g). To investigate the potential function of S. chuatsi fsrp‐3 in muscle growth, we constructed a Fsrp‐3 prokaryotic expression system and injected the purified Fsrp‐3 fusion protein into the dorsal muscle. Fsrp‐3 administration significantly influenced cross‐section area, satellite cell activation frequency and nuclear density of S. chuatsi muscle fibres. Following Fsrp‐3 treatment, the expression of myogenic regulatory factors was up‐regulated and decline in the expression of myostatin was observed. The study revealed that Fsrp‐3 may affect muscle growth by regulating myogenic regulatory factor expression and antagonizing myostatin function to initiate satellite cell activation and differentiation in S. chuatsi .

Historical demography of four gecko species specializing in boulder cave habitat: Implications in the evolutionary dead end hypothesis and conservation - Hung N. Nguyen; Chia‐Wei Lu; Jui‐Hua Chu; Larry Lee Grismer; Chih‐Ming Hung; Si‐Min Lin (Molecular Ecology, 2019)
Specialization in narrow ecological niches may not only help species to survive in competitive or unique environments but also contribute to their extermination over evolutionary time. Although the “evolutionary dead end” hypothesis has long been debated, empirical evidence from species with detailed information on niche specialization and evolutionary history remains rare. Here we use a group of four closely related Cnemaspis gecko species that depend highly on granite boulder caves in the Mekong Delta to investigate the potential impact of ecological specialization on their evolution and population dynamics. Isolated by unsuitable floodplain habitats, these boulder‐dwelling geckos are among the most narrowly distributed Squamata in the world. We applied several coalescence‐based approaches combined with the RAD‐seq technique to estimate their divergence times, gene flow and demographic fluctuations during the speciation and population differentiation processes. Our results reveal long‐term population shrinkage in the four geckos and limited gene flow during their divergence. The results suggest that the erosion and fragmentation of the granite boulder hills have greatly impacted population divergence and declines. The habitat specialization of these geckos has led to fine‐scaled speciation in these granite rocky hills; in contrast, specialization might also have pushed these species toward the edge of extinction. Our study also emphasizes the conservation urgency of these vulnerable, cave‐dependent geckos.

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Microsatellites development and cross-amplification for Aquilaria sinensis, an endangered agarwood-producing tree - Zheng-Feng Wang; Hong-Lin Cao; Chu-Xiong Cai; Yun Guo; Zhang-Ming Wang (Journal of Genetics, 2018)

The complete mitochondrial genome of Shigaste humped cattle (Bos taurus) - Xian Guo; Jie Pei; Lin Xiong; Pengjia Bao; Yanbin Zhu; Basang Wangdui; Xiaoyun Wu; Min Chu; Ping Yan; Xuezhi Ding (Conservation Genetics Resources, 2018)

Acute effect of fine and coarse particular matter on cardiovascular visits in Ningbo, China - Pei-wen Zheng; Peng Shen; Zhen-hua Ye; Zhen-yu Zhang; Peng-fei Chai; Die Li; Ming-juan Jin; Meng-Ling Tang; Huai-chu Lu; Hong-bo Lin; Jian-bing Wang; Kun Chen (Environmental Science and Pollution Research, 2018)

Natural and synthetic flavonoids, novel blockers of the volume-regulated anion channels, inhibit endothelial cell proliferation - Yucong Xue; Honglin Li; Yuanyuan Zhang; Xue Han; Gaohua Zhang; Wenya Li; Huiran Zhang; Yue Lin; Pingping Chen; Xiaorun Sun; Yalei Liu; Li Chu; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

A long-term tropical mesoscale convective systems dataset based on a novel objective automatic tracking algorithm - Xiaomeng Huang; Chenqi Hu; Xing Huang; Yang Chu; Yu-heng Tseng; Guang Jun Zhang; Yanluan Lin (Climate Dynamics, 2018)

Activating adenosine A1 receptor accelerates PC12 cell injury via ADORA1/PKC/KATP pathway after intermittent hypoxia exposure - Hong-Fang Mei; Neha Poonit; Yi-Chun Zhang; Chu-Yuan Ye; Hui-Lin Cai; Chen-Yi Yu; Yong-Hai Zhou; Bei-bei Wu; Jun Cai; Xiao-Hong Cai (Molecular and Cellular Biochemistry, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Association between short-term exposure to ambient air pollution and daily mortality: a time-series study in Eastern China - Die Li; Jian-bing Wang; Zhen-yu Zhang; Peng Shen; Pei-wen Zheng; Ming-juan Jin; Huai-chu Lu; Hong-bo Lin; Kun Chen (Environmental Science and Pollution Research, 2018)

Recent updates on phthalate exposure and human health: a special focus on liver toxicity and stem cell regeneration - Sarva Mangala Praveena; Seoh Wei Teh; Ranjith Kumar Rajendran; Narayanan Kannan; Chu-Ching Lin; Rozaini Abdullah; Suresh Kumar (Environmental Science and Pollution Research, 2018)

Effects of air pollution on hospital visits for pneumonia in children: a two-year analysis from China - Die Li; Jian-bing Wang; Zhen-yu Zhang; Peng Shen; Pei-wen Zheng; Ming-juan Jin; Huai-chu Lu; Hong-bo Lin; Kun Chen (Environmental Science and Pollution Research, 2018)

Using marker gene analysis instead of mixed lymphocyte reaction assay for identification of functional CD4+FOXP3+ regulatory T cells - Sin-Tak Chu; Kuo-Hsuan Chien; Hsiu-Hsia Lin; Wei-Hao Wu; Jhih-Yun Jian; Woan-Fang Tzeng; Tzeon-Jye Chiou (Biotechnology Letters, 2018)

Effect of the dark septate endophytic fungus Acrocalymma vagum on heavy metal content in tobacco leaves - Hui-Qing Jin; Hua-Bing Liu; Ying-Ying Xie; Yong-Gang Zhang; Qing-Quan Xu; Li-Juan Mao; Xin-Jun Li; Jin Chen; Fu-Cheng Lin; Chu-Long Zhang (Symbiosis, 2018)

Feature analysis and primary causes of pre-flood season “cumulative effect” of torrential rain over South China - Qu-cheng Chu; Qi-guang Wang; Shao-bo Qiao; Guo-lin Feng (Theoretical and Applied Climatology, 2018)

Gender-Related Hippocampal Proteomics Study from Young Rats After Chronic Unpredicted Mild Stress Exposure - Lin-Na Ning; Teng Zhang; Jiang Chu; Na Qu; Li Lin; Ying-Yan Fang; Yan Shi; Peng Zeng; Er-Li Cai; Xiao-Ming Wang; Qun Wang; You-Ming Lu; et al. (Molecular Neurobiology, 2018)

Evaluation of toxicity of Deepwater Horizon slick oil on spat of the oyster Crassostrea virginica - Julien Vignier; Anne Rolton; Philippe Soudant; Fu-lin E. Chu; René Robert; Aswani K. Volety (Environmental Science and Pollution Research, 2018)

Erratum to: Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2017)

Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2017)

Effects of genetic variants of the bovine WNT8A gene on nine important growth traits in beef cattle - Yong-Zhen Huang; Yong Zou; Qing Lin; Hua He; Li Zheng; Zi-Jing Zhang; Yong-Long Dang; Chu-Zhao Lei; Xian-Yong Lan; Xing-Shan Qi; Hong Chen (Journal of Genetics, 2017)

Air pollution and hospital visits for acute upper and lower respiratory infections among children in Ningbo, China: A time-series analysis - Pei-wen Zheng; Jian-bing Wang; Zhen-yu Zhang; Peng Shen; Peng-fei Chai; Die Li; Ming-juan Jin; Meng-Ling Tang; Huai-chu Lu; Hong-bo Lin; Kun Chen (Environmental Science and Pollution Research, 2017)

Groundwater origins and recharge in a well field near Chien-Shih, Shinchu, Taiwan - Pei-Ying Lin; Louis Loung-Yie Tsai; Chung-Ho Wang; Kuei-Wen Chang; Yu-Yen Sheng; I-Tzu Chu; Wang-Ru Lee (Sustainable Water Resources Management, 2017)

EGCG protects against homocysteine-induced human umbilical vein endothelial cells apoptosis by modulating mitochondrial-dependent apoptotic signaling and PI3K/Akt/eNOS signaling pathways - Shumin Liu; Zhengwu Sun; Peng Chu; Hailong Li; Anil Ahsan; Ziru Zhou; Zonghui Zhang; Bin Sun; Jingjun Wu; Yalin Xi; Guozhu Han; Yuan Lin; et al. (Apoptosis, 2017)

Important Roles of Ring Finger Protein 112 in Embryonic Vascular Development and Brain Functions - Jen-Hui Tsou; Ying-Chen Yang; Ping-Chieh Pao; Hui-Ching Lin; Nai-Kuei Huang; Shih-Ting Lin; Kuei-Sen Hsu; Che-Ming Yeh; Kuen-Haur Lee; Chu-Jen Kuo; De-Ming Yang; Jiann-Her Lin; et al. (Molecular Neurobiology, 2017)

Quinone/hydroquinone meroterpenoids with antitubercular and cytotoxic activities produced by the sponge-derived fungus Gliomastix sp. ZSDS1-F7 - Wei-Jun He; Xiao-Jiang Zhou; Xiao-Chu Qin; Yong-Xin Mai; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Tianyu Zhang; Zheng-Chao Tu; Jun-Feng Wang; Yonghong Liu (Natural Product Research, 2017)

Development of a fluorescence resonance energy transfer–based intracellular assay to identify novel enterovirus 71 antivirals - Wen-Wen Lu; Fang-Yen Kung; Po-An Deng; Yu-Chu Lin; Cheng-Wen Lin; Szu-Hao Kung (Archives of Virology, 2017)

Characterization and evaluation of Bacillus amyloliquefaciens strain WF02 regarding its biocontrol activities and genetic responses against bacterial wilt in two different resistant tomato cultivars - Chu-Ning Huang; Chan-Pin Lin; Feng-Chia Hsieh; Sook-Kuan Lee; Kuan-Chen Cheng; Chi-Te Liu (World Journal of Microbiology and Biotechnology, 2016)

A WD40 protein, AtGHS40, negatively modulates abscisic acid degrading and signaling genes during seedling growth under high glucose conditions - Yu-Chun Hsiao; Yi-Feng Hsu; Yun-Chu Chen; Yi-Lin Chang; Co-Shine Wang (Journal of Plant Research, 2016)

An n-alkane and carbon isotope record during the last deglaciation from annually laminated sediment in Lake Xiaolongwan, northeastern China - Qing Sun; Manman Xie; Yuan Lin; Yabing Shan; Qingzeng Zhu; Deke Xu; Youliang Su; Patrick Rioual; Guoqiang Chu (Journal of Paleolimnology, 2016)

Recent research progress and prospects in tourism geography of China - Lin Lu; Jie Bao; Jianfeng Huang; Qijing Zhu; Chenglin Mu; Xiaole Chu; Yan Xu; Xiaoli Zha (Journal of Geographical Sciences, 2016)

The Effect on Sodium/Iodide Symporter and Pendrin in Thyroid Colloid Retention Developed by Excess Iodide Intake - Xiao-yi Chen; Chu-hui Lin; Li-hua Yang; Wang-gen Li; Jin-wei Zhang; Wen-wei Zheng; Xiang Wang; Jiang Qian; Jia-luan Huang; Yi-xiong Lei (Biological Trace Element Research, 2016)

Aeromicrobium halotolerans sp. nov., isolated from desert soil sample - Zheng-Fei Yan; Pei Lin; Xiao Chu; MooChang Kook; Chang-Tian Li; Tae-Hoo Yi (Archives of Microbiology, 2016)

Estimation of winter wheat phenology under the influence of cumulative temperature and soil salinity in the Yellow River Delta, China, using MODIS time-series data - Lin Chu; Chong Huang; Qing-sheng Liu; Gao-huan Liu (International Journal of Remote Sensing, 2016)

Diversity of phototrophic phytoplankton in Northern South China Sea indicated by rbcL analysis - Nan Li; Shu-Xian Yu; Yin-Chu Wang; Jia-Lin Li; Fu-Chao Li; Song Qin (Journal of Applied Phycology, 2016)

Increased night duty loading of physicians caused elevated blood pressure and sympathetic tones in a dose-dependent manner - Hsiu-Hao Lee; Shih-Hsiang Lo; Bing-Yu Chen; Yen-Hung Lin; Dachen Chu; Tsun-Jen Cheng; Pau-Chung Chen; Yue-Liang Guo (International Archives of Occupational and Environmental Health, 2016)

Erratum to: Phosphocreatine protects against LPS-induced human umbilical vein endothelial cell apoptosis by regulating mitochondrial oxidative phosphorylation - Zhengwu Sun; Xiaoyan Lan; Anil Ahsan; Yalin Xi; Shumin Liu; Zonghui Zhang; Peng Chu; Yushu Song; Fengyuan Piao; Jinyong Peng; Yuan Lin; Guozhu Han; et al. (Apoptosis, 2016)

SIL1 Rescued Bip Elevation-Related Tau Hyperphosphorylation in ER Stress - Zan-Chao Liu; Jiang Chu; Li Lin; Jie Song; Lin-Na Ning; Hong-Bin Luo; Shu-Sheng Yang; Yan Shi; Qun Wang; Na Qu; Qi Zhang; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2016)

One-step RT-LAMP analysis for efficient detection of Odontoglossum ringspot virus from Oncidiinae hybrids (Orchidaceae) - Chi-Chu Tsai; Chun-Yen Huang; I-Szu Weng; Wen-Lin Liu; Chang-Hung Chou (Journal of General Plant Pathology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Phosphocreatine protects against LPS-induced human umbilical vein endothelial cell apoptosis by regulating mitochondrial oxidative phosphorylation - Zhengwu Sun; Xiaoyan Lan; Anil Ahsan; Yalin Xi; Shumin Liu; Zonghui Zhang; Peng Chu; Yushu Song; Fengyuan Piao; Jinyong Peng; Yuan Lin; Guozhu Han; et al. (Apoptosis, 2016)

Six new metabolites produced by Colletotrichum aotearoa 09F0161, an endophytic fungus isolated from Bredia oldhamii - Yi Hsiao; Ming-Jen Cheng; Hsun-Shuo Chang; Ming-Der Wu; Sung-Yuan Hsieh; Ta-Wei Liu; Chu-Hung Lin; Gwo-Fang Yuan; Ih-Sheng Chen (Natural Product Research, 2016)

Clinical Pedicle Screw Insertion Trials and System Improvement of C-arm Image Navigation System - Chih-Ju Chang; Ching-Hsiao Yu; Geng-Li Lin; Alex Tse; Hong-Yu Chu; Ching-Shiow Tseng (Journal of Medical and Biological Engineering, 2016)

Biohydrogen production by dark fermentation: scaling-up and technologies integration for a sustainable system - Estela Tapia-Venegas; Juan Esteban Ramirez-Morales; Fernando Silva-Illanes; Javiera Toledo-Alarcón; Florian Paillet; Renaud Escudie; Chyi-How Lay; Chen-Yeon Chu; Hoang-Jyh Leu; Antonella Marone; Chiu-Yue Lin; Dong-Hoon Kim; et al. (Reviews in Environmental Science and Bio/Technology, 2015)

SZC017, a novel oleanolic acid derivative, induces apoptosis and autophagy in human breast cancer cells - Lei Gao; Yan Wang; Zhen Xu; Xiaorui Li; Jingjun Wu; Shumin Liu; Peng Chu; Zhengwu Sun; Bin Sun; Yuan Lin; Jinyong Peng; Guozhu Han; et al. (Apoptosis, 2015)

Phosphocreatine protects endothelial cells from oxidized low-density lipoprotein-induced apoptosis by modulating the PI3K/Akt/eNOS pathway - Anil Ahsan; Guozhu Han; Junfang Pan; Shumin Liu; Arshad Ahmed Padhiar; Peng Chu; Zhengwu Sun; Zonghui Zhang; Bin Sun; Jingjun Wu; Aisha Irshad; Yuan Lin; et al. (Apoptosis, 2015)

Erratum to: The collective nuclear migration of p53 and phosphorylated S473 of Akt during ellipticine-mediated apoptosis in human lung epithelial cancer cells - Jing-Ping Wang; Ya-Chu Yu; Shih-Ping Chen; Huan-Chang Liang; Chia-Wei Lin; Kang Fang (Molecular and Cellular Biochemistry, 2015)

Fully automatic and nonparametric quantification of adipose tissue in fat–water separation MR imaging - Defeng Wang; Lin Shi; Winnie C. W. Chu; Miao Hu; Brian Tomlinson; Wen-Hua Huang; Tianfu Wang; Pheng Ann Heng; David K. W. Yeung; Anil T. Ahuja (Medical & Biological Engineering & Computing, 2015)

Increased cardiac remodeling in cardiac-specific Flt-1 receptor knockout mice with pressure overload - Liqin Mei; Yinqing Huang; Jiafeng Lin; Maoping Chu; Chaohui Hu; Ning Zhou; Lianpin Wu (Cell and Tissue Research, 2015)

The collective nuclear migration of p53 and phosphorylated S473 of Akt during ellipticine-mediated apoptosis in human lung epithelial cancer cells - Jing-Ping Wang; Ya-Chu Yu; Shih-Ping Chen; Huan-Chang Liang; Chia-Wei Lin; Kang Fang (Molecular and Cellular Biochemistry, 2015)

Invasion biology of spotted wing Drosophila (Drosophila suzukii): a global perspective and future priorities - Mark K. Asplen; Gianfranco Anfora; Antonio Biondi; Deuk-Soo Choi; Dong Chu; Kent M. Daane; Patricia Gibert; Andrew P. Gutierrez; Kim A. Hoelmer; William D. Hutchison; Rufus Isaacs; Zhi-Lin Jiang; et al. (Journal of Pest Science, 2015)

Genetic variants of retinol-binding protein 4 in adolescents are associated with liver function and inflammatory markers but not with obesity and insulin resistance - CHIN-JUNG LIN; NAIN-FENG CHU; YI-JEN HUNG; DEE PEI; CHIEN-HSING LEE; FONE-CHING HSIAO; CHIEH-HUA LU; CHANG-HSUN HSIEH (Journal of Genetics, 2015)

Vascular smooth muscle cell differentiation to an osteogenic phenotype involves matrix metalloproteinase-2 modulation by homocysteine - Tingjiao Liu; Jinghan Lin; Ting Ju; Lei Chu; Liming Zhang (Molecular and Cellular Biochemistry, 2015)

Nitrogen and phosphorus loss and optimal drainage time of paddy field under controlled drainage condition - Meng-hua Xiao; Shuang-en Yu; Dongli She; Xiu-jun Hu; Lin-lin Chu (Arabian Journal of Geosciences, 2015)

Interaction of DRD2TaqI, COMT, and ALDH2 genes associated with bipolar II disorder comorbid with anxiety disorders in Han Chinese in Taiwan - Ming-Chuan Hu; Sheng-Yu Lee; Tzu-Yun Wang; Yun-Hsuan Chang; Shiou-Lan Chen; Shih-Heng Chen; Chun-Hsien Chu; Chen-Lin Wang; I Hui Lee; Po See Chen; Yen Kuang Yang; Ru-Band Lu (Metabolic Brain Disease, 2015)

A new design method for extracorporeal high-intensity focused ultrasound annular array - Gin-Shin Chen; Yu-Cheng Lin; Chu-Chiang Chen (Medical & Biological Engineering & Computing, 2015)

Sassarandainol: a new neolignan and anti-inflammatory constituents from the stem of Sassafras randaiense - Ya-Ling Hou; Hsun-Shuo Chang; Hui-Chun Wang; Sheng-Yang Wang; Tze-Ying Chen; Chu-Hung Lin; Ih-Sheng Chen (Natural Product Research, 2015)

High seroprevalence of human herpesvirus type 8 infection in males with advanced lung carcinoma - Cheng-Chuan Su; Chun-Liang Lai; Shih-Ming Tsao; Ming-Nan Lin; Tang-Yuan Chu (Medical Microbiology and Immunology, 2015)

EGFR mediates docetaxel resistance in human castration-resistant prostate cancer through the Akt-dependent expression of ABCB1 (MDR1) - Tzyh-Chyuan Hour; Shiu-Dong Chung; Wang-Yi Kang; Ying-Chu Lin; Shu-Ju Chuang; A-Mei Huang; Wen-Jeng Wu; Shu-Pin Huang; Chao-Yuan Huang; Yeong-Shiau Pu (Archives of Toxicology, 2015)

How much does latitude modify temperature–mortality relationship in 13 eastern US cities? - Jianpeng Xiao; Ji Peng; Yonghui Zhang; Tao Liu; Shannon Rutherford; Hualiang Lin; Zhengmin Qian; Cunrui Huang; Yuan Luo; Weilin Zeng; Cordia Chu; Wenjun Ma (International Journal of Biometeorology, 2015)

High seroprevalence of human herpesvirus type 8 in patients with hepatocellular carcinoma - C.-C. Su; K.-C. Tseng; M.-N. Lin; T.-C. Hsieh; T.-Y. Chu (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Genome re-sequencing suggested a weedy rice origin from domesticated indica-japonica hybridization: a case study from southern China - Jie Qiu; Jinwen Zhu; Fei Fu; Chu-Yu Ye; Weidi Wang; Linfeng Mao; Zhangxiang Lin; Li Chen; Haiqiang Zhang; Longbiao Guo; Shen Qiang; Yongliang Lu; et al. (Planta, 2014)

Expression screening and annotation of Sepiella maindroni ink sac cDNA library - WEI-WEI SONG; CHANG-KAO MU; SHAO CHU; YU-YU ZHANG; PING-PING ZHAN; CHUN-LIN WANG (Journal of Genetics, 2014)

Contrasting elevational diversity patterns between eukaryotic soil microbes and plants - Congcong Shen; Wenju Liang; Yu Shi; Xiangui Lin; Huayong Zhang; Xian Wu; Gary Xie; Patrick Chain; Paul Grogan; Haiyan Chu (Ecology, 2014)
The diversity of eukaryotic macroorganisms such as animals and plants usually declines with increasing elevation and latitude. By contrast, the community structure of prokaryotes such as soil bacteria does not generally correlate with elevation or latitude, suggesting that differences in fundamental cell biology and/or body size strongly influence diversity patterns. To distinguish the influences of these two factors, soil eukaryotic microorganism community structure was investigated in six representative vegetation sites along an elevational gradient from forest to alpine tundra on Changbai Mountain in Northeast China, and compared with our previous determination of soil bacterial community structure along the same gradient. Using bar‐coded pyrosequencing, we found strong site differences in eukaryotic microbial community composition. However, diversity of the total eukaryotic microorganism community (or just the fungi or protists alone) did not correlate with elevation. Instead, the patterns of diversity and composition in the total eukaryotic microbial community (and in the protist community alone) were closely correlated with soil pH, suggesting that just as for bacteria, acidity is a particularly important determinant of eukaryotic microbial distributions. By contrast, as expected, plant diversity at the same sites declined along our elevational gradient. These results together suggest that elevational diversity patterns exhibited by eukaryotic microorganisms are fundamentally different from those of plants.

The Association of RAB18 Gene Polymorphism (rs3765133) with Cerebellar Volume in Healthy Adults - Chih-Ya Cheng; Albert C. Yang; Chu-Chung Huang; Mu-En Liu; Ying-Jay Liou; Jaw-Ching Wu; Shih-Jen Tsai; Ching-Po Lin; Chen-Jee Hong (The Cerebellum, 2014)

Identification and expression of the elongator protein 2 (Ajelp2) gene, a novel regeneration-related gene from the sea cucumber Apostichopus japonicus - Yanli Mei; Feng Yao; Yang Wu; Bing Chu; Cheng Cheng; Yan Liu; Xuejie Li; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Yeast Oropharyngeal Colonization in Human Immunodeficiency Virus-Infected Patients in Central Taiwan - Mao-Wang Ho; Yun-Liang Yang; Chih-Chao Lin; Chih-Yu Chi; Hui-Ting Chen; Po-Chang Lin; Li-Yun Hsieh; Chia-Hui Chou; Wen-Li Chu; Chiou-Pyng Wu; Tsai-Ling Lauderdale; Hsiu-Jung Lo (Mycopathologia, 2014)

Galectin-3 contributes to cisplatin-induced myeloid derived suppressor cells (MDSCs) recruitment in Lewis lung cancer-bearing mice - Tian Wang; Zhaohui Chu; Hao Lin; Jingwei Jiang; Xinli Zhou; Xiaohua Liang (Molecular Biology Reports, 2014)

Cingulum Correlates of Cognitive Functions in Patients with Mild Cognitive Impairment and Early Alzheimer’s Disease: A Diffusion Spectrum Imaging Study - Yi-Cheng Lin; Yao-Chia Shih; Wen-Yih I. Tseng; Yu-Hsiu Chu; Meng-Tien Wu; Ta-Fu Chen; Pei-Fang Tang; Ming-Jang Chiu (Brain Topography, 2014)

Cloning and expression analysis of the gene encoding fibrinogen-like protein A, a novel regeneration-related protein from Apostichopus japonicus - Yang Wu; Feng Yao; Yanli Mei; Bing Chu; Cheng Cheng; Yan Liu; Xuejie Li; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

cDNA cloning and molecular characterization of five cellulose synthase A genes from Eucalyptus camaldulensis - Yen Lin; Yu-Ying Kao; Zenn-Zong Chen; Fang-Hua Chu; Jeng-Der Chung (Journal of Plant Biochemistry and Biotechnology, 2014)

Effect of the BDNF Val66Met Polymorphism on Regional Gray Matter Volumes and Cognitive Function in the Chinese Population - Mu-En Liu; Chu-Chung Huang; Mu-Hong Chen; Albert C. Yang; Pei-Chi Tu; Heng-Liang Yeh; Chen-Jee Hong; Jin-Fan Chen; Jen-Ping Hwang; Ching-Po Lin; Shih-Jen Tsai (NeuroMolecular Medicine, 2014)

First study on gene expression of cement proteins and potential adhesion-related genes of a membranous-based barnacle as revealed from Next-Generation Sequencing technology - Hsiu-Chin Lin; Yue Him Wong; Ling Ming Tsang; Ka Hou Chu; Pei-Yuan Qian; Benny K.K. Chan (Biofouling, 2014)

Characterization of S-(+)-linalool synthase from several provenances of Cinnamomum osmophloeum - Yan-Liang Lin; Yi-Ru Lee; Wen-Ke Huang; Shang-Tzen Chang; Fang-Hua Chu (Tree Genetics & Genomes, 2014)

Naphtho[1,2-b]furan-4,5-dione inhibits MDA-MB-231 cell migration and invasion by suppressing Src-mediated signaling pathways - Pei-Chien Tsai; Chiao-Lun Chu; Yaw-Syan Fu; Chih-Hua Tseng; Yeh-long Chen; Long-Sen Chang; Shinne-Ren Lin (Molecular and Cellular Biochemistry, 2014)

Interleukin-1 beta C-511T polymorphism modulates functional connectivity of anterior midcingulate cortex in non-demented elderly Han males - Pei-Chi Tu; Tung-Ping Su; Chu-Chung Huang; Albert C. Yang; Heng-Liang Yeh; Chen-Jee Hong; Ying-Jay Liou; Mu-En Liu; Ching-Po Lin; Shih-Jen Tsai (Brain Structure and Function, 2014)

Genetic variation in alkaloid accumulation in leaves of Nicotiana - Bo Sun; Fen Zhang; Guo-jun Zhou; Guo-hai Chu; Fang-fang Huang; Qiao-mei Wang; Li-feng Jin; Fu-cheng Lin; Jun Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Reply to: Comment on ‘neutron imaging reveals internal plant water dynamics’ - Jeffrey M. Warren; Hassina Bilheux; Chu-Lin Cheng; Edmund Perfect (Plant and Soil, 2013)

Alkanes, compound-specific carbon isotope measures and climate variation during the last millennium from varved sediments of Lake Xiaolongwan, northeast China - Qing Sun; Manman Xie; Liming Shi; Zhuyue Zhang; Yuan Lin; Wenyu Shang; Kaijun Wang; Wei Li; Jiaqi Liu; Guoqiang Chu (Journal of Paleolimnology, 2013)

Responses to booster hepatitis B vaccination are significantly correlated with genotypes of human leukocyte antigen (HLA)-DPB1 in neonatally vaccinated adolescents - Tzu-Wei Wu; Chen-Chung Chu; Tzu-Ying Ho; Huei-Wen Chang Liao; Sheng-Kai Lin; Marie Lin; Hans Hsienhong Lin; Li-Yu Wang (Human Genetics, 2013)

Ex-situ enzyme activity and bacterial community diversity through soil depth profiles in penguin and seal colonies on Vestfold Hills, East Antarctica - Dawei Ma; Renbin Zhu; Wei Ding; Congcong Shen; Haiyan Chu; Xiangui Lin (Polar Biology, 2013)

Inhibition of formyl peptide-stimulated phospholipase D activation by Fal-002-2 via blockade of the Arf6, RhoA and protein kinase C signaling pathways in rat neutrophils - Ya-Ru Tsai; Li-Jiau Huang; Hui-Yi Lin; Yun-Jie Hung; Miau-Rong Lee; Sheng-Chu Kuo; Mei-Feng Hsu; Jih-Pyang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Neutron imaging reveals internal plant water dynamics - Jeffrey M. Warren; Hassina Bilheux; Misun Kang; Sophie Voisin; Chu-Lin Cheng; Juske Horita; Edmund Perfect (Plant and Soil, 2013)

The impact of low-frequency stimulation of subthalamic region on self-generated isometric contraction in patients with Parkinson’s disease - Chiung Chu Chen; Wey Yil Lin; Hsiao Lung Chan; Po Hsun Tu; Shih Tseng Lee; Chin Song Lu; Peter Brown (Experimental Brain Research, 2013)

Predictors of First-Week Mortality in Patients with Acute Spontaneous Cerebellar Hemorrhage - Yung-Tsan Wu; Tsung-Ying Li; Shang-Lin Chiang; Heng-Yi Chu; Shin-Tsu Chang; Liang-Cheng Chen (The Cerebellum, 2013)

Composition and Distribution of Elements and Ultrastructural Topography of a Human Cardiac Calculus - Ching-Li Cheng; Hsiao-Huang Chang; Pei-Jung Huang; Yu-Ting Chu; Shan-Yang Lin (Biological Trace Element Research, 2013)

Influences of Zero-Valent Sulfur on Mercury Methylation in Bacterial Cocultures - Rita A. Kampalath; Chu-Ching Lin; Jennifer A. Jay (Water, Air, & Soil Pollution, 2013)

Comparative and reliability studies of neuromechanical leg muscle performances of volleyball athletes in different divisions - Chi-Pang Un; Kwan-Hwa Lin; Tzyy-Yuang Shiang; En-Chung Chang; Sheng-Chu Su; Hsing-Kuo Wang (European Journal of Applied Physiology, 2013)

Impact of mercury on denitrification and denitrifying microbial communities in nitrate enrichments of subsurface sediments - Yanping Wang; Heather A. Wiatrowski; Ria John; Chu-Ching Lin; Lily Y. Young; Lee J. Kerkhof; Nathan Yee; Tamar Barkay (Biodegradation, 2013)

Crystal structures of rice (Oryza sativa) glyceraldehyde-3-phosphate dehydrogenase complexes with NAD and sulfate suggest involvement of Phe37 in NAD binding for catalysis - Yueh-Chu Tien; Phimonphan Chuankhayan; Yen-Chieh Huang; Chung-De Chen; Jahan Alikhajeh; Shou-Lin Chang; Chun-Jung Chen (Plant Molecular Biology, 2012)

Tectonics of the Middle Triassic intracontinental Xuefengshan Belt, South China: new insights from structural and chronological constraints on the basal décollement zone - Yang Chu; Michel Faure; Wei Lin; Qingchen Wang; Wenbin Ji (International Journal of Earth Sciences, 2012)

Selectivity of N170 in the left hemisphere as an electrophysiological marker for expertise in reading Chinese - Jing Zhao; Su Li; Si-En Lin; Xiao-Hua Cao; Sheng He; Xu-Chu Weng (Neuroscience Bulletin, 2012)

Formation of Volatile Halogenated By-Products During the Chlorination of Oxytetracycline - Bin Xu; He-Zhen Zhu; Yi-Li Lin; Kai-Yuan Shen; Wen-Hai Chu; Chen-Yan Hu; Kang-Ning Tian; Seleli Andrew Mwakagenda; Xiang-Yu Bi (Water, Air, & Soil Pollution, 2012)

Impact of MCP-1 and CCR-2 gene polymorphisms on coronary artery disease susceptibility - Hsiu-Ling Lin; Kwo-Chang Ueng; Yih-Shou Hsieh; Whei-Ling Chiang; Shun-Fa Yang; Shu-Chen Chu (Molecular Biology Reports, 2012)

Geographic distance and pH drive bacterial distribution in alkaline lake sediments across Tibetan Plateau - Jinbo Xiong; Yongqin Liu; Xiangui Lin; Huayong Zhang; Jun Zeng; Juzhi Hou; Yongping Yang; Tandong Yao; Rob Knight; Haiyan Chu (Environmental Microbiology, 2012)
Summary Continent‐scale biogeography has been extensively studied in soils and marine systems, but little is known about biogeographical patterns in non‐marine sediments. We used barcode pyrosequencing to quantify the effects of local geochemical properties and geographic distance for bacterial community structure and membership, using sediment samples from 15 lakes on the Tibetan Plateau (4–1670 km apart). Bacterial communities were surprisingly diverse, and distinct from soil communities. Four of 26 phyla detected were dominant: Proteobacteria , Bacteroidetes , Firmicutes and Actinobacteria , albeit 20.2% of sequences were unclassified at the phylum level. As previously observed in acidic soil, pH was the dominant factor influencing alkaline sediment community structure, phylotype richness and phylogenetic diversity. In contrast, archaeal communities were less affected by pH. More geographically distant sites had more dissimilar communities ( r = 0.443, P = 0.030). Variance partitioning analysis showed that geographic distance (historical contingencies) contributed more to bacterial community variation (12.2%) than any other factor, although the environmental factors explained more variance when combined (28.9%). Together, our results show that pH is the best predictor of bacterial community structure in alkaline sediments, and confirm that both geographic distance and chemical factors govern bacterial biogeography in lake sediments.

Exploring a sulfone linker utilizing trimethyl aluminum as a cleavage reagent: solid-phase synthesis of sulfonamides and ureas - Tsai-Wen Chung; Chih-Hau Chen; Chu-Chung Lin; Hsien-Jen Wu; Chung-Ming Sun; Wen-Sheng Chung (Molecular Diversity, 2012)

Erratum to: Association between gout and polymorphisms in GCKR in male Han Chinese - Jing Wang; Shiguo Liu; Binbin Wang; Zhimin Miao; Lin Han; Nan Chu; Kun Zhang; Dongmei Meng; Changgui Li; Xu Ma (Human Genetics, 2012)

Association between gout and polymorphisms in GCKR in male Han Chinese - Jing Wang; Shiguo Liu; Binbin Wang; Zhimin Miao; Lin Han; Nan Chu; Kun Zhang; Dongmei Meng; Changgui Li; Xu Ma (Human Genetics, 2012)

A System Dynamic Model and Sensitivity Analysis for Simulating Domestic Pollution Removal in a Free-Water Surface Constructed Wetland - Yung-Chieh Wang; Yu-Pin Lin; Chun-Wei Huang; Li-Chi Chiang; Hone-Jay Chu; Wen-Sheng Ou (Water, Air, & Soil Pollution, 2012)

Hyperglycemia as a Predictor of Poor Outcome at Discharge in Patients with Acute Spontaneous Cerebellar Hemorrhage - Yung-Tsan Wu; Tsung-Ying Li; Shao-Chi Lu; Liang-Cheng Chen; Heng-Yi Chu; Shang-Lin Chiang; Shin-Tsu Chang (The Cerebellum, 2012)

Chronic cigarette smoke exposure enhances brain-derived neurotrophic factor expression in rats with traumatic brain injury - I-Neng Lee; Martin Hsiu-Chu Lin; Chiu-Yen Chung; Ming-Hsueh Lee; Hsu-Huei Weng; Jen-Tsung Yang (Metabolic Brain Disease, 2012)

The polymorphisms of IL-4, IL-4R and IL-13 genes and bladder cancer risk in a Chinese population: a case–control study - Haiyan Chu; Lan Ma; Meilin Wang; Danni Shi; Chao Qin; Lin Yuan; Changjun Yin; Zhengdong Zhang (Molecular Biology Reports, 2012)

Cytology and ultrastructure of interactions between Ustilago esculenta and Zizania latifolia - Jing-Ze Zhang; Fu-Qiang Chu; De-Ping Guo; Kevin D. Hyde; Guang-Lin Xie (Mycological Progress, 2012)

Bp5250 inhibits vascular endothelial growth factor-induced angiogenesis and HIF-1α expression on endothelial cells - Kuan-Ting Lin; Jin-Cherng Lien; Ching-Hu Chung; Sheng-Chu Kuo; Tur-Fu Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Involvement of OsNPR1/NH1 in rice basal resistance to blast fungus Magnaporthe oryzae - Jia-Xun Feng; Lin Cao; Juan Li; Cheng-Jie Duan; Xue-Mei Luo; Ning Le; Haihong Wei; Shujia Liang; Chengcai Chu; Qinghua Pan; Ji-Liang Tang (European Journal of Plant Pathology, 2011)

Biosynthesis of 2-amino-2,3-dimethylbutyramide by nitrile hydratase from a newly isolated cyanide-resistant strain of Rhodococcus qingshengii - Zhi-Jian Lin; Ren-Chao Zheng; Yu-Guo Zheng; Yin-Chu Shen (Biotechnology Letters, 2011)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

A Review of the Major Penaeid Shrimp EST Studies and the Construction of a Shrimp Transcriptome Database Based on the ESTs from Four Penaeid Shrimp - Jiann-Horng Leu; Shu-Hwa Chen; Yu-Bin Wang; Yen-Chen Chen; Sheng-Yao Su; Chung-Yen Lin; Jan-Ming Ho; Chu-Fang Lo (Marine Biotechnology, 2011)

Diversity of killer cell immunoglobulin-like receptor genes in four ethnic groups in China - Yufeng Yao; Lei Shi; Yufen Tao; Keqin Lin; Shuyuan Liu; Liang Yu; Zhaoqing Yang; Wen Yi; Xiaoqin Huang; Hao Sun; Jiayou Chu; Li Shi (Immunogenetics, 2011)

Retrieval of chlorophyll a concentration from a fluorescence enveloped area using hyperspectral data - Fen-Fen Liu; Chu-Qun Chen; Shi-Lin Tang; Da-Zhao Liu (International Journal of Remote Sensing, 2011)

Late Mesozoic extensional tectonics of the Liaodong Peninsula massif: Response of crust to continental lithosphere destruction of the North China Craton - Wei Lin; QingChen Wang; Jun Wang; Fei Wang; Yang Chu; Ke Chen (Science China Earth Sciences, 2011)

HLA polymorphism of the Zhuang population reflects the common HLA characteristics among Zhuang-Dong language-speaking populations - Li Shi; Xiao-qin Huang; Lei Shi; Yu-fen Tao; Yu-feng Yao; Liang Yu; Ke-qin Lin; Wen Yi; Hao Sun; Katsushi Tokunaga; Jia-you Chu (Journal of Zhejiang University-SCIENCE B, 2011)

A single amino acid substitution in PthA of Xanthomonas axonopodis pv. citri altering canker formation on grapefruit leaves - Hsin-Cheng Lin; Mu-Kuei Chu; Yuang-Chuen Lin; Wen-Ling Deng; Hsiang Chang; Shih-Tien Hsu; Kuo-Ching Tzeng (European Journal of Plant Pathology, 2011)

Monitoring and identification of spatiotemporal landscape changes in multiple remote sensing images by using a stratified conditional Latin hypercube sampling approach and geostatistical simulation - Yu-Pin Lin; Hone-Jay Chu; Yu-Long Huang; Chia-Hsi Tang; Shahrokh Rouhani (Environmental Monitoring and Assessment, 2011)

Lipopolysaccharide-stimulated activation of murine DC2.4 cells is attenuated by n-butylidenephthalide through suppression of the NF-κB pathway - Ru-Huei Fu; Horng-Jyh Hran; Ching-Liang Chu; Chin-Mao Huang; Shih-Ping Liu; Yu-Chi Wang; Ya-Hsien Lin; Woei-Cherng Shyu; Shinn-Zong Lin (Biotechnology Letters, 2011)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

Using a hybrid approach to optimize experimental network design for aquifer parameter identification - Liang-Cheng Chang; Hone-Jay Chu; Yu-Pin Lin; Yu-Wen Chen (Environmental Monitoring and Assessment, 2010)

Effects of land cover changes induced by large physical disturbances on hydrological responses in Central Taiwan - Nien Ming Hong; Hone-Jay Chu; Yu-Pin Lin; Dung-Po Deng (Environmental Monitoring and Assessment, 2010)

Application of System Dynamics on Shallow Multipurpose Artificial Lakes: A Case Study of Detention Pond at Tainan, Taiwan - Hone-Jay Chu; Liang-Cheng Chang; Yu-Pin Lin; Yung-Chieh Wang; Yu-Wen Chen (Environmental Modeling & Assessment, 2010)

Probiotic Lactobacillus casei Expressing Human Lactoferrin Elevates Antibacterial Activity in the Gastrointestinal Tract - Hsiao-Ling Chen; Yi-Wen Lai; Chua-Shun Chen; Te-Wei Chu; Willie Lin; Chih-Ching Yen; Ming-Fong Lin; Ming-Yu Tu; Chuan-Mu Chen (BioMetals, 2010)

Metal Concentrations in Sediments of the Tamsui River, Flows Through Central Metropolitan Taipei - Dong-Shang Lai; Jye-Bin Lin; Wen-Shan Liu; Lung-Kwang Pan; Kuang-Hua Chu; Chien-Yi Chen; Ding-Bang Lin (Bulletin of Environmental Contamination and Toxicology, 2010)

Veterinary antibiotic sorption to agroforestry buffer, grass buffer and cropland soils - Bei Chu; Keith W. Goyne; Stephen H. Anderson; Chung-Ho Lin; Ranjith P. Udawatta (Agroforestry Systems, 2010)

Variation of biomass and kinetic parameters for nitrifying species in the TNCU3 process at different aerobic hydraulic retention times - Tzu-Yi Pai; Ren-Jie Chiou; Chwen-Jeng Tzeng; Tung-Sheng Lin; Shan-Chun Yeh; Pao-Jui Sung; Chu-Hui Tseng; Chia-Ho Tsai; Yao-Sheng Tsai; Wen-Jui Hsu; Yuh-Ling Wei (World Journal of Microbiology and Biotechnology, 2010)

Role of Diverse Non-Systemic Fungal Endophytes in Plant Performance and Response to Stress: Progress and Approaches - Zhi-lin Yuan; Chu-long Zhang; Fu-cheng Lin (Journal of Plant Growth Regulation, 2010)

Increasing trend of the incidence of esophageal squamous cell carcinoma, but not adenocarcinoma, in Taiwan - Ching-Liang Lu; Hui-Chu Lang; Jiing-Chyuan Luo; Chun-Chu Liu; Han-Chieh Lin; Full-Young Chang; Shou-Dong Lee (Cancer Causes & Control, 2010)

Fractionated evaluation of immunohistochemical hormone receptor expression enhances prognostic prediction in breast cancer patients treated with tamoxifen as adjuvant therapy - Ching-hung Lin; Huang-chun Lien; Fu-chang Hu; Yen-shen Lu; Sung-hsin Kuo; Ling-chu Wu; San-lin You; Ann-lii Cheng; King-jen Chang; Chiun-sheng Huang (Journal of Zhejiang University-SCIENCE B, 2010)

Mitigation of micro vibration by viscous dampers - Tzu-Kang Lin; Chun-Chung Chen; Kuo-Chun Chang; Chu-Chieh Jay Lin; Jenn-Shin Hwang (Earthquake Engineering and Engineering Vibration, 2009)

A note on reviving the Goddard Satellite-based Surface Turbulent Fluxes (GSSTF) dataset - Chung-Lin Shie; Long S. Chiu; Robert Adler; Eric Nelkin; I. -I. Lin; Pingping Xie; Feng-Chin Wang; R. Chokngamwong; William Olson; D. Allen Chu (Advances in Atmospheric Sciences, 2009)

Atmospheric Aerosols over a Southwestern Region of Texas - Paul Chiou; Wei Tang; Che-Jen Lin; Hsing-Wei Chu; Rafael Tadmor; T. C. Ho (Environmental Modeling & Assessment, 2009)

Atmospheric Aerosol over a Southeastern Region of Texas: Chemical Composition and Possible Sources - Paul Chiou; Wei Tang; Che-Jen Lin; Hsing-Wei Chu; T. C. Ho (Environmental Modeling & Assessment, 2009)

Identification and Characterization of a Chitinase-Produced Bacillus Showing Significant Antifungal Activity - Liang Xiao; Chi-chu Xie; Jun Cai; Zhi-Jie Lin; Yue-Hua Chen (Current Microbiology, 2009)

Sterol production and phytosterol bioconversion in two species of heterotrophic protists, Oxyrrhis marina and Gyrodinium dominans - Fu-Lin Evelyn Chu; Eric D. Lund; Paul R. Littreal; Kate E. Ruck; Ellen Harvey; Jean-René Le Coz; Yanic Marty; Jeanne Moal; Philippe Soudant (Marine Biology, 2008)

Control of Growth Factor Networks by Heparan Sulfate Proteoglycans - Kimberly Forsten-Williams; Chia Lin Chu; Michael Fannon; Jo Ann Buczek-Thomas; Matthew A. Nugent (Annals of Biomedical Engineering, 2008)

Dry deposition study by using dry deposition plate and water surface sampler in Shalu, central Taiwan - Chia-Chun Chu; Guor-Cheng Fang; Jhy-Cherng Chen; I-Lin Yang (Environmental Monitoring and Assessment, 2008)

Seasonal change and correlation with environmental parameters for 2-MIB in Feng-Shen Reservoir, Taiwan - Shu-Chu Tung; Tsair-Fuh Lin; Feng-Cheng Yang; Chia-Lin Liu (Environmental Monitoring and Assessment, 2008)

Chemical constituents of Antrodia camphorata submerged whole broth - Yi-Yuan Shao; Chin-Chu Chen; Hsin-Yi Wang; Hsi-Lin Chiu; Tzong-Hsiung Hseu; Yueh-Hsiung Kuo (Natural Product Research, 2008)

Mechanism(s) of long chain n-3 essential fatty acid production in two species of heterotrophic protists: Oxyrrhis marina and Gyrodinium dominans - Eric D. Lund; Fu-Lin E. Chu; Ellen Harvey; Richard Adlof (Marine Biology, 2008)

White-spot disease of Chinese soft-shelled turtles (Trionyx sinens) caused by Paecilomyces lilacinus - Xiao-liang Li; Chu-long Zhang; Wei-huan Fang; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2008)

T-2 toxin-induced apoptosis involving Fas, p53, Bcl-xL, Bcl-2, Bax and caspase-3 signaling pathways in human chondrocytes - Jing-hong Chen; Jun-ling Cao; Yong-lie Chu; Zhi-lun Wang; Zhan-tian Yang; Hong-lin Wang (Journal of Zhejiang University-SCIENCE B, 2008)

The trend on runoff variations in the Lhasa River Basin - Xuedong Lin; Yili Zhang; Zhijun Yao; Tongliang Gong; Hong Wang; Duo Chu; Linshan Liu; Fei Zhang (Journal of Geographical Sciences, 2008)

Development of a molecular marker for a bruchid (Callosobruchus chinensis L.) resistance gene in mungbean - Huei-Mei Chen; Chien-An Liu; C. George Kuo; Ching-Mei Chien; Horng-Chi Sun; Chung-Chu Huang; Yu-Chung Lin; Hsin-Mei Ku (Euphytica, 2007)

Analysis of the agglutinating activity from unicellular algae - Chun-Yao Chu; Rang Huang; Lian-Ping Lin (Journal of Applied Phycology, 2007)

Dissipation of Pendimethalin in the Garlic (Allium sativum L.) under Subtropical Condition - H. T. Lin; S. W. Chen; C. J. Shen; C. Chu (Bulletin of Environmental Contamination and Toxicology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Genetic analysis of an attenuated Papaya ringspot virus strain applied for cross-protection - Chu-Hui Chiang; Chun-Yee Lee; Ching-Hsien Wang; Fuh-Jyh Jan; Shih-Shun Lin; Tsung-Chi Chen; Joseph A. J. Raja; Shyi-Dong Yeh (European Journal of Plant Pathology, 2007)

Short-term decomposition of 14C-labelled glucose in a fluvo-aquic soil as affected by lanthanum amendment - Haiyan Chu; Jianguo Zhu; Xiangui Lin; Rui Yin; Zubin Xie; Zhihong Cao; Takeshi Fujii (Biology and Fertility of Soils, 2007)

Expression of truncated phosphoproteins of Nipah virus and Hendra virus in Escherichia coli for the differentiation of henipavirus infections - Ji-Ming Chen; Koon Chu Yaiw; Meng Yu; Lin-Fa Wang; Qing-Hua Wang; Gary Crameri; Zhi-Liang Wang (Biotechnology Letters, 2007)

Efficient purification of transglutaminase from recombinant Streptomyces platensis at various scales - Shie-Jea Lin; Yi-Fang Hsieh; Pei-Ming Wang; Wen-Shen Chu (Biotechnology Letters, 2006)

Over-expressed estrogen receptor-α up-regulates hTNF-α gene expression and down-regulates β-catenin signaling activity to induce the apoptosis and inhibit proliferation of LoVo colon cancer cells - Hsi-Hsien Hsu; Sue-Fei Cheng; Li-Mien Chen; Jer-Yu Liu; Chun-Hsien Chu; Yi-Jiun Weng; Zih-Ying Li; Chung-Sheng Lin; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Cardiomyoblast apoptosis induced by insulin-like growth factor (IGF)-I resistance is IGF-II dependent and synergistically enhanced by angiotensin II - Wei-Wen Kuo; Chung-Jung Liu; Li-Ming Chen; Chieh-Hsi Wu; Chun-Hsien Chu; Jer-Yuh Liu; Min-Chi Lu; James A. Lin; Shin-Da Lee; Chih-Yang Huang (Apoptosis, 2006)

A tissue culture system for different germplasms of indica rice - Xiaojia Ge; Zhaohui Chu; Yongjun Lin; Shiping Wang (Plant Cell Reports, 2006)

The Highly Charged Region of Plant β-type Phosphatidylinositol 4-kinase is Involved in Membrane Targeting and Phospholipid Binding - Ying Lou; Hui Ma; Wen-Hui Lin; Zhao-Qing Chu; Bernd Mueller-Roeber; Zhi-Hong Xu; Hong-Wei Xue (Plant Molecular Biology, 2006)

Trophic modification of essential fatty acids by heterotrophic protists and its effects on the fatty acid composition of the copepod Acartia tonsa - Adriana J. Veloza; Fu-Lin E. Chu; Kam W. Tang (Marine Biology, 2006)

OsGLU1, A Putative Membrane-bound Endo-1,4-ß-D-glucanase from Rice, Affects Plant Internode Elongation - Hua-Lin Zhou; Si-Jie He; Yang-Rong Cao; Tao Chen; Bao-Xing Du; Cheng-Cai Chu; Jin-Song Zhang; Shou-Yi Chen (Plant Molecular Biology, 2006)

A fine physical map of the rice chromosome 5 - Chia-Hsiung Cheng; Mei-Chu Chung; Shu-Mei Liu; Shi-Kuang Chen; Fang-Yi Kao; Shu-Jen Lin; Shin-Hsin Hsiao; I-Chieh Tseng; Yue-Ie C. Hsing; Hong-Pang Wu; Ching-San Chen; Jei-Fu Shaw; et al. (Molecular Genetics and Genomics, 2005)

Chilling stress suppresses chloroplast development and nuclear gene expression in leaves of mung bean seedlings - Ming-Tzong Yang; Shu-Ling Chen; Chu-Yung Lin; Yih-Ming Chen (Planta, 2005)

Mitochondrial DNA Diversity in two populations of Taiwanese macaque (Macaca cyclopis) - Jui-Hua Chu; Yao-Sung Lin; Hai-Yin Wu (Conservation Genetics, 2005)

Haemagglutinating and antibiotic activities of freshwater microalgae - C.Y. Chu; W.R. Liao; R. Huang; L.P. Lin (World Journal of Microbiology and Biotechnology, 2004)

Characterization of the genomic structures and selective expression profiles of nine class I small heat shock protein genes clustered on two chromosomes in rice (Oryza sativa L.) - Jiahn-Chou Guan; Tsung-Luo Jinn; Ching-Hui Yeh; Shi-Pin Feng; Yih-Ming Chen; Chu-Yung Lin (Plant Molecular Biology, 2004)

The blockade of formyl peptide-induced respiratory burst by 2',5'-dihydroxy-2-furfurylchalcone involves phospholipase D signaling in neutrophils - Jih-Pyang Wang; Ling-Chu Chang; Mei-Feng Hsu; Chun-Nan Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Ferredoxin from sweet pepper (Capsicum annuum L.) intensifying harpinpss-mediated hypersensitive response shows an enhanced production of active oxygen species (AOS) - Badri Venkata Dayakar; Hao-Jan Lin; Cheng-Hsien Chen; Mang-Jye Ger; Bor- Heng Lee; Chia-Hwei Pai; David Chow; Hsiang-En Huang; Shaw-Yhi Hwang; Mei-Chu Chung; Teng-Yung Feng (Plant Molecular Biology, 2003)

Establishment of red fluorescent protein-tagged HeLa tumor metastasis models: Determination of DsRed2 insertion effects and comparison of metastatic patterns after subcutaneous, intraperitoneal, or intravenous injection - Jau-Yeong Lu; Hui-Chun Chen; Ricky Yuan-Yuan Chu; Tsu-Chun Emma Lin; Ping-I Hsu; Ming-Shyan Huang; Ching-Jiunn Tseng; Michael Hsiao (Clinical & Experimental Metastasis, 2003)

Lactococcus garvieae , a cause of disease in grey mullet, Mugil cephalus L., in Taiwan - S‐C Chen; L‐L Liaw; H‐Y Su; S‐C Ko; C‐Y Wu; H‐C Chaung; Y‐H Tsai; K‐L Yang; Y‐C Chen; T‐H Chen; G‐R Lin; S‐Y Cheng; et al. (Journal of Fish Diseases, 2002)

The Use of in Vitro Metabolic Stability for Rapid Selection of Compounds in Early Discovery Based on Their Expected Hepatic Extraction Ratios - Yau Yi Lau; Gopal Krishna; Nathan P. Yumibe; Diane E. Grotz; Elpida Sapidou; Laura Norton; Inhou Chu; Cliff Chen; A. D. Soares; Chin-Chung Lin (Pharmaceutical Research, 2002)

Inhibitory effect of berberine on tert -butyl hydroperoxide-induced oxidative damage in rat liver - Jin-Ming Hwang; Chau-Jong Wang; Feu-Pi Chou; Tsui-Hwa Tseng; Yih-Shou Hsieh; Wea-Lung Lin; Chia-Yih Chu (Archives of Toxicology, 2002)

Topaz–albite granites and rare-metal mineralization in the Limu District, Guangxi Province, southeast China - Jin-Chu Zhu; Ren-Ke Li; Fu-Chun Li; Xiao-Lin Xiong; Feng-Ying Zhou; Xiao-Long Huang (Mineralium Deposita, 2001)

Molecular epidemiology of enterovirus 71 in Taiwan - P.-Y. Chu; K.-H. Lin; K.-P. Hwang; L.-C. Chou; C.-F. Wang; S.-R. Shih; J.-R. Wang; Y. Shimada; H. Ishiko (Archives of Virology, 2001)

Translational Regulation as a Novel Mechanism for the Development of Cellular Drug Resistance - John C. Schmitz; Jun Liu; Xiukun Lin; Tian-min Chen; Wu Yan; Ningwen Tai; Ashwin Gollerkeri; Edward Chu (Cancer and Metastasis Reviews, 2001)

Polymorphic microsatellite loci and low-invasive DNA sampling inMacaca cyclopis - Jui-Hua Chu; Hai-Yin Wu; Yi-Ju Yang; Osamu Takenaka; Yao-Sung Lin (Primates, 1999)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Functional activity of sporamin from sweet potato (Ipomoea batatas Lam.): a tuber storage protein with trypsin inhibitory activity - Kai-Wun Yeh; Jen-Chih Chen; Mei-In Lin; Yih-Ming Chen; Chu-Yung Lin (Plant Molecular Biology, 1997)

Effects of tributyltin on defense-related activities of oyster hemocytes - William S. Fisher; Arieh Wishkovsky; Fu -Lin E. Chu (Archives of Environmental Contamination and Toxicology, 1990)